Small but big player: the important role of microRNAs in legume crops - Flavia Thiebaut; Maria Clara Urquiaga; Paula Machado de Araújo; Aislan de Carvalho Vivarini; Clicia Grativol (Molecular Genetics and Genomics, 2026)
Legumes are essential components of global cropping systems due to their nutritional value and contribution to sustainable agriculture. Among the regulatory molecules, small RNAs (sRNAs), particularly microRNAs (miRNAs), play crucial roles in plant development and in responses to biotic and abiotic stresses. miRNAs regulate genes involved in diverse developmental processes, including nodule formation, which is fundamental for the nitrogen-fixing symbiosis that characterizes legumes. Functional studies have demonstrated that miRNAs are key modulators of plant defense, contributing to resistance against pathogens and environmental challenges. Moreover, miRNAs also participate in cross-kingdom communication, such as plant–bacteria interactions, influencing symbiotic efficiency. Advances in molecular biology have enabled the manipulation of miRNAs and their targets for crop improvement. Current approaches include the design of artificial miRNAs (amiRNA), modulation of miRNA expression through miRNA-encoded peptides, genome editing of non-coding genes using CRISPR/Cas9, and the application of RNA interference (RNAi) technology. Together, these strategies highlight the potential of miRNA-based tools in plant biotechnology. A deeper understanding of the molecular mechanisms governing miRNA-mediated gene silencing will provide powerful resources for optimizing legume productivity and resilience within sustainable agricultural systems.

An integrative bioinformatics framework for functional annotation and prioritization of hypothetical proteins in Bacillus thuringiensis relevant to biological pest control - Vilmar Machado; Marcelo Rios Kwecko; Maria Alice Peglow Dos Reis; Jose Galian (Brazilian Journal of Microbiology, 2026)
Bacillus thuringiensis is a widely used biological control agent whose genomes contain a substantial proportion of coding sequences annotated as hypothetical proteins, limiting functional interpretation and hindering their exploitation in biotechnology and genetic engineering. Here, we present an integrative and reproducible bioinformatics workflow for the systematic annotation and prioritization of hypothetical proteins from three B. thuringiensis serovars (Kurstaki, Pakistani, and Toumanoffi). The pipeline combines consensus-based functional annotation, virulence-associated prediction, subcellular localization analysis, pathogen-enrichment statistics, and structure-aware prioritization. Sequential filtering reduced an initial dataset of 2,052 hypothetical proteins to 11 non-redundant candidates supported by convergent computational evidence. Prioritized proteins included SGNH/GDSL hydrolases, iron–sulfur cluster repair proteins, HNH nucleases, transcriptional regulators, and envelope-associated proteins potentially related to stress adaptation and host-associated processes. Localization analyses identified extracellular, membrane-associated, and cytoplasmic candidates, suggesting participation in complementary adaptive functions. Structural prioritization based on physicochemical stability, topology-associated features, and docking-readiness criteria identified six proteins with favorable profiles for downstream structural and functional analyses. Rather than assigning definitive biological functions, this study provides a transferable computational framework for reducing the functional uncertainty associated with hypothetical proteins and supporting rational candidate selection for functional genomics and biotechnological applications in Bacillus and related bacterial systems.

Occurrence of mollicutes infection and molecular identification of ureaplasmas from the reproductive tract of dairy cattle kept under tropical conditions - Ana Carolina Nunes de Morais; Danielle Regis Pires; Leandro dos Santos Machado; Lucas de Figueiredo Cardoso Barbosa; Pedro Panzenhagen; Mario Felipe Alvarez Balaro; Guilherme Nunes de Souza; Maria Lucia Barreto; Elmiro Rosendo do Nascimento; Nathalie Da Cunha (Brazilian Journal of Microbiology, 2026)
Bacterial diseases associated with the Mollicutes class can lead to decreased milk production and reproductive disorders in cattle, causing significant economic losses and compromising animal welfare. This study aimed to investigate the presence of Mollicutes and Ureaplasma diversum in the reproductive tract of dairy cows and determine the associated risk factors, as well as identify circulating strains of Ureaplasma in herds. Vaginal swab samples from 392 lactating cows were subjected to generic polymerase chain reaction (PCR) for Mollicutes detection and specific PCR for U. diversum identification. An epidemiological questionnaire was used to analyze the risk factors. Positive samples for U. diversum were sequenced from the intergenic region 16–23 S rRNA and multiple alignments were performed to generate a phylogram. The geographical coordinates of the municipalities where the herds were located were used for the phylogeographic analysis. Mollicutes and U. diversum were detected in 45.4% (178/392) and 21.7% (85/392) of the samples, respectively, with a herd-level prevalence of 88.8%. Age group heifers (OR = 4.006; CI 1.283–12.510) and history of genital lesions (OR = 5.564; CI 3.011–10.284) were the biggest associated risk factors, in addition to other effects. The frequency of these agents was high and different strains of U. diversum were found to be spread throughout the studied states, likely due to the extensive animal movement network.

[Lys3, Lys4] M-PONTX-Dq3a [1–15]: a selective dinoponeratoxin-derived peptide that disrupts parasite membranes and inhibits TcGAPDH activity in Trypanosoma cruzi - Evelline Araújo Edson; Emanuel Paula Magalhães; Márcia Machado Marinho; Emmanuel Silva Marinho; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Alice Maria Costa Martins (Toxicon, 2026)

Feline sporotrichosis hotspots during a period of declining notifications: A surveillance-sensitive analysis in hyperendemic Rio de Janeiro - Vitor Campos Assumpção de Amarante; Angelita Reis Gomes; Bianca Conrad Bohm; Maysa Seibert de Leão; Liandra Scherer Schmegel; Maria Enilda Borges Machado; Renata Osório de Faria; Isabella Dib Ferreira Gremião; Sandro Antonio Pereira; Fabio Raphael Pascoti Bruhn (Preventive Veterinary Medicine, 2026)

The hidden power of trees: Do local trees combat excessive body weight in Southern Europe? - Ana C. Lourenço; Helena G. Nogueira; Daniela Rodrigues; Augusta Gama; Aristides M. Machado-Rodrigues; Maria Raquel G. Silva; Cristina Padez (Urban Forestry & Urban Greening, 2026)

Modeling northeastern Brazilian swells combining onshore microseismic noise, oceanographic, and meteorological data - Maria Rayla dos Santos; Aderson Farias do Nascimento; Weber Andrade Gonçalves; Marcio Machado Cintra; Marcus André Silva (Estuarine, Coastal and Shelf Science, 2026)

Aqueous grape pomace extract suppresses seed germination and seedling responses of the invasive plant Leucaena leucocephala (Fabaceae) - Rosivaldo Machado da Silva Junior; Lidiane Machado Dionizio; Flivia Fernandes De Jesus; Venâncio Guimarães Silva; Maria Eduarda Coutinho; Valeska Cristina Souza Silva De Assis; Katiane Santiago Silva Benett; Francival Cardoso Félix (Plant Biosystems, 2026)

Multielement Composition and in Vitro Bioaccessibility in Brazilian Edible Floral Supplement Capsules Containing Dandelion and Hibiscus - Taís Lorena Santos Fiais; Jorge Machado Freitas Junior; Ygor Felipe Garcez Brito; Eliabe Sousa da Silva; Clícia Maria de Jesus Benevides; Thaís Luz de Souza; Jamille Santos Santana; Aníbal de Freitas Santos Júnior (Biological Trace Element Research, 2026)

Gonad Status, Condition Index and Biochemical Composition of the Yellow Clam Amarilladesma mactroides - Melissa Herrera-Perez; Débora Machado Fracalossi; Virginia Fonseca Pedrosa; Renata Oselame Nobrega; José Maria Monserrat; Luis Alberto Romano; Ronaldo Olivera Cavalli (Fishes, 2026)
The yellow clam, Amarilladesma mactroides, is an abundant component of the intertidal infauna of the southwestern Atlantic Ocean and an important source of food and income for local communities. In recent years, this species has been increasingly affected by anthropogenic and environmental pressures, contributing to the decline and collapse of several populations. In this study, we characterized the reproductive cycle of A. mactroides in the southernmost region of Brazil using standard approaches, including gonadal histology and biometric parameters, complemented by analyses of proximal composition and fatty acid profiles. Monthly samples of ≥100 clams were collected from October 2021 to September 2022. The results revealed two distinct reproductive peaks: a major peak from October to December (austral spring–summer) and a less pronounced peak from May to July (autumn–winter). Although gonadal histology, particularly oocyte diameter, provided the primary evidence for defining these reproductive peaks, the condition index and concentrations of total lipids and n-3 polyunsaturated fatty acids (n-3 PUFA) also proved useful indicators of reproductive activity. These findings provide new insights into the reproductive dynamics of A. mactroides in southern Brazil and may contribute to the development of strategies for the sustainable management, conservation and aquaculture of this ecologically and socioeconomically important bivalve.

Governing urban heat adaptation and green inequality: Toward a thermal justice architecture — A scoping review - Adriano Bressane; Mirela Beatriz Silva; Anna Maria Galvão Carneiro Lyra; Vivian Martins Machado; Julia Simões Neves da Silva; Ana Clara de Souza; Ricardo Almendra (Urban Forestry & Urban Greening, 2026)

Linoleic acid enhances prostaglandin signaling and IFNT expression in bovine trophoblast cells in vitro - Lucas de Oliveira Bezerra; Laura Chuba Machado Rolniche; Adriano Felipe Mendes; Amanda Guimarães da Silva; Isabella Rio Feltrin; Karine Galhego Morelli; Catarina Lazarevicius Prestes; Maria Eduarda Rocha Pinto; Mariângela Bueno Cordeiro Maldonado; Cecilia Constantino Rocha; Alan Ealy; Vitor Mercadante; et al. (Theriogenology, 2026)

Agroforestry systems enhance the functional diversity of soil macrofauna in southeastern Brazil - Emmeline Machado França; Irene Maria Cardoso; André Mundstock Xavier de Carvalho; Frederico Falcão Salles; Edvaldo Renner da Costa Cardoso; Waldênia de Melo Moura; Emanuelle Mercês Barros Soares (Geoderma Regional, 2026)

Cryopreservation-induced proteomic alterations in Pêga donkey (Equus asinus) spermatozoa - Camilo Jose Ramirez-Lopez; Isabella Cristina Tolêdo Alves Costa; Wassali Valadares de Sousa; Yara Martins da Silva; Faider Alberto Castano Villadiego; Tayna Bolsam da Silva; Renner Philipe Rodrigues Carvalho; Arabela Guedes de Azevedo Viana; Jose Carlos Montes-Vergara; Mariana Machado-Neves; Simone Eliza Facioni Guimaraes; Fabio Cesar Sousa Nogueira; et al. (Cryobiology, 2026)

Optimized surface decontamination of gametophores for axenic in vitro culture of the moss Warnstorfia sarmentosa (Wahlenb.) Hedenäs, with application to other polar mosses - Stephan Machado Dohms; Isabela Lopes Figueredo Bravo; Thaíssa Pereira Mendes; Maria Karollina Gonçalves; Maria Clara Menezes Mello; Izabele Prudência Oliveira Braga; Giovanna Melo Nishitani; Ana Júlia da Matta Maciel; Ana Laura Pereira Lourenço; Lorena Ferreira Peixoto; Marcelo Henrique Soller Ramada (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)
Mosses are non-vascular plants widely distributed across multiple habitats and capable of thriving in extreme environments, such as Antarctica and the Arctic. However, knowledge of the genetic, metabolic, and molecular diversity of polar species remains limited, necessitating a better understanding of their mechanisms of response to harsh conditions. In this context, axenic in vitro cultivation under laboratory conditions is a powerful tool for plant sciences to elucidate physiological and biochemical responses. Nevertheless, in vitro cultivation of polar mosses can be challenging, as most species lack viable sporophytes or are predominantly sterile. Alternatively, gametophores can be used; however, many fail to withstand surface decontamination or are subsequently overrun by microorganisms. To establish an efficient and replicable decontamination method, we compared the efficacy of treatments applied to field‑collected gametophores from three sites and pre‑cultured leafy shoots of Warnstorfia sarmentosa (Wahlenb.) Hedenäs as a model species, using different concentrations of sodium dichloroisocyanurate (NaDCC) and sodium hypochlorite (NaClO). Explants derived from pre-cultured tissue achieved an overall success rate of 64.1%, compared with 12.7% for field-collected material, and success among field samples varied markedly across collection sites (0–28%). For pre-cultured material, NaDCC (0.1% and 0.5%) was more effective than NaClO (0.5% and 1%) ( p = 0.0309). This optimized method was subsequently applied to other species. Currently, 33 ecotypes from 12 polar moss species are successfully maintained under axenic conditions, providing a valuable resource for applications including stress tolerance studies, metabolite profiling, ex situ conservation of endangered taxa, and biotechnological exploitation.

Evaluation of the antimicrobial and NorA and MepA efflux pump inhibitory activity of a hydrazone derivative of hydralazine against Staphylococcus aureus - Karla Susanna Tavares Grangeiro Belém; Janaina Esmeraldo Rocha; Ana Joyce Morais Bento; Jaiza Maria Lima Dias; Henrique Douglas Melo Coutinho; Francisco das Chagas Lima Pinto; Ramon Róseo Paula Pessoa Bezerra de Menezes; Mateus Edson da Silva; Emmanuel Silva Marinho; Marcia Machado Marinho; Hélcio Silva dos Santos (Archives of Microbiology, 2026)

Estimation of anthropogenic heat flux in a city in the Central Amazon - Carla de Souza Farias; Maria Juliana de Melo Monte; Denisi Holanda Hall; Joice de Jesus Machado; Bruno Takeshi Tanaka Portela; Vinicius Buscioli Capistrano; Cléo Quaresma Dias-Júnior; Luiz Antonio Candido (Urban Climate, 2026)

Metallic trace element concentrations, vertical patterns and environmental implications in soils under the “cabruca” agroforestry system of Brazil's largest cocoa-producing region - Tatiana Reis dos Santos Bastos; João Carlos Medeiros; Clistenes Williams Araújo do Nascimento; Paula Nascimento Alves; Pâmalla Graziely Carvalho Morais; Glécio Machado Siqueira; Maria Eugênia Ortiz Escobar; Kaique Mesquita Cardoso; Thomas Vincent Gloaguen; Simone Aparecida da Silva Lins; Cácio Luiz Boechat (Science of The Total Environment, 2026)

PEGylated Liposomal Resveratrol Induces Region-Specific Redox Modulation Without Behavioral or Neurotrophin Recovery in a VPA Model of Autism - Victória Linden de Rezende; Maria Fernanda Pedro Ebs; Flávia da Silva Daros; Maiara de Aguiar da Costa; Sofia Januário Bolan; Germano Lapa Viana; Leonardo Pelegrini; Nathan de Souza Colonetti; Maria Júlia Ferro Spillere; Giseli da Silva Souza; Rafaela de Sousa Anastácio; Ellen De-Pieri; et al. (Journal of Molecular Neuroscience, 2026)
Autism Spectrum Disorder (ASD) is associated with neuroinflammation and oxidative stress that disrupt neurodevelopmental processes. Resveratrol (RSV) is a polyphenol with antioxidant and anti-inflammatory properties, but its poor bioavailability limits therapeutic use. This study investigated whether PEGylated liposomes encapsulating RSV (LipRSV) could modulate oxidative and behavioral alterations in a valproic acid (VPA)-induced rat model of ASD. PEGylated LipRSV were synthesized, characterized as hemocompatible, and administered to offspring from postnatal day (PND) 6 to 27. Behavioral tests included developmental milestones, olfactory discrimination, negative geotaxis, open field, and three-chamber social interaction. Oxidative stress markers and neurotrophins (BDNF, NGF) were quantified in the following brain regions: hippocampus, hypothalamus, striatum, cerebellum, frontal and posterior cortex. LipRSV exerted limited and region-dependent redox effects, reducing ROS levels only in the hippocampus, cerebellum, and posterior cortex, while failing to improve behavioral outcomes and being associated with unfavorable neurochemical alterations, including reduced BDNF and NGF levels. Importantly, LipRSV also induced behavioral deficits, redox imbalance, and neurochemical alterations in control animals, indicating treatment-related effects in the absence of VPA exposure. LipRSV modulated oxidative stress in a region-dependent manner without improving behavioral deficits in the VPA model and was associated with reduced BDNF and NGF levels. This study provides evidence that modulation of oxidative stress alone is insufficient to rescue behavioral phenotypes in the VPA model of ASD. These findings highlight the partial neurochemical efficacy and translational limitations of this formulation, suggesting the need for optimized nanocarrier design and dosing strategies in ASD pharmacotherapy.

Toxicity and Morphological Alterations Caused By Azadirachtin in the Stingless Bee Nannotrigona testaceicornis Lepeletier, 1836 (Insecta: Hymenoptera: Apidae: Meliponini - Andressa Santoro; Talita Aparecida Tódora Santana; Wingly Santos Beltrame; Nathalia Rodrigues da Silva de Carvalho; Larissa Eduarda de Oliveira Garcia; Fernanda Giovana Martins de Oliveira; Giovana Natiele Machado Esquissato; Vagner de Alencar Arnaut de Toledo; Daiani Rodrigues Moreira; Adriana Aparecida Sinópolis Gigliolli; Maria Claudia Colla Ruvolo Takasusuki (Neotropical Entomology, 2026)
Nannotrigona testaceicornis are essential pollinators for biodiversity maintenance and agricultural production. However, during foraging in agroecosystems, they may be exposed to residues of bioinsecticides used for pest management. Thus, this study evaluated the toxicity of the commercial product AzaMax® (azadirachtin) to the stingless bee N. testaceicornis . Adult worker bees were exposed to this bioinsecticide by contact and ingestion at concentrations recommended for strawberry crops, and mortality was assessed after 24, 48, and 72 h. Morphological alterations of the midgut and changes in chromatin structure in brain cells were evaluated in the surviving stingless bees. Exposure resulted in low mortality, precluding the estimation of the LC₅₀, but revealed significant sublethal effects, such as disorganization of the midgut epithelium, loss of digestive cells, reduction of regenerative cells, and disappearance of the peritrophic membrane. An increase in chromatin condensation was detected at different exposure times and concentrations, suggesting disruption of gene regulatory processes. These findings indicate that although azadirachtin does not induce immediate lethality in N. testaceicornis , it may compromise digestive physiology and genomic integrity, potentially affecting individual performance and long-term colony maintenance. The results highlight the importance of considering sublethal parameters in bioinsecticide risk assessments, as they may reveal hidden and ecologically relevant impacts that are not detected by mortality alone. By incorporating both lethal and sublethal endpoints, this research contributes to the development of safer agricultural practices and supports the conservation of stingless bees, which are key pollinators in tropical ecosystems.

Monitoring bioremediation of an impacted coastal lagoon through nature-based solutions: a case study of the Maricá Lagoon (RJ, Brazil) - Valquiria Maria de Carvalho Aguiar; Rodrigo Coutinho Abuchacra; Beatriz Freitas dos Santos Gonçalves; Joel de Mattos Junior; Joana Aiko Takiguchi Senra da Cruz; Paulo Henrique Campos; Milena Bertges de Carvalho Magalhães; Alcinei Rodrigues Machado; José Antônio Baptista Neto (Environmental Monitoring and Assessment, 2026)
This study evaluates bioremediation using effective microorganisms (EM) to improve quality in the eutrophic Maricá Lagoon (RJ, Brazil). The intervention, implemented in late 2021, consisted of the regular application of EM in one of the lagoon’s main fluvial contributors: the Mumbuca-Ubatiba drainage basin. To evaluate bioremediation, physicochemical and biogeochemical variables were monitored in the water column and sediments from 2020 to 2023. Whereas the drainage basin was sampled monthly, the lagoon was sampled every 3 months. Dissolved inorganic nitrogen (DIN) concentrations showed strong spatial variability in the system, reaching up to 2412 µM in the eastern margin (Mumbuca-Ubatiba)—dominated by ammonium (> 80% of DIN)—and up to 234 µM in the western margin (São Bento channel), where nitrate predominated (> 70%). Chlorophyll-a concentrations declined from 240 µg L⁻ 1 in 2020 to 11.44 µg L⁻ 1 in 2023 in Mumbuca-Ubatiba basin. Improvements associated with bioremediation were more evident in sedimentary variables in the lagoon. Total organic carbon decreased from 7.79% (2021) to 2.72% (2023), while total phosphorus showed an overall decreasing trend despite a peak of 2826 mg kg⁻ 1 in August 2023. The Trophic State Index (TSI) revealed a general improvement in water quality, with conditions shifting from hypereutrophic (TSI ≥ 59.1) and supereutrophic (58.2–59.0) to mesotrophic levels (53.2–55.7) in several stations. Despite improvements, persistent hypoxia (DO < 2 mg.L −1 ) and continuous high nutrient inputs indicate that bioremediation alone is insufficient to fully restore system conditions. These findings demonstrate that EM-based bioremediation should be integrated with broader environmental governance strategies for long-term effectiveness.

Kaolin-based particle film mitigates high light stress in native tree seedlings through anatomical and growth adjustments - Amanda Lúcia Pereira Machado da Silva; Rosana Maria dos Santos Nani de Miranda; Guilherme Augusto Rodrigues de Souza; Diesily de Andrade Neves; Larissa Crisostomo de Souza Barcellos; Anne Reis Santos; Paulo Ricardo dos Santos; Cláudia Franca Barros; Eliemar Campostrini (Protoplasma, 2026)
Deforestation and environmental degradation increase the need for effective strategies to improve seedling establishment in ecological restoration programs, particularly under high irradiance conditions. Although processed kaolin particle film (PKPF) has been widely used to mitigate abiotic stress in agricultural crops, its potential application to native forest species during restoration remains poorly understood. This study evaluated the effects of PKPF on anatomical, ultrastructural, and biometric traits of Cordia superba and Citharexylum myrianthum , two native Atlantic Forest species commonly used in restoration projects. Seedlings were grown under full sunlight with or without PKPF application and compared with greenhouse-grown plants. PKPF reduced leaf temperature, preserved chloroplast and mitochondrial ultrastructure, and promoted the accumulation of starch grains and plastoglobules. These responses indicate improved maintenance of cellular integrity and energy metabolism under high irradiance, contributing to enhanced stress tolerance during seedling establishment. Growth responses were more pronounced in C. superba , whereas C. myrianthum exhibited greater intrinsic tolerance to light stress. Overall, the results demonstrate that PKPF mitigates the adverse effects of excessive solar radiation by protecting cellular structures associated with photosynthetic performance and supporting seedling development. This study provides novel evidence for the use of kaolin-based technologies in native forest species and highlights their potential to improve restoration success under increasingly challenging environmental conditions.

Electrochemotherapy with carboplatin and bleomycin associated with mastectomy in cats with mammary carcinoma: A pilot study - Renata Regadas; Graziela Souza Dias; Carlos Henrique Maciel Brunner; Vitor de Moraes Pina de Carvalho; Laís Pereira Silva; Karine Araújo Damasceno; Thanielle Novaes Fontes; Marcos André Nino Rocha; Stella Maria Barrouin-Melo; Marília Carneiro de Araújo Machado; Alessandra Estrela-Lima (Topics in Companion Animal Medicine, 2026)

New insights into laticifers in Mimosa caesalpiniifolia Benth. (Fabaceae): anatomy, ultrastructure, and development, emphasizing the presence of callose - Tatiane Maria Rodrigues; Stefany Cristina de Melo Silva; Yasmin Massimino Sampaio de Souza; Lúcio Queiroz de Carvalho; Yve Canaveze; Silvia Rodrigues Machado (Protoplasma, 2026)

Gold nanoparticles prevent the establishment of severe malaria in a murine animal model - Sarah Aparecida dos Santos Alves; Douglas Esteves Teixeira; Lavínia Reif Correa Oliveira; Maria Eduarda Lopes Souza; Monique Martins Melo; Mayck Medeiros; Sabrina Sodré-Serra; Paticia Machado Rodrigues Silva; Marco Aurélio Martins; Pedro Leme Silva; Patricia Rieken Macedo Rocco; Celso Caruso-Neves; et al. (Journal of Pharmaceutical Investigation, 2026)

Beyond technical metrics: Key indicators as boundary objects for assessing environmental injustice in green space access and urban heat exposure — A scoping review - Anna Maria Galvão Carneiro Lyra; Mirela Beatriz Silva; Julia Simoes Neves da Silva; Ana Clara de Souza; Vivian Martins Machado; Ricardo Almendra; Adriano Bressane (Urban Forestry & Urban Greening, 2026)

Hybridization of mantle- and crust-derived magmas during the late-collisional stage of the Sergipano Orogenic System, NE Brazil - Luis Felipe dos Santos Rodrigues; Fábio dos Santos Pereira; Cleverton Correia Silva; Jean-Michel Lafon; Rômulo Machado; Herbet Conceição; Maria de Lourdes da Silva Rosa (Journal of South American Earth Sciences, 2026)

Hydrocolloid-structured tucupi: physicochemical, rheological, and sensory characterization for culinary applications - Cássia Santos do Amaral; Lorena Maria Freire Sampaio; Luis Felipe Santos Araújo; Adriana Camurça Pontes Siqueira; Maria de Fátima Lopes Fernandes; Jeanny da Silva Maciel; Paulo Henrique Machado de Sousa; Fátima Miranda Nunes (International Journal of Gastronomy and Food Science, 2026)

The anatomy of fruit development and its evolution in the Myrteae tribe (Myrtaceae) - Nayara Carreira Machado; Maria Luiza Dias Piassa; Karinne Sampaio Valdemarin; Daiane Aparecida Camargo Portella; Leonardo Cazuza Bondezan; Beatriz Fernanda da Silva Pittarelli; Marcela Thadeo; Eve Lucas; Káthia Socorro Mathias Mourão (Flora, 2026)

Urban heatscapes and environmental injustice: Structural drivers and governance pathways for equitable climate adaptation – A scoping review - Anna Maria Galvão Carneiro Lyra; Adriano Bressane; Mirela Beatriz Silva; Vivian Martins Machado; Julia Simões Neves da Silva; Ana Clara de Souza; Ricardo Almendra (Environmental Science & Policy, 2026)

Dietary biological silage from tambaqui by products affect performance, physiology, and egg quality of young and old laying hens - Cristiane Cunha Guimarães; João Paulo Ferreira Rufino; Alexandre Augusto Barai; Adriene Núzia de Almeida Santos; Maria Fernanda da Silva Gomes; Tiago Cabral Nóbrega; Maiko Willas Soares Ribeiro; Philip Dalbert da Silva Castro; Joana Maia Mendes; Francisco Alberto de Lima Chaves; Joel Lima da Silva Junior; Marco Antonio de Freitas Mendonça; et al. (Tropical Animal Health and Production, 2026)
This study evaluated the effects of increasing inclusion levels of biological silage produced from tambaqui ( Colossoma macropomum ) by-products (BST) in diets of commercial hens at different ages. A completely randomized design in a 2 × 5 factorial arrangement was adopted, comprising two hen ages (23 and 83 weeks) and five BST inclusion levels (0, 1, 2, 3, and 4%), with four replicates of six birds per treatment. Moderate BST inclusion (1–2%) improved egg production, egg mass, and feed efficiency, particularly in younger hens, while maintaining physiological homeostasis. In contrast, higher inclusion levels (≥ 3%) reduced feed intake and performance and negatively affected erythropoietic indicators, with more pronounced effects in older hens, highlighting age-dependent metabolic responses. Egg physical quality, including albumen height, Haugh unit, and eggshell thickness, was optimized at 2% BST, whereas excessive inclusion compromised shell quality and egg weight. Egg composition was modestly affected, mainly in lipid and moisture contents, with interactions between diet and hen age. Sensory evaluation revealed that eggs from hens fed up to 1% BST maintained high acceptability, while higher inclusion levels negatively affected taste. The observed benefits at moderate inclusion levels are likely associated with the presence of highly digestible proteins, bioactive peptides, and fermentation-derived compounds that enhance nutrient utilization and productive efficiency. Conclusively, BST represents a viable and sustainable ingredient for laying hen diets when included at moderate levels (≤ 2%), providing a novel strategy for valorizing aquaculture by-products while optimizing productive performance, physiological responses, and egg quality, considering age-related adaptability.

Aqueous extract of Psidium glaziovianum Kiaersk leaves acts on muscarinic and opioid receptors and reduces cytokines and inflammatory infiltrates in vivo models - Wêndeo Kennedy Costa; Paulo Henrique Eloi Fernandes; Paloma Maria da Silva; Samuel José Oliveira de Freitas; Eduardo Alves Camêlo; Gildomar Guilherme Interaminense Nunes; Janaina Carla Barbosa Machado; Magda Rhayanny Assunção Ferreira; Luiz Alberto Lira Soares; Alisson Macário de Oliveirad; Márcia Vanusa da Silva; Maria Tereza dos Santos Correia (Inflammopharmacology, 2026)

Nanoencapsulation of red alga Pyropia spiralis extract by freeze-drying using maltodextrin DE20: Evaluation of antioxidant, antiglycation and anti-aging properties - Laura Maria Bigeschi Nucci; Filipe Oliveira Granero; Célia Cristina Malaguti Figueiredo; Luciana Pereira Silva; Patrícia Soares Santiago; Levi Pompermayer Machado; Regildo Márcio Gonçalves da Silva (Algal Research, 2026)

Partitioning Soil Respiration: Differentiating Root Contributions and Environmental Factors - Wanderson Benerval de Lucena; Daniel Carlos Machado; Polyana Pereira; Maria Elisa Vicentini; José A. Neira Román; Glauco de Sousa Rolim; Alan Rodrigo Panosso; Newton La Scala (Agricultural Research, 2026)

Antibiofilm biosynthetic terpene derivatives against clinically and food-relevant bacteria, including synergistic interactions with β -lactam antibiotics: quantum chemical calculations, molecular docking and ADMET study - Rafaela Mesquita Bastos Cavalcante; Ana Maria Aguiar Nascimento; Rhanna Karyne Rodrigues Muniz; Jéssica Híade Silva Cristino; Victor Moreira de Oliveira; Emmanuel Silva Marinho; Marcia Machado Marinho; Francisco Nithael Melo Lucio; Jesyka Macedo Guedes; Glaydson Leandro Farias Mendonça; Thiago dos Santos Francisco; Francisco Ferdinando Mesquita Cajazeiras; et al. (Biofouling, 2026)

Soil attributes are key drivers of calcium, potassium, and magnesium concentrations and stocks in a tropical dry forest - Alice Batista dos Santos; Ana Cristiana Silva; Marcelo Tabarelli; Maria Fabiola Barros; Elvis Joacir De Franca; Silvia Rafaela Machado Lins; Renato Soares Vanderlei (Journal of Arid Environments, 2026)

Polycyclic aromatic oxygen heterocyclic as molecular markers to fossil fuels: Analytical methods and applications - Flávia Lima e Cima Miranda; Diego Nery do Amaral; Maria Elisabete Machado (International Journal of Coal Geology, 2026)

Retraction notice to ‘Aluminum: A potentially toxic metal with dose-dependent effects on cardiac bioaccumulation, mineral distribution, DNA oxidation and microstructural remodeling’ [Environ. Pollut. 242, Part A (2018) 814-826] - Rômulo D. Novaes; Viviane G.S. Mouro; Reggiani V. Gonçalves; Andrea A.S. Mendonça; Eliziária C. Santos; Maria C.Q. Fialho; Mariana Machado-Neves (Environmental Pollution, 2026)

Increases in cell-wall homogalacturonan but decreases in xylogalacturonan accompany transition from dormant to vegetative stages in Chrysolaena obovata rhizophores - Marina Câmara Mattos Martins; Fernanda dos Santos Kretzschmar; Nicholas C. Carpita; Adriana Hissae Hayashi; Maria Angela Machado de Carvalho; Breno Leite; Marcia Regina Braga (Carbohydrate Polymers, 2026)

Scaling biogas production with a new sorghum cultivar: biomass yield as a key driver - Ana Claudia Lazaroto; Marina Celant De Prá; João Fernando Ferri da Silva; Deisi Cristina Tápparo; Dagmara Beltrame de Assis; Ricardo Luís Radis Steinmetz; Fabiane Goldschmidt Antes; Rafael Augusto da Costa Parrella; Maria Lúcia Ferreira Simeone; Flaviane Eva Magrini; Igor Vinicius Machado Sophiatti; Suelen Paesi; et al. (Biomass and Bioenergy, 2026)

Beef quality, liver gluconeogenesis, and muscle lipid metabolism of Nellore steers fed a magnesium oxide blend combined or not with monensin - Javier Alexander Bethancourt-Garcia; Mateus Pies Gionbelli; José Maria Oliveira; Karolina Batista Nascimento; Germán Dario Ramírez-Zamudio; Luana Ruiz dos Santos; Priscilla Dutra Teixeira; Tathyane Ramalho Santos Gionbelli; Marcio Machado Ladeira (Animal Feed Science and Technology, 2026)

Valorization of barley bagasse for lactic acid production using an enzymatic cocktail produced by Aspergillus brasiliensis - Thiago Machado Pasin; Rosymar Coutinho de Lucas; Maria de Lourdes Teixeira de Moraes Polizeli (Archives of Microbiology, 2026)

Strategies for recombinant laccase expression and their roles in environmental remediation - Isabeli Bannach-Machado; Rafael Trindade Maia; Rosane Marina Peralta; Cristina Giatti Marques de Souza; Charles Windson Isidoro Haminiuk; Giselle Maria Maciel (World Journal of Microbiology and Biotechnology, 2026)
Laccases are multicopper enzymes capable of oxidizing a wide variety of compounds, standing out as green tools for industrial and environmental applications. However, production from native sources faces limitations that have driven advances in recombinant expression. This scoping review includes studies published between 2019 and 2025, selected from major online databases, describing recombinant fungal and bacterial laccases for environmental applications. Strategies to optimize expression are discussed, including the use of efficient vectors, codon optimization, His-tag addition, mutagenesis, and computational approaches, with an emphasis on their advantages, trade-offs, and limitations. Pichia pastoris is widely used for the expression of fungal laccases, while Escherichia coli is preferred for the expression of bacterial laccases. However, significant variability in expression efficiency and enzyme performance is observed across hosts and constructs. The use of alternative culture media, such as agro-industrial residues, is also explored as a sustainability-driven strategy; however, its applicability remains limited for certain heterologous expression systems. In the environmental field, recombinant laccases demonstrate high efficiency in the degradation of textile dyes, the treatment of lignocellulosic waste, the biodegradation of pharmaceuticals, and the degradation of various toxic compounds, often requiring redox mediators to achieve high conversion rates. Despite significant advances, challenges remain, such as inconsistent catalytic performance among studies and limited stability under extreme temperature and pH conditions. Overall, this review highlights the key challenges in developing recombinant laccase and demonstrates that advances in protein engineering, expression systems, and process optimization are crucial for environmental applications.

Eucalyptus wood waste biochar as an eco-friendly adsorbent for arsenic detoxification in wastewater - Yu Shuang Ren; Muhammad Ilyas; Islamud Din; Syeda Maria Ali; Shahid Iqbal; Thiago Machado da Silva Acioly; Zhanate Idrisheva; Khalid Z. Elwakeel; Alibek Ydyrys; Abdullah Faiz Al Asmari; Saiful Islam (Natural Product Research, 2026)

An eco-friendly approach for determination of polycyclic aromatic compounds in water hyacinth (Eichhornia crassipes) - Lucas Bonfim Gonçalves; Pedro Victor Bomfim Bahia; Jailson Bittencourt de Andrade; Maria Elisabete Machado; Sérgio Luís Costa Ferreira (Marine Pollution Bulletin, 2026)

Urban heat riskscape and green injustice: A scoping review of health and environmental impacts - Mirela Beatriz Silva; Adriano Bressane; Ricardo Almendra; Anna Maria Galvão Carneiro Lyra; Vivian Martins Machado (Urban Forestry & Urban Greening, 2026)

Arboreal Camera Trap-based Insights into the Activity, Resource Use, and Demography of Black Lion Tamarins (Leontopithecus chrysopygus) and Sympatric Mammals in Atlantic Forest Fragments - Daniel Angelo Felippi; Maria Carolina Rodella Manzano; Paolla Nicole Franco; Vinícius José Alves Pereira; João Vitor Medeiros Teixeira; João Pedro Fernandes Machado; Gabriela Cabral Rezende (International Journal of Primatology, 2026)
Wildlife monitoring is essential for guiding biodiversity conservation strategies, particularly in fragmented ecosystems under intense anthropogenic pressure. While noninvasive methods, such as camera traps, are widely used for terrestrial species, their application in other forest strata is underexplored despite its potential for studying elusive and nocturnal arboreal mammals. We aim to evaluate whether arboreal camera trapping is a relevant tool for monitoring the endangered black lion tamarin ( Leontopithecus chrysopygus ) and other sympatric arboreal and scansorial mammals in two Atlantic Forest remnants in Pontal do Paranapanema, São Paulo, Brazil. With 27 cameras in the lower and mid-canopy (0.5–8.0 m) and 9,872 camera-days, we recorded 1,316 independent video events representing seven species of mammal. Arboreal camera traps provided robust estimates of diel activity patterns, resource partitioning, and demographic dynamics, including the development of one tamarin infant and one juvenile over time. They also revealed interspecific sharing of sleeping sites and nest boxes, emphasizing the role of these structures in supporting both diurnal and nocturnal species. By documenting community-wide temporal niche partitioning, our study demonstrates how arboreal and scansorial mammals segregate activity in time when sharing the same arboreal structures. Overall, our results show that arboreal camera traps are relevant, noninvasive tool that simultaneously capture species-specific behavior, community-level interactions, and demographic information, highlighting their value for primatology, biodiversity monitoring, and integrative conservation planning in human-modified tropical forests.

Influence of Conspecific Male Odour and Host Kairomones on the Behaviour of Sternochetus mangiferae, a Pest of Mangoes in Brazil and Ghana - Miguel Borges; Mirian F. F. Michereff; Raúl A. Laumann; József Vuts; Marla J. Hassemer; João Victor C Machado; Michely F. S. Aquino; Kamila K S Leite; Alessandra de Carvalho Silva; Marcelo P Ricalde; Haruna Braimah; Michael A. Birkett; et al. (Journal of Chemical Ecology, 2026)
Sternochetus mangiferae is a pest of mangoes, occurring worldwide in regions where mangoes are cultivated. In Brazil, this insect was first detected in 2014 in Seropédica, Rio de Janeiro, and since then, various measures and studies have been conducted to contain, monitor and potentially eradicate it. Semiochemicals may provide feasible targets to develop sensitive detection and monitoring tools. Therefore, this study aimed to evaluate whether S. mangiferae use pheromones from conspecifics and kairomones from mango tree host in their chemical communication. The findings identify a blend of mango volatiles that influence the behaviour of S. mangiferae females. A synthetic blend containing the EAD-active compounds γ-butyrolactone, benzaldehyde, 6-methyl-5-hepten-2-one, myrcene, ( Z )-ocimene, 2-methoxyphenol, ( S )-linalool, methyl salicylate and methyl benzoate was attractive to females of S. mangiferae from Ghanaian and Brazilian populations in two-choice olfactometry experiments. The results also indicate that the absolute configuration of linalool in the mango synthetic blend is crucial for female attraction, as females respond only to blends containing ( S )-linalool. Furthermore, females from both populations were attracted to the odour of live males from their respective localities. Chemical analysis of aeration samples from the Brazilian population revealed that males and females emitted qualitatively similar volatile profiles. Although no male-specific compounds could be identified to fully explain female attraction, this study provides the first evidence of intraspecific chemical communication in S. mangiferae . These findings advance our understanding of the chemical ecology of this pest and support the development of semiochemical-based monitoring and management strategies for mango orchards.

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

Hyperdominant Trees Reveal Savanna Vulnerability Under Climate Change - Facundo Alvarez; Ben Hur Marimon‐Junior; Beatriz Schwantes Marimon; Wesley Jonatar Alves da Cruz; Norberto Gomes Ribeiro Júnior; Raiane Gonçalves Béu; Polyanna da Conceição Bispo; Aldair de Souza Medeiros; Glécio Machado Siqueira; Marcelo Leandro Bueno; Fabiana de Gois Aquino; Frederico Augusto Guimarães Guilherme; et al. (Global Change Biology, 2026)
The Cerrado biome, spanning ~2 million km 2 , is one of the most extensive and biodiverse tropical savannas, yet it is paradoxically dominated by only 30 hyperdominant tree species (~2% of all species, > 50% of all stems). However, their vulnerability to climate change and the effectiveness of current conservation efforts remain uncertain. By combining (i) species distribution models calibrated with edaphic‐climatic predictors and occurrence data for hyperdominant Cerrado trees with (ii) functional‐trait analyses related to ecological strategies (leaf economics, bark investment, ecophysiology, drought tolerance, regeneration, and dispersal), we identified the biomass production and reproductive traits that best predict species persistence under high‐emission scenarios (RCP8.5). Currently, only 427,980 km 2 (~17.4%) of the modeled potential environmental suitability falls within protected areas; under future climate scenarios, this protected suitable area is projected to decline by ~45.9% to 231,377 km 2 (~18.1%). This loss, resulting from land conversion with the expansion of agricultural frontiers and fire events, highlights a mismatch in current regional conservation priorities, overlooking the needs of the Cerrado and its associated biodiversity. Given ongoing land‐use change and that 58% of remaining native vegetation occurs on private lands, this mismatch highlights the urgent need to align conservation and agricultural policy. Functional trait analyses revealed a clear gradient from acquisitive “fast” to conservative “slow” strategies, reflecting trade‐offs in water‐use efficiency and biomass allocation, with leaf structural and reproductive traits best predicting species resilience to climate change. Our results indicate that a small subset of hyperdominant species not only forms current community structure but also signals the biome's resilience/vulnerability to climate change. Conservation planning should prioritize identified climate refuges and be based on functional traits to buffer the loss of functional and structural integrity in one of the world's richest and most threatened savanna ecosystems.

Amorphous solid dispersions as a strategy to enhance the bioavailability and stability of formulations containing plant active ingredients: An integrative review - Maria Eduarda de Oliveira Cardoso Melo; Camila Castro da Silva; Thainá dos Santos Dantas; Janaina Carla Barbosa Machado; Mágda Rhayanny Assunção Ferreira; Luiz Alberto Lira Soares (DARU Journal of Pharmaceutical Sciences, 2026)
Objectives Plant-derived active pharmaceutical ingredients (APIs), including crude extracts, phytocomplexes, and isolated compounds, have been extensively investigated due to their therapeutic potential. However, their pharmaceutical application is often hindered by challenges such as low solubility, limited stability, and poor bioavailability. Amorphous solid dispersions (ASDs) have emerged as a promising strategy to overcome these limitations, enhancing solubility, dissolution, and oral absorption of these compounds, while also protecting active constituents and improving their stability. Accordingly, this review aims to explore the use of ASDs for plant-derived APIs, focusing on production methods, polymers and carriers employed, as well as characterization techniques applied to these formulations. Methods A literature search was conducted in ScienceDirect, Scopus, Web of Science and PubMed databases for articles published between 2000 and 2025. Using terms related to ASDs and plant-derived compounds, 566 articles were retrieved, of which 84 met the inclusion criteria after screening. Results and discussion The review highlights successful incorporation of several plant-derived APIs into ASDs, primarily to improve solubility and membrane permeability, with isolated compounds being the most frequently studied. The solvent evaporation method was the most used, although efforts toward more sustainable production methods were also reported. Among polymeric carriers, poly(vinylpyrrolidone) (PVP), poly(vinyl alcohol) (PVA), and poly(ethylene glycol) (PEG) were the most frequently employed. The most common physicochemical characterization techniques included scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and X-ray diffraction (XRD). Conclusion Overall, ASDs represent a viable and effective approach to unlock the therapeutic potential of plant-derived APIs, supporting the development of more stable and bioactive herbal formulations.

TcGAPDH peptidic inhibitors derived from dinoponeratoxin M-PONTX-Dq4e with trypanocidal effect - Emanuel Paula Magalhães; Dânya Bandeira Lima; Evelline Araújo Edson; Brenna Pinheiro Silva; Márcia Machado Marinho; Emmanuel Silva Marinho; Vani Xavier Oliveira; Ramon Róseo Paula Pessoa Bezerra de Menezes; Alice Maria Costa Martins (Toxicon, 2026)

Crop sequence effects on the genesis of soil aggregates in no-tillage systems: A focus on biogenic structures - Itaynara Batista; Deivid Lopes Machado; Maria Elizabeth Fernandes Correia; Maria Helena Moraes Spinelli; José Eduardo Corá (Soil and Tillage Research, 2026)

Physical quality of a Ferralsol under different management systems - Ésio De Castro Paes; Saulo Henrique Barroso; Fabiane Pereira Machado Dias; Iara Oliveira Fernandes; Elisângela Gonçalves Pereira; José Maria De Lima; Rafaela Simão Abrahão Nóbrega; Júlio César Azevedo Nóbrega (Soil and Tillage Research, 2026)

Physicochemical and cytological stability of cerebrospinal fluid in small ruminants and agreement between methods for lactate measurement - Juliana Massitel Curti; Caroline Ambiel Barros Gil Duarte; Caroline Gonzatto Fracasso; Stefany Lia Oliveira Camilo; Maria Antonia de Campos Tornich; Lais Sodré Santana Alves; Gabriela Fernanda Vitoretti Machado; Priscilla Fajardo Valente Pereira; Karina Keller Marques da Costa Flaiban (Small Ruminant Research, 2026)

Influence of sorghum grain tannin content on the composition and properties of pyrolysis products - Pablo Batista Mendes; Jéssika Thayanne da Silva; Júlia Martins Carolino; Rafael de Araújo Miguel; Maria Lucia Ferreira Simeone; Valéria Aparecida Vieira Queiroz; Cícero Beserra de Menezes; Alan Rodrigues Teixeira Machado; Lúcia Pinheiro Santos Pimenta (Biomass and Bioenergy, 2026)

Rotavirus Outbreak Traced in Clinical, Environmental, and Food Matrices: Whole Genomic Characterization of an Equine-like G3P[8] Genotype - Fernanda Marcicano Burlandy; Bruna Campestrini Casarin; Meylin Bautista Gutierrez; Carina Pacheco Cantelli; Shênia Patricia Corrêa Novo; Rosane Maria Santos de Assis; Bruna Candia Piccoli; Amanda Haisi; Anelise da Costa Daneli; Roberta Danieli Marchesan; Julia Kuhns; João Pessoa Araújo Junior; et al. (Food and Environmental Virology, 2026)
The emergence of new viral strains has been frequently associated with the onset of outbreaks in different epidemiological settings. This study investigated an acute gastroenteritis (AGE) outbreak, which occurred at a university campus in southern Brazil, in 2024, affecting approximately 30–40% of undergraduate students, with over 400 reported cases. The objectives were to describe the epidemiological and molecular features of the outbreak, identify the probable transmission route, and assess the genetic relatedness of the detected strain to recently circulating rotavirus A (RVA) lineages. Clinical, environmental, and food samples were analysed for RVA and norovirus genogroup (G) I and GII. RT-qPCR detected RVA in the three specimen types with concentrations reaching 2.4 × 10 8 genome copies (GC)/g in faeces, 3.5 × 10 2 GC/g in food and 5.5 log₁₀ GC/l in water. Genotyping revealed an equine-like G3P[8] strain in clinical samples with whole genome sequencing establishing a DS-1-like backbone; G3-P[8]-I2-R2-C2-M2-A2-N2-T2-E2-H2. Sequencing data of the VP6 gene of RVA detected in one of the environmental samples confirmed the same genotype (I2), consistent with the genotype found in the clinical stool samples. The detection of RVA in multiple environmental and food specimens suggests that the possible source of contamination was associated with water supply systems. Phylogenetic analyses showed that the outbreak strain clustered with equine-like G3P[8] lineages. These findings highlight the importance of integrating molecular surveillance and environmental monitoring to trace viral transmission pathways and detect the emergence of RVA strains in community outbreaks.

Seasonality and habitat affect tick parasitism in typical antbirds (Thamnophilidae) of the Atlantic Forest - Mariah O. M. Vecchi; Gilberto S. Gazeta; Ingrid B. Machado; Maria Alice S. Alves (Journal of Ornithology, 2026)
Records of tick parasitism in Brazilian birds result from specific community studies, in which similar parasitic rates are found among species phylogenetically close and with similar habitat use. However, to understand the tick–bird dynamics, it is necessary to consider the ecological aspects of the organisms and the environment. Over a year, during both dry and rainy periods, we captured three Thamnophilidae species with mist nets and examined the birds for ticks. Concurrently, we conducted field observations along linear transects to characterise the vertical distribution of vegetation of these species. We identified the collected ticks taxonomically and molecularly. We hypothesise that the lowest tick prevalence rates will be found in the forest that the highest rates will occur in the dry season, and that will be higher in birds occupying lower heights above the ground. Contrary to expectations, the restinga had a lower parasite prevalence. In the forest, there was a higher prevalence in the dry months. Unlike the pattern observed in other areas of the Atlantic Forest, the birds in the restinga were parasitised exclusively during rainy months. The use of vertical space of vegetation differed among the birds but did not determine the parasitism rates. Our results indicate that ecological factors regulate exposure to tick parasitism, even among phylogenetically close birds, as species in the Thamnophilidae family did not show the same pattern. The host–parasite interaction varied across areas and seasons, suggesting that these factors may determine the availability of ticks for parasitism.

Correction: Partitioning Soil Respiration: Differentiating Root Contributions and Environmental Factors - Wanderson Benerval de Lucena; Daniel Carlos Machado; Polyana Pereira; Maria Elisa Vicentini; José A. Neira Román; Glauco de Sousa Rolim; Alan Rodrigo Panosso; Newton La Scala (Agricultural Research, 2026)

Development of Organoclay as an Artificial Micro Substrate for Chemoautotrophic Biofloc Aquaculture Systems (BFT) - Talita Ribeiro Gagliardi; Maria Helena de Araujo Mendes; Claudia Machado; Loic Hilliou; Wilson Wasielesky; Felipe Boéchat Vieira (Fishes, 2026)
This study investigated the characterization and application of organoclay formulations in a chemoautotrophic biofloc system. Organoclays were produced using the calcination method and bentonite, chitosan, corn, and tapioca starches as ingredients. Thermogravimetric analysis confirmed the high thermal stability of bentonite, whereas biopolymers (tapioca, chitosan, and corn starch) exhibited greater thermal sensitivity and a lower residual mass. Scanning electron microscopy revealed that organoclays had increased porosity (4–21 µm) compared to bentonite, while energy-dispersive spectroscopy confirmed the retention of key chemical elements. X-ray diffraction and Fourier-transform infrared spectroscopy indicated structural modifications due to thermal processing. In aqueous conditions, bentonite and organoclays disaggregated into particles with sizes between 0.76 and 1.24 μm. Based on these physicochemical properties, three formulations were selected for nitrification trials due to their stability in water, O1 (bentonite + tapioca), O2 (bentonite + tapioca + chitosan), and O6 (bentonite + corn starch), along with a 100% bentonite treatment and a control group (C) supplemented with inorganic salts and artificial Needlona® substrates. All treatments achieved full nitrification within 37 days, with O1 exhibiting the best performance by maintaining ammonia and nitrite levels within safe thresholds. These findings suggest that organoclays, particularly O1, can enhance nitrification stability, providing a promising strategy for water quality management in intensive aquaculture systems.

Video-assisted ovarian sterilization by occluding the vascular supply with a modified Miller's knot and performing bilateral partial excision of the ovaries in the red-eared slider turtle (Trachemys scripta elegans) - Luis Baselly-Cueva; Diego A. Ospina-Argüelles; Luan Sitó-Silva; Beatriz Lippe de Camillo; Kárita da Mata Fuchs; Alessandra Dhom Pimentel de Moraes; Vania Maria de Vasconselos Machado; Paulo Fernandes Marcusso; Carlos González-Zambrano; Luís F. Barbisan; David Javier Galindo; Luis Mauricio Montoya Florez; et al. (The Veterinary Journal, 2026)

Occurrence and diversity of human enteric viruses in bivalve mollusks from the Amazon mangrove ecosystem in Brazil - Isabella Rodrigues Negreiros; Maria Luisa Rabelo Evas; Guilherme Caetano Lanzieri Tavares; Natália Lourenço dos Santos; Adriana Gonçalves Maranhão; ·. Bruna Barbosa de Paula; Flávia Freitas de Oliveira Bonfim; Livia Melo Villar; Tulio Machado Fumian; Nancyleni Pinto Chaves Bezerra; Alcina Vieira de Carvalho-Neta; José Paulo Gagliardi Leite; et al. (Science of The Total Environment, 2026)

Coprolites from the Romualdo Formation (Lower Cretaceous, Araripe Basin, Brazil): brief comments on morphology and trophic interactions - Maria Aline Pereira Dino; Rafael César Lima Pedroso de Andrade; Naiara Cipriano Oliveira; Fábio Hideki Yamada; Antônio Álamo Feitosa Saraiva; Renan Alfredo Machado Bantim (Journal of South American Earth Sciences, 2026)

Black women facing food insecurity are more vulnerable to the double burden of malnutrition in Brazil: evidence from Brazilian National Dietary Survey - Sávio Marcelino Gomes; Aline Martins de Carvalho; Alisson Diego Machado; Eduardo De Carli; Mariana Alves Ferreira; Michelle Cristine Medeiros Jacob; Dirce Maria Lobo Marchioni (Food Security, 2026)

First report of Penicillium digitatum causing postharvest rot in lemon in Brazil - Glícia Silva de Moraes; Amanda Cupertino de Queiroz Brito; Ana Elisa de Almeida Souza; Jordana Alves da Silva Melo; José Vitorino da Silva Neto; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Pathology, 2026)

Unraveling the role of fungi in shrimp health and disease: a focus on host-microbe interactions - Rafael Diego Rosa; Gabriel Machado Matos; María Soledad Morales-Covarrubias; André Felipe da Silva; Diogo Robl; Luciane Maria Perazzolo (Aquaculture, 2026)

Unveiling the hidden consequences of mining tailings on ecosystem processes: Disruption of decomposition of native species in the Rio Doce watershed - João Carlos Figueiredo; Yule Roberta Ferreira Nunes; Walisson Kenedy-Siqueira; Renata Maia; Yumi Oki; Milton Barbosa; Débora Lima-Santos; Flávio Mariano Machado Mota; Daniel Negreiros; Letícia Ramos; Marcos Paulo dos Santos; Rebeca Ferreira Reis; et al. (Forest Ecology and Management, 2026)

Membrane Trafficking in Psychiatric Disorders: Bridging Cellular Dysfunction and Mental Health—A Narrative Review - Maiara de Aguiar da Costa; Lucas Cândido Pedro; Maria Fernanda Pedro Ebs; Henrique Medeiros Menegaz; Sofia Januário Bolan; Amanda Duarte Machado; Júlio César Claudino dos Santos; Gislaine Zilli Réus; Cinara Ludvig Gonçalves (Molecular Neurobiology, 2026)

Microglial Inflammatory Response in the Glioblastoma Microenvironment in Preclinical Models - Ana Helena Larangeira Nóbrega; Ana Paula Soares do Prado; Rafael Sampaio Pimentel; Áquila Rodrigues Costa Santos; Rafaela Rodrigues Valerio; Luiza Clemente dos Santos de Souza; Maria Alice de Souza; Patrícia Machado Rodrigues e Silva; Marco Aurélio Martins; Rudimar Luiz Frozza; Andressa Bernardi (Molecular Neurobiology, 2026)

HAT p300/CBP Activity in the Prelimbic Cortex Underlies Reconsolidation of Contextual Fear Memory - Mariana Furtado Bergmann; Jeferson Machado Batista Sohn; Ana Maria Raymundi; Manoela de Aguiar Ferreira; Cristina Aparecida Jark Stern (Molecular Neurobiology, 2026)

Unveiling the adequacy of existing legislation in protecting urban river ecosystems in the context of One Health - Marcos Dias; Ana Raquel Calapez; Alexandra Aragão; Carina Dantas; Natália Machado; Harm op den Akker; Maria João Feio (Environmental Management, 2026)

Gendered dimensions of mental health in High-Risk occupations: A systematic review of the mining and extractive sectors - Ana Carolina Russo; Rita Aparecida Longo Russo; Maria Renata Machado Stellin; Sérgio Médici de Eston (The Extractive Industries and Society, 2025)

Abortion associated with Brucella abortus strain RB51 vaccination during gestation in a dairy cow immunized with strain 19 as a calf - Enzo Cabaña; Paula Rejf; Maria Virginia Zbrun; Maria del Rocio Marini; Andres Ilardo; Selva Machado; Oscar Garnero; Camila Nayla Foster; Maria Belen Novoa (Research in Veterinary Science, 2025)

New insights into gravitational tectonics of the Amazon deep-sea fan: A comparative study of overpressure mechanisms in the Northwest and Southeast compartments - Juliana Maria Gonçalves Souza; Alberto Machado Cruz; Nadaya Cubas; Claudio Rabe; Renaud Divies; Jean Letouzey; Daniel Brian Praeg; Didier Granjeon; Cleverson Guizan Silva; Antonio Tadeu dos Reis; Christian Gorini (Marine and Petroleum Geology, 2025)

Tailor-made zeolite-based magnetic nanocomposites (MNCs): rational design for effective and recyclable adsorption of sulfanilamide and methylene blue - Domenico Pirozzi; Paolo Allia; Gabriele Barrera; Paola Maria Tiberto; Elena Sonia Olivetti; Alessandro Latte; Antonello Marocco; Michele Pansini; Serena Esposito; Fernando Machado Machado; Ana Carolina Ferreira Piazzi Fuhr; Filomena Sannino (Journal of Environmental Management, 2025)

Restoration effectiveness in pure and mixed plantings in the southern Atlantic forest Biome, Brazil - Júlia Luiza Stahl; Maristela Machado Araujo; Adriana Maria Griebeler; Felipe Turchetto; Camila Fonseca Galvan; Suelen Carpenedo Aimi; Claudia Costella; Felipe Manzoni Barbosa; Álvaro Luís Pasquetti Berghetti; Ervandil Corrêa Costa (Journal for Nature Conservation, 2025)

Silica decorated with palladium nanoparticles applied in a miniaturized method to separation and quantification of sulfur-containing compounds in fuel samples - Lua Morena Leoncio de Oliveira; Flávia Lima e Cima Miranda; Fabio Xavier Antunes Sampaio; Diego Nery do Amaral; Karina Santos Garcia; Antonio Fernando de Souza Queiroz; Edilson Valmir Benvenutti; Maria Elisabete Machado (Fuel, 2025)

FlorestaSC: A double-up approach to improve biodiversity monitoring in hyperdiverse forests - André Luís de Gasper; Guilherme Salgado Grittz; Giesta Maria Olmedo Machado; Anderson Kassner-Filho; Luís Adriano Funez; Marcos Sobral; Débora Vanessa Lingner; Alexander Christian Vibrans (Forest Ecology and Management, 2025)

Feasibility and safety of intrathecal transplantation of allogeneic bone marrow mesenchymal stem cells in horses - Lucas Vinícius de Oliveira Ferreira; Leandro Maia; Danielle Jaqueta Barberini; Regina Kiomi Takahira; Vânia Maria de Vasconcelos Machado; Gisele Fabrino Machado; Guilherme Dias de Melo; Rogério Martins Amorim (Veterinary Research Communications, 2025)

Canopy-Level Photosynthetic Homogeneity Accounts for Greater Biomass in Energy Cane Compared to Sugarcane - Larissa P. Cruz; Maria D. Pissolato; Rafael L. Almeida; Eduardo C. Machado; Rafael V. Ribeiro (Tropical Plant Biology, 2025)

A Mixture of Four Probiotic Strains (Probiatop®) Mitigates Food Allergy to Ovalbumin in Mice - Vivian C. Miranda; Ramon O. Souza; Bruno Gallotti; Marcos F. A. de Oliveira; Ana Maria C. Faria; Jacques R. Nicoli; Enio Ferreira; Denise C. C. Machado; Flaviano S. Martins (Probiotics and Antimicrobial Proteins, 2025)

Load-cooling strategy and associated heat stress in piglets transported by road in semiarid climates - João José de Mesquita Sales; José Antonio Delfino Barbosa Filho; Nítalo André Farias Machado; Maria Simone Mendes Peixoto; Luiza Diniz Macêdo; Carla Caroline de Sousa Vasconcelos (International Journal of Biometeorology, 2025)

Angiotensin-(1-7) treatment improves pneumonia and prevents sepsis caused by pneumococcal infection - Eliza Mathias Melo; Izabela Galvão; Franciel Batista Felix; Fernanda Medeiros Vale Magalhães; Flavia Rago; Marina Gomes Machado; Fernando Roque Ascenção; Maria José Campagnole-Santos; Robson Augusto Souza dos Santos; Geovanni Dantas Cassali; Mauro Martins Teixeira (Inflammation Research, 2025)

Inequalities in the community food environment around Brazilian households with children under 5 years from a national survey in Brazil - Inês Rugani Ribeiro de Castro; Raquel Machado Schincaglia; Maria Alvim Leite; Elisa Maria de Aquino Lacerda; Paula Normando; Neilane Bertoni; Gilberto Kac (Food Security, 2025)

Applying a Functional Trait-based Approach for Ecological Succession Monitoring and Species Management in Areas under Active Restoration in a Tropical Forest - Adriana P. Manhães; Mariana Saavedra; Marcelo P. Pansonato; Moab T. Andrade; Beatriz Camelo; Frederico Santos Machado; Jorge Eduardo Paes; Jerônimo B. B. Sansevero; Adriana Maria Zanforlin Martini; Dulce Mantuano (Environmental Management, 2025)

Epstein-barr virus (EBV) in cervical carcinoma detected by in situ hybridization targeting ebers and the viral genome - Álife Diêgo Lima Silva; Julia Graziele Alves Marelli; Maria Willaiara Lira Lopes; Myrella Tavares Rodrigues; Cecília Paz Lopes; José Nairton Coelho Silva; Sávio Samuel Feitosa Machado; Racquel Oliveira da Silva Souza; Maria Aparecida Tibúrcio; Alexandre Quental Sampaio; Isabelle Joyce de Lima Silva Fernandes; Claudia do Ó Pessoa; et al. (Brazilian Journal of Microbiology, 2025)

Targeting Trypanosoma cruzi with silver and gold-based N-heterocyclic carbene complexes: insights into parasite death and trypanothione reductase interaction - Yuly Bernal; Angie Melo Marquez; Hector Rafael Rangel; Maria Cristina Goite; Pedro Noguera; Franmerly Fuentes; Rubén Machado; William Castro; Vaneza Paola Lorett Velasquéz; Cristian Buendia-Atencio; Eduvan Valencia Cristancho; Anny Karely Rodriguez; et al. (BioMetals, 2025)
Chagas disease remains a major public health challenge, and there is a need for new therapeutic agents. N-heterocyclic carbene (NHC) complexes, particularly those linked to silver or gold, have shown significant anticancer, antimicrobial, and antiparasitic activities. This study aimed to evaluate the efficacy of four NHC compounds (QMT3, QMT4, QMT7, and QMT8) against Trypanosoma cruzi , the causative agent of Chagas disease. In vitro assays revealed that QMT3 and QMT8 exhibited the strongest antiparasitic effects, with QMT3 showing the highest potency and stability over time (IC₅₀ = 10.3 µg/mL at 24 h). Both compounds induced rapid, irreversible cell death in epimastigotes, primarily through late apoptotic-like and necrotic pathways, as evidenced by Annexin V/PI labeling. Additionally, treatment with QMT3 and QMT8 led to significant increases in intracellular reactive oxygen species (ROS), particularly superoxide (SO). Notably, both compounds displayed high specificity for the parasite with low cytotoxicity towards mammalian cells, although QMT8 was less toxic to host cells than QMT3 at short exposure times. Molecular modeling studies revealed that QMT3, and QMT8 bind to the active site of TryR, a crucial player in maintaining redox homeostasis in trypanosomatids, potentially competing with its natural ligand and disrupting its enzymatic function. These findings suggest that QMT3 and QMT8, silver- and gold-based NHC complexes, act through redox system disruption and TryR inhibition, positioning them as promising candidates for the development of new treatments for Chagas disease.

Toxicity of λ-cyhalothrin and fenpyroximate on Nannotrigona testaceicornis - Jaíne Santos Rebouças; Jefferson Alves dos Santos; Maiara Janine Machado Caldas; Maria Angélica Pereira de Carvalho Costa; Ana Tereza Bittencourt Guimarães; Nuno G. C. Ferreira; Carlos Alfredo Lopes de Carvalho (Environmental Science and Pollution Research, 2025)
The use of pesticides in agriculture is linked to pollinators’ decline, which also impacts crop productivity. Determining pesticide effects on pollinating bees is of utmost importance for defining crop management strategies and public policies. This study assessed the toxicity of λ-cyhalothrin and fenpyroximate in Nannotrigona testaceicornis bees through three exposure routes (ingestion, topical and contact). The concentrations were selected based on field application doses and median lethal concentration for social bee species. Survival and behavioural changes were assessed up to 96 h of exposure. Data showed that λ-cyhalothrin caused a significant decrease in bee survival in all exposure routes, while fenpyroximate did not cause any lethal effect. The Bees’ Behavioural Stress Index (BSI) was created as a simple tool to assess behavioural changes, allowing for the identification of stress levels and significant differences from control groups. The data presented here can be used for protecting stingless bees and as a standard testing method.

Experimental assessment of beauvericin toxicity in tadpoles of Dendropsophus minutus (Anura: Hylidae) - Monica Chacon de Vicente; Luiza Gabriella Ferreira de Paula; Renata Maria Pereira de Freitas; Adieli dos Anjos Almeida; Diego da Silva Lima; Rebeca dos Santos Gabriel; Nathany Geraldino Nogueira; Nádya Raquel dos Santos Batista; Alexandre Có Mangoni Barros; Marcelino Benvindo de Souza; Rogério Pereira Bastos; Pedro Vale de Azevedo Brito; et al. (Toxicon, 2025)

Global warming impacts on lactating mammalian milk: A systematic review - Artur Nogueira de São José; Maria Cândida Ferrarez Bouzada Viana; Márcia Gomes Penido Machado; Sophia Livas de Morais Almeida; Ursula do Carmo Resende; Hilton de Oliveira Mota; Marcelo Lopes Pereira Júnior; Adson Ferreira da Rocha; Daniel Orquiza de Carvalho; Paulo de Jesus Hartmann Nader; Zilma Silveira Nogueira Reis (Science of The Total Environment, 2025)

Sustainable aqueous extraction of Brazilian varieties avocado oil: Effects on yield, physical and chemical properties, fatty acids and Triacylglycerols - Diego Fernando García-Ramón; Joanna Cios; Maria Eduarda Machado Soares; João Pedro Fernandes de Sant'Ana; Juliane Viganó; Christianne Elisabete da Costa Rodrigues; Caroline West; Alessandra Lopes de Oliveira (Food Chemistry, 2025)

Zoonotic variants of Bartonella henselae in domesticated cats, including blood donors, in central-western Brazil - Lorena Freitas das Neves; Clara Morato Dias; Anna Claudia Baumel Mongruel; Gabrielly de Oliveira Lopes; Liliane Maria do Rosario Batista; Francisco Anilton Alves Araujo; Gener Tadeu Pereira; Rosangela Zacarias Machado; Marcos Rogério André (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Cordiaquinone B induces cytotoxicity and oxidative stress-mediated apoptosis in human colorectal cancer cells in vitro and in vivo - Stéphanie Aguiar de Negreiros Matos Silva; Fabrício dos Santos Machado; Luciano de Souza Santos; Maria Victoria Lima de Castro; Mateus Lima Nogueira; Milena Botelho Pereira Soares; Simone Alves Serafim Rocha; Renata Mendonça Araújo; Rosane Borges Dias; Daniel Pereira Bezerra; Ana Jérsia Araújo; José Delano Barreto Marinho Filho (Chemico-Biological Interactions, 2025)

Physicochemical and structural changes of cassava starch modified by pyrodextrinization with glacial acetic acid as catalyst - Erivan de Souza Oliveira; Mighay Lovera; Alex Altair Costa Machado; Lorena Maria Freire Sampaio; Kelvi Wilson Evaristo Miranda; Angelo Roncalli Alves e Silva; Maria do Socorro Rocha Bastos; Ana Cristina de Oliveira Monteiro Moreira (Biocatalysis and Agricultural Biotechnology, 2025)

Corrigendum to “Silver nanoparticles for control of foliar pathogens in passion fruit (Passiflora edulis) crops” [Biocatal. Agric. Biotechnol. 68 (2025) 103717] - Natália Deniz Brito; Rafael José Vilela de Oliveira; Felipe Leon Nascimento de Sousa; Ana Júlia Silva Rocha; Maria Eduarda Almeida Matos; Laura Lima Turani; Raphael Ferreira Queiroz; Bianca Galúcio Pereira Araújo; Giovanna Machado; Quelmo Silva de Novaes (Biocatalysis and Agricultural Biotechnology, 2025)

Coxiella burnetii in ruminants from Somalia - Aamir M. Osman; Ahmed A. Hassan-Kadle; Igor S. Silito; Caroline Tostes Secato; Abdalla M. Ibrahim; Maria Carolina A. Serpa; Marcos R. André; Thállitha S. W. J. Vieira; Marcelo B. Labruna; Rosangela Z. Machado; Rafael F. C. Vieira (Tropical Animal Health and Production, 2025)
Q fever in humans and coxiellosis in ruminants are caused by Coxiella burnetii , a zoonotic obligate intracellular bacterium. This infection poses significant health and economic risk. Effective control strategies rely on a thorough understanding of their epidemiology. In this study, we examined the prevalence of C. burnetii in 372 ruminants (190 goats, 133 cattle, and 49 sheep) from the Lower Shabelle and Benadir Regions of Somalia. Diagnostic testing was performed using a quantitative PCR (qPCR) assay that targets the bacterium’s repetitive element IS111 and the Indirect Fluorescent Antibody Test (IFAT) against the C. burnetii strain At12. A total of 47 out of 372 (12.6%) ruminants tested positive for anti- Coxiella burnetii IgG antibodies, with seropositivity detected in 40 out of 190 goats (21.1%) with endpoint titers ranging from 64 to 2,048, and 7 out of 49 sheep (14.3%) with endpoint titers ranging from 64 to 8,192, while all cattle tested negative. Notably, only one goat that was seropositive also tested positive for C. burnetii by qPCR, while all other ruminants were negative. These findings provide evidence of the presence of C. burnetii in Somali livestock, emphasizing its public health risk and highlighting the necessity for targeted surveillance and control strategies to prevent zoonotic transmission.

Exploring leaf anatomy in Athenaea species (Solanaceae Juss.): studying secondary metabolite diversity and potential taxonomic characters - João Victor da Costa Santos; José Danizete Brás Miranda; Fabiano Machado Martins; Izabella Martins da Costa Rodrigues; João Paulo Viana Leite; Renata Maria Strozi Alves Meira (Protoplasma, 2025)

Quantification of heterocyclic aromatic compounds (NSO-HET) in fuels by offline HPLC-GC×GC-ToFMS - Pedro Victor Bomfim Bahia; Anaïs Rodrigues; Aleksandra Gorska; Paula Albendea; Djulia Bensaada; Pierre-Hugues Stefanuto; Jean-François Focant; Giorgia Purcaro; Maria Elisabete Machado (Analytica Chimica Acta, 2025)

Oleic acid supplementation increases the PGE2:PGF2α ratio and alters expression of prostaglandin biosynthesis and maternal pregnancy recognition genes in bovine trophoblast cells in vitro - Valeska de Castro Lourenço; Letícia de Oliveira; Mariângela Bueno Cordeiro Maldonado; Laura Chuba Machado Rolniche; Lucas de Oliveira Bezerra; Isabella Rio Feltrin; Karine Galhego Morelli; Adriano Felipe Mendes; Cecilia Constantino Rocha; Caliê Castilho; Alessandra Bridi; Guilherme Pugliesi; et al. (Theriogenology, 2025)

Effects of adding equine chorionic gonadotropin (eCG) to cloprostenol-based estrus synchronization protocol on luteogenesis, pregnancy rate, and embryo development in cyclic dairy goats - Luana Rangel Côrtes; Juliana Nascimento Duarte Rodrigues; Gabriel Brun Vergani; Lucas Machado Figueira; Paulo Sergio Cerqueira Rangel; Ribrio Ivan Tavares Pereira Batista; Bruna Waddington de Freitas; Felipe Zandonadi Brandão; Joanna Maria G. Souza-Fabjan; Jeferson Ferreira Fonseca (Small Ruminant Research, 2025)

Potential immunoprophylactic use of a multi-epitope protein of CD4+ and CD8+ T cells against visceral leishmaniasis in Balb/c mice - Scarleth Silva Costa; Naianda Rezende Ribeiro; Luiza dos Reis Cruz; Gabriel José Lucas Moreira; Vivian Tamietti Martins; Daniela Pagliara Lage; Danniele Luciana Vale; Camilly Vitória Silva Costa; Nathalia Coral Galvani; Gabriel Paulino Luiz; Maria Eduarda de Oliveira; Ricardo Andrez Machado-de-Ávila; et al. (Research in Veterinary Science, 2025)

Stress memory increases cane yield and juice quality of field-grown sugarcane - Maria D. Pissolato; Larissa P. Cruz; Rafael L. Almeida; Tamires S. Martins; Eduardo C. Machado; Júlio C. Garcia; Marcos G.A. Landell; Mauro A. Xavier; Rafael V. Ribeiro (Plant Science, 2025)

Phytochemical composition and biological activities of Pleroma granulosum (Melastomataceae) leaf extract - Thaywane Azevedo Marquesa; Débora Machado de Lima; Anna Lívia Oliveira Santos; Carlos Henrique Gomes Martins; Carla de Moura; Alberto de Oliveira; Raquel Maria Ferreira Sousa (Phytochemistry Letters, 2025)

Antibacterial and cytotoxic activities of bark and branches extracts from Lafoensia replicata Pohl (Lythraceae) - Débora Machado de Lima; Ana Carolina Costa Santos; Carlos Ueira-Vieira; Matheus Reis Santos de Melo; Denise Crispim Tavares; Raquel Maria Ferreira Sousa (Phytochemistry Letters, 2025)

Application of encapsulated tomato by-product extract as a colorant in mascarpone - Adriana K. Molina; Maria G. Leichtweis; Manuela Machado; Sara Silva; Manuela Pintado; João C.M. Barreira; Maria Inês Dias; Miguel Á. Prieto; Lillian Barros; Carla Pereira (Food Research International, 2025)

Ecotoxicological assessment of pesticide mixtures: effects of imidacloprid and propiconazole on Danio rerio and Astyanax lacustris - Maria Vitória Raupp Sebastião; Johana Marcela Concha Obando; Davi da Silva Nascimento; Angela Hisamitsu Carolino; Gisele de Souza Silva; Beatriz Pellis; Nicole Grasmuk Israel; Eduardo Alves de Almeida; Carlos Augusto Prata Gaona; Guilherme Wolff Bueno; Levi Pompermayer Machado; Ana Leticia Madeira Sanches (Aquatic Toxicology, 2025)

Processed-kaolin particle film can mitigate solar radiation damage in young Atlantic Forest species - Amanda Lúcia Pereira Machado da Silva; Guilherme Augusto Rodrigues de Souza; Rosana Maria dos Santos Nani de Miranda; Diesily de Andrade Neves; Larissa Crisostomo de Souza Barcellos; Silas Magno Medeiros Garonce; Moises de Souza Marcelino; Newton de Matos Roda; Paulo Ricardo dos Santos; Cláudia Franca Barros; Eliemar Campostrini (Trees, 2025)

Assessment of petroleum hydrocarbons and ecotoxicity level in marine sediments after the mysterious 2019 oil spill in Northeast Brazil - Thayane Cristina da Silva Moreira; Estefani Santana do Nascimento; Cristiane Maria Varela de Araújo-Castro; Alex Souza Moraes; Jandyson Machado Santos (Journal of Soils and Sediments, 2025)

Correction to: Mapping family farming in brazil’s midwest: assessing socioeconomic and environmental factors for enhancing regional food security - Lucas de Almeida Moura; Caroline de Oliveira Gallo; Francisco Chiaravalloti Neto; Alisson Diego Machado; Marina Maintinguer Norde; Giovanna Garrido; Nadine Marques Nunes Galbes; Aline Martins de Carvalho; Dirce Maria Lobo Marchioni (Food Security, 2025)

Mapping family farming in Brazil’s Midwest: Assessing socioeconomic and environmental factors for enhancing regional food security - Lucas de Almeida Moura; Caroline de Oliveira Gallo; Francisco Chiaravalloti Neto; Alisson Diego Machado; Marina Maintinguer Norde; Giovanna Garrido; Nadine Marques Nunes Galbes; Aline Martins de Carvalho; Dirce Maria Lobo Marchioni (Food Security, 2025)

Conjugated linoleic acid supplementation: Insights into prostaglandin synthesis and in vitro embryonic development - Mariângela Bueno Cordeiro Maldonado; Dayane Colhados Cabrini; Lucas de Oliveira Bezerra; Laura Chuba Machado Rolniche; Valeska de Castro Lourenço; Isabella Rio Feltrin; Karine Galhego Morelli; Adriano Felipe Mendes; Cecilia Constantino Rocha; Alessandra Bridi; Guilherme Pugliesi; Marcelo Fábio Gouveia Nogueira; et al. (Animal Reproduction Science, 2025)

Effects of the inclusion of a rumen-protected B-vitamin blend and hydroxy trace minerals in the diets of confined Nellore cattle on performance and cecal and ruminal histology - Maria Carolina Gonçalves de Arruda; Rodrigo de Nazaré Santos Torres; Daniela Bernadete Rozza; Luis Arthur Loyola Chardulo; Welder Angelo Baldassini; Rogério Abdallah Curi; Guilherme Luis Pereira; Iasmin Myrele Santos Calaça de Farias; Marco Aurélio Porcionato; Otávio Rodrigues Machado Neto (Animal Feed Science and Technology, 2025)

Silver nanoparticles for control of foliar pathogens in passion fruit (Passiflora edulis) crops - Natália Deniz Brito; Rafael José Vilela de Oliveira; Felipe Leon Nascimento de Sousa; Ana Júlia Silva Rocha; Maria Eduarda Almeida Matos; Laura Lima Turani; Raphael Ferreira Queiroz; Bianca Galúcio Pereira Araújo; Giovanna Machado; Quelmo Silva de Novaes (Biocatalysis and Agricultural Biotechnology, 2025)

Potential use of petroleum drilling waste in the substrate mixture to produce seedlings native to South America - Victória Maria Monteiro Mendonça; Matheus Severo de Souza Kulmann; Yan Vidal de Figueiredo Gomes Diniz; José Henrique Camargo Pace; Dione Richer Momolli; Alan Henrique Marques de Abreu; Júlio César Ribeiro; Marcos Vinicius Winckler Caldeira; José Carlos Arthur Júnior; Jorge Makhlouta Alonso; Deivid Lopes Machado; Gilsonley Lopes dos Santos; et al. (New Forests, 2025)

Respiratory virus circulation during pandemic: Why were some viruses still circulating? - Eva Maria de Assis Carvalho; Katia Ozanic; Alessandra Ferreira Barbosa Machado; Vanessa Cordeiro Dias; Claudio Galuppo Diniz; Vania Lucia da Silva; Nancy Bellei; Aripuanã Watanabe (Brazilian Journal of Microbiology, 2025)

A multispecies microcosm to assess the effect of footwear wastes on soil biota: a contribution towards sustainability - Beatriz Fernandes; Verónica Nogueira; Sirine Bouguerra; Cristiano Soares; Fernanda Fidalgo; Joana Machado; Susana M. P. Carvalho; Maria José Ferreira; Vera Pinto; José Rodrigues; Carlos M. Pereira; Ruth Pereira (Environmental Science and Pollution Research, 2025)
Due to the high quantities of solid waste with high concentrations of chromium that the footwear industry produces and its disposal sites, it is vital to understand whether leather residue itself is harmful to the ecosystem. Thus, a microcosm test with multispecies ( Brassica oleracea and Eisenia fetida ) was carried out using an agricultural soil contaminated with two different leather residues (Wet Blue and Finished Leather) from the footwear industry. After the stabilization period, Brassica oleracea seedlings and Eisenia fetida adults were exposed to these treatments. At the end of the experiment, a series of parameters were analysed in the B. oleracea leaves (leaf chlorophyl content, gas exchange measurements and photosynthetic parameters), in the E. fetida organisms (alkaline comet assay and biomarkers such as acetylcholinesterase and lipid peroxidation) and in the soils (total chromium content, enzymes activity and nitrogen mineralization and potential nitrification). In the case of soil’s enzymatic activity, even though some were significantly altered, no negative effects could be attributed to the leather residues. Moreover, the addition of residues to the soil did not significantly affect the plant species; however, the same was not observed for the earthworm E. fetida when in contact with Finished Leather. Overall, Finished Leather residue was the one that caused more effects on the parameters analysed and therefore its disposal should be carefully examined.

Thermal comfort and seminal traits in stallion reproduction: New methods to understand these relationships - Luiza Maria Feitosa Ribeiro; João Victor Bersot Gomes; Wilder Hernando Ortiz Vega; Andressa da Silva Alves; Maurício Netto Machado; Luan Junio Wutke; Célia Raquel Quirino; Roberta Carvalho Basile; Paula Alessandra Di Filippo (Journal of Equine Veterinary Science, 2025)

Bronchopneumonia by Granulicatella balaenopterae in a humpback whale (Megaptera novaeangliae) - Anderson Hentz Gris; Derek Blaese de Amorim; Gabriela Merker Breyer; Fernanda Felicetti Perosa; Manoela Marchezan Piva; Emanoelly Machado Sousa da Silva; Larissa Caló Zitelli; Maria Eduarda Rocha Jacques da Silva; Mariana Costa Torres; Elisandro Oliveira dos Santos; Vanessa Lanes Ribeiro; Franciele Maboni Siqueira; et al. (Veterinary Research Communications, 2025)

How shade impacts the fitness of Euterpe edulis saplings, a palm tree from the Atlantic Forest biome - Takefumi Ushimaru; Sérgio Yoshimitsu Motoike; Kacilda Naomi Kuki; Débora Durso Caetano Madeira; Geís Ferreira Neves; Maria Antônia Machado Barbosa (Plant Ecology, 2025)

3-(3-(diethylamino)propyl)-2-(4-(methylthio)phenyl)thiazolidin-4-one Attenuates Scopolamine-induced Cognitive Impairment in Rats: Insights Into Neuroprotective Effects - Anita Avila de Souza; Kelen Cristiane Machado Goularte; Raphaela Cassol Piccoli; Solange Vega Custódio; Julia Eisenhardt de Mello; Melinda Gomes Victor; William Borges Domingues; Lucas Petitemberte de Souza; Laís dos Santos Gonçalves; Vinicius Farias Campos; Wilson Cunico; Jean Pierre Oses; et al. (Molecular Neurobiology, 2025)

Effects of Metformin Treatment Against Endometrial Cancer Cells Cultured In Vitro or Grafted into Female Balb/C Nude Mice: Insights into Cell Response and IGF-1R and PI3K/AKT/mTOR Signaling Pathways - Vânia Marísia Santos Fortes dos Reis; Franciely Machado Ramos; Henrique Leal de Oliveira; Fernanda Dapper Machado; Sara Hartke; Amanda Machado-Weber; Ariane Germeyer; Thomas Strowitzki; Lúcia Maria Kliemann; Helena von Eye Corleta; Ilma Simoni Brum; Edison Capp; et al. (Cell Biochemistry and Biophysics, 2025)

Characterization and pathogenicity of Colletotrichum species causing anthracnose on pitaya (Hylocereus spp.) in Brazil - Maria Hilma dos Santos; Jaqueline Figueredo de Oliveira Costa; Kevison Romulo da Silva França; Taciana Ferreira dos Santos; Mayra Machado de Medeiros Ferro; Maruzanete Pereira de Melo; Victor Breno Campelo Lima; Jorge Luiz Xavier Cunha; Gaus Silvestre de Andrade Lima; Iraildes Pereira Assunção (Physiological and Molecular Plant Pathology, 2025)

An innovative carbonated beverage based with milk permeate and prebiotics - Roberta Cristina L.G.S. Lasset; Elson Rogério T. Filho; Tatiana C. Pimentel; Jonas T. Guimarães; Marcello R. Silveira; Elane S. Prudêncio; Maria Terezinha S.L. Neta; Eliane T. Mársico; Monica Q. Freitas; Gisela M. Machado; Junio Cesar J. Paula; Adriano G. Cruz (Food Research International, 2025)

Microalgae as innovative mineral and nutrient carriers; potential applications in soil improvement and animal nutrition - María del Rosario Martínez-Macias; Omar Nateras-Ramírez; Dalia Isabel Sánchez-Machado; Jaime López-Cervantes; Joel Arias-Martínez; Luz Angélica Ávila-Villa; Maria Magdalena Armendariz-Ontiveros; Jael Teresa de Jesús Quintero-Vargas; Yedidia Villegas-Peralta (Food and Bioproducts Processing, 2025)

Association between temperature and snakebite incidents in the state of Rio Grande do Sul, Brazil - Livia da Silva Freitas; Fernanda Machado da Silva; Paula Florencio Ramires; Gabriella Mello Gomes Vieira de Azevedo; Bruno Martins da Costa Batista; Rafael Kenji Anzai; Isabela da Silva Pereira; Matheus Pissarelli; Fabiano Morezi de Andrade; Romina Buffarini; Xesús Feás; Selma Maria Almeida-Santos; et al. (Theoretical and Applied Climatology, 2025)

Morphophysiological responses of tree species under shading levels in the field as a function of climatic seasonality - Júlia Luiza Stahl; Maristela Machado Araujo; Adriana Maria Griebeler; Suelen Carpenedo Aimi; Felipe Turchetto; Claudia Costella; Vanessa Viera Trindade de Oliveira (International Journal of Biometeorology, 2025)

Threats and challenges for the conservation of marine molluscs in the southwestern Atlantic - Cristiane Xerez Barroso; Eliane Pintor de Arruda; Florencia Arrighetti; Andrés Averbuj; Gregorio Bigatti; Ramiro Braga; Alvar Carranza; Susete Wambier Christo; Mariana Osório Côrtes; Paulo Márcio Santos Costa; Mariano Cumplido; Omar Defeo; et al. (Aquatic Sciences, 2025)

Morphological Insights into Echinometra lucunter Spines Reveal Cellular Sources of Bioactive Molecules - Juliana Mozer Sciani; Marta Maria Antoniazzi; Carlos Jared; José Roberto Machado Cunha da Silva; Daniel Carvalho Pimenta (Oceans, 2025)
Echinometra lucunter, the most abundant sea urchin in Brazil, causes numerous accidents by puncture wounds, primarily on hands and feet. Beyond mechanical trauma, recent research has identified bioactive molecules in spine extracts and coelomic fluid contributing to these inflammatory reactions. This study investigated spine morphology to better understand the envenomation and defense processes for the animal. Using various microscopy techniques, the spines were revealed to be mineral structures with longitudinal canals and a sponge-like central mesh rich in granular cells. These cells extend from the spine’s center to its edges, terminating in fimbriae-like structures, likely involved in molecular exchange with the environment. The spine tip is more cellular than the base, suggesting a defensive role, while the base provides structural support. Several cell types were identified, including granulocytes, red spherulocytes, and phagocytic amoebocytes, also found in the coelomic fluid. Other cells displayed prominent Golgi apparatuses and secretory granules, indicating specialized secretory functions, likely the source of bioactive molecules involved in chemical defense and spine regeneration. Understanding this cellular structure is crucial for comprehending the urchin’s envenomation and defense mechanisms.

Brazil nut (Bertholletia excelsa Bonpl.) in health and disease: A narrative review - Larissa Naomi Takeda; Amanda Omine; Lucas Fornari Laurindo; Adriano Cressoni Araújo; Nathália Mendes Machado; Jefferson A. Dias; Joachim Kavalakatt; Sabyasachi Banerjee; Ricardo de Alvares Goulart; Atanas G. Atanasov; Anupam Bishayee; Sandra Maria Barbalho (Food Chemistry, 2025)

Phytochemical and chemometric investigation of morphotypes of Calophyllum brasiliense Cambess. (Calophyllaceae) in the mountainous region of Espírito Santo, Brazil - Lucas Evangelista dos Santos; Maria Gabriela Pissinati Trindade; Vanessa Silva dos Santos; Isadora Maria Coelho Vieira; Ricardo Machado Kuster; Maria do Carmo Pimentel Batitucci (Biochemical Systematics and Ecology, 2025)

Evaluation of clinical and hematological parameters in pregnant ewes naturally infected by Haemonchus contortus - Franciele Delevati de Oliveira; Natália Freddo; Natalie Renata Zorzi; Luciana Grazziotin Rossato Grando; Márcio Machado Costa; Wagner Antonio Tamagno; Maria Isabel Botelho Vieira (Tropical Animal Health and Production, 2025)

Selection signatures detection in Nelore, Gir, and Red Sindhi cattle breeds - Maria Victória Henrique Genuíno; Ayrton Fernandes de Oliveira Bessa; Roney Teixeira da Silva; Giovanna Maria dos Santos Câmara; João Cláudio do Carmo Panetto; Marco Antônio Machado; Sabrina Luzia Caetano; Salvador Boccaletti Ramos; Danísio Prado Munari; Tad Sonstegard; Marcos Vinícius Gualberto Barbosa da Silva; Marcos Eli Buzanskas (Mammalian Genome, 2025)

Toxicity of Melaleuca rhaphiophylla essential oils against Sitophilus zeamais and Sitophilus oryzae - Rubens Candido Zimmermann; Ana Marta Schafaschek; Adélia Maria Bischoff; Matheus Beger; Julia Sant’ana; Sofia Bin de Macedo; Milena Ielen; Carlos Eduardo Nogueira Martins; Sarah da Costa Amaral; Rilton Alves de Freitas; Alessandra Benatto; Carolina Gracia Poitevin; et al. (Journal of Pest Science, 2025)

Correction: first report of Colletotrichum siamense and Colletotrichum theobromicola causing anthracnose on achachairu (Garcinia humilis) - Caio Vitor da Silva Anjos; Denise de Santana Silva; Kevison Romulo da Silva França; Mayra Machado de Medeiros Ferro; Jaqueline Figueredo de Oliveira Costa; João Narciso de Melo Marques; Maria Gabriela Monteiro de Carvalho Andrade; Iraildes Pereira Assunção; Gaus Silvestre de Andrade Lima (Australasian Plant Pathology, 2025)

Detection of white sand patches in central Amazonia using remote sensing and meteorological data - Nikolai S. Espinoza; Maria Teresa F. Piedade; Layon O. Demarchi; Gisiane R. Lima; Angélica F. Resende; Rosaria R. Ferreira; Francisco Alcinei G. Silva; Luiz Augusto T. Machado; Jochen Schörgart (International Journal of Remote Sensing, 2025)

Unconventional polycyclic aromatic compounds distribution profiles in sediment cores collected from Todos os Santos Bay, Northeastern Brazil - Eileen Rocio Niño-Zambrano; Pedro V.B. Bahia; Madson M. Nascimento; Fábio X.A. Sampaio; Ricardo da S. Duarte; Vanessa Hatje; Maria Elisabete Machado; Jailson B. de Andrade; Gisele O. da Rocha (Journal of Hazardous Materials, 2025)

EHMT2 as a Candidate Gene for an Autosomal Recessive Neurodevelopmental Syndrome - Laura Machado Lara Carvalho; Jessica Rzasa; Jennifer Kerkhof; Haley McConkey; Veniamin Fishman; Galina Koksharova; Alexander Augusto de Lima Jorge; Elisa Varella Branco; Danyllo Felipe de Oliveira; Beatriz Martinez-Delgado; Maria J. Barrero; Tjitske Kleefstra; et al. (Molecular Neurobiology, 2025)

Ayahuasca Pretreatment Prevents Sepsis-Induced Anxiety-Like Behavior, Neuroinflammation, and Oxidative Stress, and Increases Brain-Derived Neurotrophic Factor - Rick Wilhiam de Camargo; Larissa Joaquim; Richard Simon Machado; Suelen de Souza Ramos; Lara Rodrigues da Rosa; Linério Ribeiro de Novais Junior; Khiany Mathias; Lara Maximiano; Yasmin Ribeiro Strickert; Rafael Nord; Maria Laura Gava; Eduarda Scarpari; et al. (Molecular Neurobiology, 2025)

The microbiota playing “musical chairs” in a glacier retreat zone of maritime Antarctica - Tomás Gomes Reis Veloso; José Maria Rodrigues da Luz; Marliane de Cássia Soares da Silva; José João Lelis Leal Souza; Larissa Marcia Anastácio; Tiago Iglésias Machado; Mateus Ferreira de Santana; Carlos Ernesto Gonçalves Reynaud Schaefer; Maria Catarina Megumi Kasuya (Applied Soil Ecology, 2025)

Molecular evolution of coxsackievirus A6 associated with atypical hand, foot, and mouth disease in Northern Brazil in 2019 - Raiana Scerni Machado; Ivanildo Pedro de Sousa; Wanderley Dias das Chagas Júnior; James Lima Ferreira; Daniela Pereira Lopes; Maria Cleonice Aguiar Justino; Fernando Neto Tavares (Archives of Virology, 2025)

The impact of modafinil on memory and brain oxidative stress: contrasting effects of acute and chronic administration in healthy rats - Jorge M. Aguiar-Geraldo; Bruno Spalenza da Silva; Taise Possamai-Della; Maria Luísa Machado-Laureano; Aline Vitoreti-Vargas; João Quevedo; Samira S. Valvassori (Metabolic Brain Disease, 2025)

Exposure to Oil Spill Among Fishers on the Brazilian Coast in 2019/2020 - Louise Oliveira Ramos Machado; Rita de Cássia Franco Rêgo; Amanda Laura Northcross; Armando Meyer; Luize da Silva Rezende Mota; Charlene da Silva; Paulo Gomes de Jesus Lino; Lilia Carolina Carneiro da Costa; Ruy Kenji Papa de Kikuchi; Verônica Maria Cadena Lima (Journal of Agromedicine, 2025)

Antitumor and antiproliferative potential of crotoxin in triple negative breast tumors - De Andrade Camila Marques; Machado Cleni Mara Marzocchi; De Castro Fabíola Attié; Teixeira Natércia; Amaral Cristina; Campos Felipe; Canicoba Nathália Cristina; Torqueti Maria Regina (Toxicon, 2025)

Resilience in adversity: Exploring adaptive changes in cancer cells under stress - Taissa dos Santos Uchiya; Helena Napoli da Cunha; Matheus Correia Casotti; Giulia de Souza Cupertino de Castro; Gabrielle Feu Pereira; João Augusto Diniz Moura; André Manhães Machado; Fabio Victor Vieira Rocha; Lorena Souza Rittberg Mauricio; Victor Alves Lopes; Fellipe Pesente; Giulia Maria Giacinti; et al. (Tissue and Cell, 2025)

An integrated analysis of the use and potential risks of pharmaceutical drugs in hospital wastewater: Consumption and occurrence by suspect screening analysis, and antibiotic resistance - Eloísa Stéphanie da Silva; Raquel W. Becker; Maria Clara V.M. Starling; Elayne C. Machado; Ana Paula V. Reis; Ananda Pereira Aguilar; Tiago Antônio de Oliveira Mendes; Carla Sirtori; Camila C. Amorim (Science of The Total Environment, 2025)

A reassessment of the type-materials of Ostracoda (Crustacea, Oligostraca) lost in the “Museu Nacional” Great Fire of September 2, 2018 - Lucas Silveira Antonietto; David Ian Machado Alves; Cláudio Magalhães Almeida; Dermeval Aparecido do Carmo; Vera Maria Medina da Fonseca (Revue de Micropaléontologie, 2025)

First report of Colletotrichum siamense and Colletotrichum theobromicola causing anthracnose on achachairu (Garcinia humilis) - Caio Vitor da Silva Anjos; Denise de Santana Silva; Kevison Romulo da Silva França; Mayra Machado de Medeiros Ferro; Jaqueline Figueredo de Oliveira Costa; João Narciso de Melo Marques; Maria Gabriela Monteiro de Carvalho Andrade; Iraildes Pereira Assunção; Gaus Silvestre de Andrade Lima (Australasian Plant Pathology, 2025)

Multiple mechanisms of action of a triazole-derived salt against Leishmania amazonensis: Apoptosis-like death and autophagy - Andrezza Rodrigues de Souza; Luciana Maria Ribeiro Antinarelli; Ari Sergio de Oliveira Lemos; Nicolas Glanzmann; Bruno Vicente; Victor do Valle Midlej; Adolfo Firmino da Silva Neto; Rachel Rocha Pinheiro Machado; Adilson David da Silva; Elaine Soares Coimbra (Chemico-Biological Interactions, 2025)

Viral diversity in stool samples of fur seals from Antarctica using metagenomic shotgun - Tatiana Prado; Daniel Andrade Moreira; Maithê Gaspar Pontes Magalhães; Letícia Ferreira Lima; Martha Lima Brandão; Marcia Chame; Luciana Leomil; Maria Ogrzewalska; José Paulo Gagliardi Leite; Wim Maurits Sylvain Degrave; Marize Pereira Miagostovich; Tulio Machado Fumian (Polar Biology, 2025)

The roles of periostin derived from cancer-associated fibroblasts in tumor progression and treatment response - Yasmin De Oliveira Macena; Maria Eduarda Nunes Cezar; Cinthya Brunelly Ferreira Lira; Laryssa Bheatriz Dantas Machado De Oliveira; Thais Noronha Almeida; Ana Dora Alecio Virtuoso Costa; Bernardo Mansur Dantas De Araujo; Durval de Almeida Junior; Henrique Macêdo Dantas; Emanuel Cézar De Mélo; Sandra Taveiros de Araújo; Raimundo Rodrigues de França Júnior; et al. (Cancer and Metastasis Reviews, 2025)

Carbon-dot pequi-nut in the development of immunosensor to detect pathogenic bacteria - Rachel Menezes Castelo; Marília de Albuquerque Oliveira; Roselayne Ferro Furtado; Bruno Peixoto de Oliveira; Lucas Vinicius Leite Martoni; Terezinha Feitosa Machado; Celli Rodrigues Muniz; Flávia Oliveira Monteiro da Silva Abreu; Sérgio Antônio Spinola Machado; Airis Maria Araújo Melo; Huai N. Cheng; Atanu Biswas; et al. (Brazilian Journal of Microbiology, 2025)

Highly resistant Salmonella Heidelberg circulating in broiler farms in southern Brazil - Bianca Fagundes Saggin; Karen Apellanis Borges; Thales Quedi Furian; Gustavo da Rosa Fünkler; Rafael Mollerke; Manuela Machado Cenci; Roberta de Castro Bönmann; Tiele Maria Feijó de Fraga; Daniela Tonini da Rocha; Hamilton Luiz de Souza Moraes; Vladimir Pinheiro do Nascimento (Brazilian Journal of Microbiology, 2025)

Spreading further: the first record of the alien bivalve Theora lubrica in the Southwestern Atlantic Ocean - Fabrizio Marcondes Machado; Cristiane Midori Suga; Fabio Kiyoshi Camara Onodera; Mariana Sousa Melo; Thais Viti; Vilma Maria Cavinatto; Ana Carolina da Rocha Lammardo; Carolina Yumi Yonamine; Regina Sawaia Sáfadi; Luis Antonio Nogueira-Junior; Luiz Fernando Maciel Oliva (Frontiers in Marine Science, 2025)
Biological invasions are globally recognized as one of the main drivers of biodiversity loss. Over the past four decades, there has been significant progress in understanding the mechanisms of alien species introduction into marine and estuarine environments. It is currently known that although humans can spread non-native species in various ways (e.g. aquaculture, vessel biofouling and oil and gas activities), ballast water is one of the most effective being considered one of the main threats to marine biodiversity. This pathway also appears to be the main transport vector to explain the spread of the exotic bivalve Theora lubrica (or Asian Semele) since the late 1950s. In this study, we report for the first time the presence of Asian Semele in the Southwestern Atlantic, specifically along the Southeast coast of Brazil. Furthermore, we also provide new insights into shell morphology, gross anatomy and ecological aspects, as well as the updated global distribution of this invasive alien species.

Healthcare delay in neurogenetic disorders of adult onset and the role of predictive genetic testing - Daniele Lima Rocha; Jordânia dos Santos Pinheiro; Gabriel Vasata Furtado; Thayne Woycinck Kowalski; Karina Carvalho Donis; Marta Chaves; Greice Chini; Thais Lampert Monte; Raphael Machado de Castilhos; Maria Luiza Saraiva-Pereira; Lavínia Schuler-Faccini; Laura Bannach Jardim (Journal of Community Genetics, 2025)

A new genus of Mycosphaerellaceae associated with leaf spots in Philodendron sp. from the Brazilian Atlantic forest - Jordana Alves da Silva Melo; Eliude dos Santos Oliveira da Silva; Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; Ana Elisa de Almeida Souza; Cristina Maria de Souza-Motta; André Luiz Firmino; Alexandre Reis Machado (Mycological Progress, 2025)

Ozonized water as a promising strategy to remove biofilm formed by Pseudomonas spp. on polyethylene and polystyrene surfaces - Tatiane Marques Santos; Maria Eduarda Teixeira Lopes; Ernandes Rodrigues de Alencar; Marcus Vinícius de Assis Silva; Solimar Gonçalves Machado (Biofouling, 2025)

Understanding the effects of Bothrops erythromelas and Bothrops leucurus venoms on human blood coagulation - Eduardo Oliveira Venancio de Lima; Lídia Jorge Tasima; Daniela Miki Hatakeyama; Maria Amélia Farias Rodrigues; Caroline Serino-Silva; Daniel Rodrigues Stuginski; Giovanni Perez Machado da Silveira; Benedito Carlos Prezoto; Kathleen Fernandes Grego; Sávio Stefanini Sant’Anna; Anita Mitico Tanaka-Azevedo; Karen de Morais-Zani (Toxicon, 2025)

Determining conditions for inactivation of multispecies biofilm cells by peracetic acid applying response surface methodology - Gabriel Silva Oliveira; Leonardo Luíz Freitas; Solimar Gonçalves Machado; Maria Cristina Dantas Vanetti (International Dairy Journal, 2025)

Origin of Rhithropanopeus harrisii (Crustacea: Panopeidae) invasion on the Southwest Atlantic coast - Renan C. Machado; Maria Cristina S. Cortinhas; Bianca Possamai; Luiz Felipe Cestari Dumont (Estuarine, Coastal and Shelf Science, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

New reports of Rhizopus and Mucor (Mucorales, Mucoromycota) causing post-harvest rot in tropical fruits in Brazil - Ana Elisa de Almeida Souza; André Luiz Cabral Monteiro de Azevedo Santiago; Amanda Cupertino de Queiroz Brito; Jordana Alves da Silva Melo; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Diseases and Protection, 2025)

Feeding ecology of the sympatric waterbirds in Neotropical floodplain - Rosa Maria Dias; Elaine Antoniassi Luiz Kashiwaqui; João Carlos Barbosa da Silva; Henrique Ortêncio Filho; Luiz Carlos Gomes; Geza Thaís Rangel e Souza; Raffael Marcos Tófoli; Marion Haruko Machado; Angelo Antonio Agostinho (Hydrobiologia, 2025)

High molecular weight polycyclic aromatic hydrocarbon (HMW-PAH) isomers: unveiling distinct toxic effects from cytotoxicity to oxidative stress-induced DNA damage - Lara Ferreira Azevedo; Cecilia Cristina de Souza Rocha; Marília Cristina Oliveira Souza; Ana Rita Thomazela Machado; Paula Pícoli Devóz; Bruno Alves Rocha; Lusania Maria Greggi Antunes; Fernando J. Uribe-Romo; Andres D. Campiglia; Fernando Barbosa (Archives of Toxicology, 2025)

Identification of a chordovirus hosted by Angelica lignescens - Sara Luna; Maria Susana Lopes; Eduardo Dias; Dinis Pereira; Artur da Câmara Machado; Duarte Mendonça (Journal of Plant Pathology, 2025)
Summary Angelica lignescens , an endangered plant species endemic to the Azores Archipelago and member of the Apiaceae family, was subjected to Next Generation Sequencing (NGS) virome analysis. This analysis revealed the presence of contigs associated with a virus member of the Chordovirus genus. Through RT–PCR and additional Sanger sequencing, the complete genome of the virus was assembled and provisionally named angelica chordovirus (AChV). The AChV has a genome length of 8145 nt, exhibiting a similar organization to the Trivirinae subfamily ( Betaflexiviridae family). Upon BLAST analysis, the highest genomic homology was uncovered with carrot chordovirus 4 (CChV4), displaying a nucleotide identity of 76%. Pairwise comparisons further emphasized this similarity, with 80% and 82% amino acid identity to the complete replicase and coat protein genes of CChV4, respectively. These values lie on the borderline of species demarcation criteria. Given that, to ensure precise classification, additional research is imperative to unravel the epidemiology and ecology of AChV. Furthermore, a more profound understanding of its impact on A. lignescens and its potential broader ecological implications is essential, especially concerning potential host crops.

First reports of Fusarium agrestense, F. gossypinum, F. grosmichelii and F. triseptatum causing cassava root rot in Pernambuco, Brazil - Jenifer Sthephanie Araujo da Silva; Ana Carla da Silva Santos; Carlos Alberto Fragoso de Souza; Diogo Paes da Costa; Amanda Cupertino de Queiroz Brito; Renan do Nascimento Barbosa; Erika Valente de Medeiros; Alexandre Reis Machado; Cristina Maria de Souza-Motta (Crop Protection, 2025)

Monogamy and sexual dimorphism: Evaluation of the morphometric relationship of body and secondary sexual structures in heterosexual pairs of Alpheus estuariensis Christoffersen, 1984 - Carla Janes Fernandes Alcantara; Ana Laura de Alcântara Pontes; Maria das Graças Ferreira Alcântara; Allysson Pontes Pinheiro; Whandenson Machado do Nascimento (Zoologischer Anzeiger, 2025)

Evaluation of the antimicrobial effect of oregano essential oil (Origanum vulgare) on cooked mussels (Perna perna) experimentally contaminated with Escherichia coli and Salmonella Enteritidis - Laura Ribeiro Cerqueira de Oliveira; Ana Carolina Monteiro de Barros da Cruz Machado; Carlos Eduardo de Freitas Guimarães Filho; Erick Almeida Esmerino; Flávia Aline Andrade Calixto; Eliana de Fátima Marques de Mesquita; Maria Carmela Kasnowski Holanda Duarte (Food Control, 2025)

Exploring the therapeutic potential of avocado oil: Insights into obesity metabolism and immune regulation through in vitro models - Manuela Machado; Eduardo M. Costa; Sara Silva; Ana Maria Gomes; Manuela Pintado (Biocatalysis and Agricultural Biotechnology, 2025)

Unveiling early-stage responses of sensitive traits to water stress in tropical maize: a characterization study of a public panel - Ingrid Pinheiro Machado; Fernanda Carla Ferreira de Pontes; Maria Valnice de Souza Silveira; Antônio Lucas Aguiar Lobo; Michele Jorge Silva Siqueira; Roberto Fritsche-Neto; Júlio César DoVale (Euphytica, 2025)

Characterization of useful plants cultivated in productive homegardens in a rural community in the semi-arid region of northeastern Brazil - Maria Nayane Batista de Sousa; José Ribamar de Sousa Júnior; Ernani Machado de Freitas Lins Neto; Julio Marcelino Monteiro (Agroforestry Systems, 2025)

Urea fertilization can reduce soil bacterial and archaeal diversity in agroforestry systems - Janerson José Coelho; Valéria Xavier de Oliveira Apolinário; Luciano Cavalcante Muniz; Maria Karoline de Carvalho Rodrigue de Sousa; Thaís Lima Figueiredo; Diana Valadares Pessoa; Leonardo de Jesus Machado Gois de Oliveira; Antônia Alice Costa Rodrigues; Kátia Pereira Coelho; Caio Roberto Soares Bragança; Joaquim Bezerra Costa (Agroforestry Systems, 2025)

Distance From Nest and Climate Explain Geographical Trends of Harvester Ant's Food Resource Use: A Multi‐Species Approach - Diego Anjos; Pedro Luna; Kleber Del‐Claro; Rodrigo G. Pol; Javier Lopez de Casenave; Helena Maura Torezan‐Silingardi; Martha L. Baena; Florencia Baudino; Judie Bronstein; Melissa Burt; Eduardo Calixto; Ana Laura Cao; et al. (Journal of Biogeography, 2025)
Main Animals not only forage for abundant and nearby resources, but their diets can also be influenced by abiotic and geographic factors. This often results in non‐random interactions among species. We investigate how seed density, distance from nest, abiotic (e.g., climate stability, temperature, precipitation) and geographic factors (e.g., latitude, elevation and continental hemisphere) influence the removal of food items (i.e., seeds and dead arthropods) by Pogonomyrmex species. Location South and North America, from Patagonia to the Rocky Mountains. Taxon Genus Pogonomyrmex (Formicidae: Hymenoptera). Methods Conducting standardised experiments, we performed a seed removal experiment and an assessment of the items retrieved by ant workers of 160 nests from eight Pogonomyrmex spp. at 16 sites extending the American continent. Results Pogonomyrmex ants native to North America removed more seeds than their South American counterpart. In general, results align with optimal foraging theory, indicating a higher probability of seed removal near ant nests. High climate stability correlated with lower seed predation rates, emphasising seed consumption's significance in historically arid environments. Increased precipitation and temperature led to reduced removal of food resources, suggesting reduced water availability and lower mean temperatures increases the consumption of seeds by harvester ants. Conclusions Overall, Pogonomyrmex ants' food resource use is influenced by a combination of factors such as region, distance from the nest and climate. This study underscores harvester ants' potential impact on plant distribution over large spatial scales consuming seeds from the immediate proximity of their nest and preventing establishment.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

First account of vivipary, including physical and chemical attributes, in fruits of Cereus hildmannianus K. Schum. (Cactaceae) - Everaldo dos Santos; Gilberto Codignole Luz; Claudete Aparecida Mangolin; Maria de Fátima Pires da Silva Machado; Jorge Hugo Cota-Sánchez (Brazilian Journal of Botany, 2024)

No-take zone in check: An ecological assessment of the management role in reef fish conservation in a Brazilian Hope Spot region - Augusto A. Machado; Aline A. Aguiar; Maria L. Abieri; Bruno P. Masi; Mauricio Hostim-Silva; Áthila A. Bertoncini (Ocean & Coastal Management, 2024)

Health benefits of acerola (Malpighia spp) and its by-products: A comprehensive review of nutrient-rich composition, pharmacological potential, and industrial applications - Lucas Fornari Laurindo; Larissa Naomi Takeda; Nathalia Mendes Machado; Alda Maria Machado Bueno Otoboni; Ricardo de Alvares Goulart; Vitor Cavallari Strozze Catharin; Luís R. Silva; Sandra Maria Barbalho; Rosa Direito (Food Bioscience, 2024)

COVID-19, Anxiety, and Body Mass Index Increase Leptin Levels: a Cross-sectional Multicentric Study - Gislaine Z. Réus; Kelen C. C. Recco; Karynne M. S. H. Machado; Ritele H. Silva; Camila O. Arent; Graziela Amboni; Flávia S. Niero; Lucas C. Pedro; Laura A. Borba; Margarete D. Bagatini; Gabriela G. de Oliveira; Alana Patrícia da Silva; et al. (Molecular Neurobiology, 2024)

Prospecting for New Potential Biocontrol Agents Against Colletotrichum lindemuthianum, the Causal Agent of Bean Anthracnose - Rosilene C. Matos; Sibele A. da Silva; Isabella F. Cordeiro; Angélica B. Sanchez; Maria R. A. Damasceno; Lorrana C. M. Rocha; Gustavo S. Kajitani; Josino José Barbosa; Marisa V. de Queiroz; Camila Carrião Machado Garcia; Leandro M. Moreira (Journal of Soil Science and Plant Nutrition, 2024)

Gallic acid attenuates lipopolysaccharide - induced memory deficits, neurochemical changes, and peripheral alterations in purinergic signaling - Vânia Machado Recart; Luiza Spohr; Mayara Sandrielly Soares de Aguiar; Anita Avila de Souza; Kelen Cristiane Machado Goularte; Natália Pontes Bona; Nathalia Stark Pedra; Fernanda Cardoso Teixeira; Francieli Moro Stefanello; Roselia Maria Spanevello (Metabolic Brain Disease, 2024)

Mechanisms of action of coffee bioactive compounds – a key to unveil the coffee paradox - Fernanda Machado; Manuel A. Coimbra; Maria Dolores del Castillo; Filipe Coreta-Gomes (Critical Reviews in Food Science and Nutrition, 2024)

Plastic pollution on beaches in an Antillean manatee conservation area, Brazil - Mário Herculano de Oliveira; Maria Eduarda Santana Verissimo; Breno Carvalho da Silva; André Luiz Machado Pessanha (Marine Pollution Bulletin, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Single and combined applications of dopamine and 24-epibrassinolide in soybean seedlings under water deficiency: tolerance mechanisms essential to inhibit deleterious effects - Caio Victor Silva Pontes; Lohana Ribeiro Prestes; Antonio Ferreira Vieira Neto; Layse Kristine Corrêa Lopes; Maria Antonia Machado Barbosa; Allan Klynger da Silva Lobato (Plant Biosystems, 2024)

The effect of flunixin meglumine on the premature regression of corpus luteum, recovery rate, and embryo production in superovulated Dorper ewes - Ana Lucia Rosa e Silva Maia; Lucas Machado Figueira; Marcela Sene Rocha; Jasmine Bantim de Souza Pinheiro; Thais de Almeida Oliveira; Felipe Zandonadi Brandão; Jeferson Ferreira Fonseca; Maria Emilia Franco Oliveira; Claudio Alvarenga de Oliveira; Joanna Maria Gonçalves Souza-Fabjan (Animal Reproduction Science, 2024)

Diaporthe ueckeri causing cassava root rot in Pernambuco, Brazil - Jenifer Sthephanie Araujo da Silva; Vitória Cristina Santiago Alves; Sílvio Francisco da Silva; Renan do Nascimento Barbosa; Carlos Alberto Fragoso de Souza; Diogo Paes da Costa; Alexandre Reis Machado; Erika Valente de Medeiros; Cristina Maria de Souza-Motta (Crop Protection, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Paleoenvironment assessment of Irati Formation (Paraná Basin, Brazil) based on the semi-quantification of organic sulfur markers by FTICR-MS - Lua Morena Leoncio de Oliveira; José Roberto Cerqueira; Karina Santos Garcia; Antonio Fernando Queiroz; Helio Jorge Portugal Severiano Ribeiro; Thomas B.P. Oldenburg; Maria Elisabete Machado (Marine and Petroleum Geology, 2024)

Aboveground and soil carbon, nitrogen, and phosphorus concentrations and stocks and their responses to environmental and human-related drivers in a tropical dry forest - Alice Batista dos Santos; Ana Cristiana Silva; Maria Fabíola Barros; Renato Soares Vanderlei; Marcelo Tabarelli; Silvia Rafaela Machado Lins (Journal of Arid Environments, 2024)

The role of culture in the representation of probiotic foods - Michele Christine Machado-Oliveira; Heber Rodrigues; Antonio Bisconsin-Junior; Gustavo H.T.A. Camillo; Héctor Sierra; Oluwadara Alegbeleye; Carlos Gomez-Corona; Dusanka Micetic-Turk; Luz Maria Paucar-Menacho; Alexandra A.I.A. Chincha; Andrea Gomez-Zavaglia; Mara Virginia Galmarini; et al. (Food Research International, 2024)

Comprehensive analysis of the phytochemical composition and antitumoral activity of an olive pomace extract obtained by mechanical pressing - Diana Melo Ferreira; Juliana Barreto-Peixoto; Nelson Andrade; Susana Machado; Cláudia Silva; Joana C. Lobo; Maria A. Nunes; Gerardo Álvarez-Rivera; Elena Ibáñez; Alejandro Cifuentes; Fátima Martel; M. Beatriz P.P. Oliveira; et al. (Food Bioscience, 2024)

Bioactive jambu extract (Acmella ciliata) as source of spilanthol for the development of a functional vegetable gelatin - Tatiana Maria de Freitas Gomes Lima; Larissa Morais Ribeiro da Silva; Paulo Henrique Machado de Sousa; Francisco Ernani Magalhaes; Nágila Maria Pontes Silva Ricardo; Icaro Gusmao Pinto Vieira; Luiz Bruno de Sousa Sabino; Raimundo Wilane de Figueiredo (Food Bioscience, 2024)

Life cycle assessment of bioethanol production from banana, potato, and papaya waste - Victória Dutra Fagundes; Ênio Leandro Machado; Rosana de Cássia de Souza Schneider; Luciane Maria Colla (The International Journal of Life Cycle Assessment, 2024)

Insights of potential trypanocidal effect of the synthetic derivative (2E)-1-(4-aminophenyl)-3-(2,4-dichlorophenyl)prop-2-en-1-one: in vitro assay, MEV analysis, quantum study, molecular docking, molecular dynamics, MPO analysis, and predictive ADMET - Márcia Machado Marinho; Matheus Nunes da Rocha; Emanuel Paula Magalhães; Lyanna Rodrigues Ribeiro; Caio Henrique Alexandre Roberto; Francisco Wagner de Queiroz Almeida-Neto; Marília Lopes Monteiro; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Emmanuel Silva Marinho; Pedro de Lima Neto; Alice Maria Costa Martins; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Ticks infesting terrestrial small mammals in a rural settlement in the Amazonas state, Brazil - Juliana Machado Portela; Alessandra Ferreira Dales Nava; Helder Ribeiro Batista; Thiago F. Martins; Sebastian Muñoz-Leal; Maria Nazareth Ferreira da Silva; Salatiel Ribeiro Dias; Marcelo B. Labruna; Antonio Humberto Hamad Minervino (Experimental and Applied Acarology, 2024)

Soil organic carbon stock and litter mass in silvopastoral systems with Eucalyptus - Alan Figueiredo de Oliveira; Claudinei Alves dos Santos; Lúcio Carlos Gonçalves; Maria Celuta Machado Viana; Miguel Marques Gontijo Neto; Edilane Aparecida da Silva; Ângela Maria Quintão Lana (Agroforestry Systems, 2024)

Transcervical uterine flushing and embryo transfer in sheep: Morphophysiological basis for approaches currently used, major challenges, potential improvements, and new directions (alas, including some old ideas) - Joedson Dantas Gonçalves; Jenniffer Hauschildt Dias; Mariana Machado-Neves; Gabriel Brun Vergani; Bahareh Ahmadi; Ribrio Ivan Tavares Pereira Batista; Joanna Maria Gonçalves Souza-Fabjan; Maria Emilia Franco Oliveira; Pawel Mieczyslaw Bartlewski; Jeferson Ferreira da Fonseca (Reproductive Biology, 2024)

Molecular markers that make energy cane differ from sugarcane cultivars (Saccharum spp.) - Mariana Mancini Benez; Rone Charles Maranho; Hugo Zeni Neto; Claudete Aparecida Mangolin; Joseli Cristina Silva; Maria de Fátima Pires da Silva Machado (Plant Gene, 2024)

Use of nitrogen markers to assess source rock paleodepositional environment of the Candeias (Recôncavo Basin) and Barreirinha (Amazonas Basin) formations - Diego Nery do Amaral; Flávia Lima e Cima Miranda; Luise Carvalho Dias; José Roberto Cerqueira; Hélio Jorge Severiano Ribeiro; Olívia Maria Cordeiro de Oliveira; Antônio Fernando de Souza Queiroz; Maria Elisabete Machado; Sérgio Luís Costa Ferreira (Marine and Petroleum Geology, 2024)

Microplastic atmospheric pollution in an urban Southern Brazil region: What can spider webs tell us? - Mercia Barcellos da Costa; João Marcos Schuab; Cristina Maria dos Santos Sad; Enrique Ronald Yapuchura Ocaris; Mariana Beatriz Paz Otegui; Daniel Gosser Motta; Karina Machado Menezes; Felipe Barcellos Caniçali; Antônio Augusto Lopes Marins; Gustavo Zambon Dalbó; Mateus Marçal; Bruno Fioresi Paqueli; et al. (Journal of Hazardous Materials, 2024)

Inferring population trends of Syagrus coronata (Arecaceae) in areas under different management in Brazilian Caatinga using a transition matrix model - Bianca Santana Dias Nascimento; Jhonathan de Oliveira Silva; Uriel de Jesus Araújo Pinto; Daniel Cavalcante Bispo; Priscyla Maria Silva Rodrigues; Ernani Machado de Freitas Lins-Neto (Journal for Nature Conservation, 2024)

DNA lesions that block transcription induce the death of Trypanosoma cruzi via ATR activation, which is dependent on the presence of R-loops - Isabela Cecilia Mendes; Willian dos Reis Bertoldo; Adalberto Sales Miranda-Junior; Antônio Vinícius de Assis; Bruno Marçal Repolês; Wesley Roger Rodrigues Ferreira; Daniela Ferreira Chame; Daniela De Laet Souza; Raphael Souza Pavani; Andrea Mara Macedo; Glória Regina Franco; Esteban Serra; et al. (DNA Repair, 2024)

Preliminary profile of the gut microbiota from amerindians in the Brazilian amazon experiencing a process of transition to urbanization - Rodrigo M. Alencar; José G. Martínez; Valéria N. Machado; Juan F. Alzate; Cinthya P. Ortiz-Ojeda; Rosiane R. Matias; Denise C. Benzaquem; Maria C.F. Santos; Enedina N. Assunção; Evelyn C. Lira; Spartaco Astolfi-Filho; Tomas Hrbek; et al. (Brazilian Journal of Microbiology, 2024)
The Yanomami are one of the oldest indigenous tribes in the Amazon and are direct descendants of the first people to colonize South America 12,000 years ago. They are located on the border between Venezuela and Brazil, with the Venezuelan side remaining uncontacted. While they maintain a hunter-gatherer society, they are currently experiencing contact with urbanized populations in Brazil. The human gut microbiota of traditional communities has become the subject of recent studies due to the Westernization of their diet and the introduction of antibiotics and other chemicals, which have affected microbial diversity in indigenous populations, thereby threatening their existence. In this study, we preliminarily characterized the diversity of the gut microbiota of the Yanomami, a hunter-gatherer society from the Amazon, experiencing contact with urbanized populations. Similarly, we compared their diversity with the population in Manaus, Amazonas. A metabarcoding approach of the 16 S rRNA gene was carried out on fecal samples. Differences were found between the two populations, particularly regarding the abundance of genera (e.g., Prevotella and Bacteroides ) and the higher values of the phyla Bacteroidetes over Firmicutes, which were significant only in the Yanomami. Some bacteria were found exclusively in the Yanomami ( Treponema and Succinivibrio ). However, diversity was statistically equal between them. In conclusion, the composition of the Yanomami gut microbiota still maintains the profile characteristic of a community with a traditional lifestyle. However, our results suggest an underlying Westernization process of the Yanomami microbiota when compared with that of Manaus, which must be carefully monitored by authorities, as the loss of diversity can be a sign of growing danger to the health of the Yanomami.

Detection of Mycoplasma spp. in free-living seabirds - Samara Gomes de Brito; Thomas Salles Dias; Leandro dos Santos Machado; Jenif Braga de Souza; Nathalie Costa da Cunha; Virginia Léo de Almeida Pereira; Maria Lúcia Barreto; Aloysio de Mello Figueiredo Cerqueira; Felipe Piedade Gonçalves Neves (Brazilian Journal of Microbiology, 2024)

Impact of different fermentation times on the microbiological, chemical, and sensorial profile of coffees processed by self-induced anaerobiosis fermentation - Juliana Maria Campos Palumbo; Pâmela Mynsen Machado Martins; Luís Gustavo Amaral Salvio; Nádia Nara Batista; Luciana Silva Ribeiro; Flávio Meira Borém; Disney Ribeiro Dias; Rosane Freitas Schwan (Brazilian Journal of Microbiology, 2024)

Pressurized liquid extraction as an innovative high-yield greener technique for phenolic compounds recovery from grape pomace - Tatiane de O.X. Machado; Isabella Portugal; Helena de A.C. Kodel; Alireza Fathi; Faezeh Fathi; Maria Beatriz P.P. Oliveira; Cláudio Dariva; Eliana B. Souto (Sustainable Chemistry and Pharmacy, 2024)

Acacia mearnsii pyroligneous acid as a promoter of rooting and quality of rooted cuttings of subtropical Eucalyptus - Adriana Maria Griebeler; Maristela Machado Araujo; Felipe Turchetto; Ezequiel Gasparin; Claudia Costella; Berta Maria Heinzmann; Bibiana Fontana Batista; Fábio André da Encarnação; Osmarino Pires dos Santos; Nathália Pimentel; Júlia Luiza Stahl (Trees, 2024)

Liquid-liquid and solid-liquid extractions with low-temperature partitioning – A review - Adilson Correia Goulart; Alessandra Aparecida Zinato Rodrigues; Fernanda Fernandes Heleno; Anizio Marcio de Faria; Simone Machado Goulart; Maria Eliana Lopes Ribeiro de Queiroz (Analytica Chimica Acta, 2024)

Effects of two external cooling strategies on physiological and perceptual responses of athletes with tetraplegia during and after exercise in the heat - Ingrid Ludimila Bastos Lôbo; Samuel Penna Wanner; Renato de Carvalho Guerreiro; Bruno Lourenço Pinto Coelho; Felipe Emanuel dos Santos Coimbra; Maria Eduarda Machado Martins; Larissa Cristina de Abreu Duarte; Eduardo Stieler; Marco Túlio de Mello; Andressa Silva (Journal of Thermal Biology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

The impact of different levels of functional oil supplementation in combination with salinomycin on growth performance and intestinal microbiota of broilers undergoing Eimeria challenge: An analysis of dynamics - Thaís Bastos Stefanello; Kátia Maria Cardinal; Catiane Orso; Carolina Haubert Franceschi; Jéssica Pereira Silva; Micheli Bertoni Mann; Jeverzon Frazzon; Priscila Oliveira Moraes; Andréa Machado Leal Ribeiro (Research in Veterinary Science, 2024)

Comparative study of ultrasound application versus mechanical agitation on pork belly brining for bacon production - Marcio Augusto Ribeiro-Sanches; Maria Júlia Neves Martins; André Luiz Borges-Machado; Micael José de Almeida; Bruna Grassetti Fonseca; Tiago Carregari Polachini; Javier Telis-Romero (Meat Science, 2024)

Wastewater-grown microalgae biomass as a source of sustainable aviation fuel: Life cycle assessment comparing hydrothermal routes - Bianca Barros Marangon; Jackeline de Siqueira Castro; Paula Peixoto Assemany; Nádia Almeida Machado; Maria Lúcia Calijuri (Journal of Environmental Management, 2024)

Desorption properties of taioba (Xanthosoma taioba E.G. Gonç.) leaves: A non-conventional edible plant - André Luiz Borges-Machado; Maria Júlia Neves-Martins; Marcio Augusto Ribeiro-Sanches; Ligia Sarneiro Pereira; Priscila Alonso dos Santos; Javier Telis-Romero (Food Bioscience, 2024)

Functional pâté elaborated with tambica (Oligosarcus robustus) and viola (Loricariichythys anus): Oxidative stability, microbiological and sensory quality - Patrícia Radatz Thiel; Khadija Bezerra Massaut; Daiane Machado Souza; Andreza de Brito Leal; Igor Henrique de Lima Costa; Helen Cristina dos Santos Hackbart; Márcia Arocha Gularte; Claudio Eduardo dos Santos Cruxen; Wladimir Padilha da Silva; Ângela Maria Fiorentini (Biocatalysis and Agricultural Biotechnology, 2024)

Exogenous Serotonin and 24-Epibrassinolide Boost Root Protection and Suppress Oxidative Damages Occasioned by Severe Water Deficit in Soybean Seedlings - Caio Victor Silva Pontes; Aline Hipólito Assunção dos Santos; Layse Kristine Corrêa Lopes; Maria Antonia Machado Barbosa; Andrzej Bajguz; Allan Klynger da Silva Lobato (Journal of Plant Growth Regulation, 2024)

A single dose of angiotensin-(1–7) resolves eosinophilic inflammation and protects the lungs from a secondary inflammatory challenge - Giselle Santos Magalhaes; Juliana Fabiana Gregorio; Vinicius Amorim Beltrami; Franciel Batista Felix; Livia Oliveira-Campos; Caio Santos Bonilha; Renato Fraga Righetti; Iolanda de Fátima Lopes Calvo Tibério; Frederico B. De Sousa; Barbara Maximino Rezende; Andréa Teixeira-Carvalho; Robson AS Santos; et al. (Inflammation Research, 2024)

Recent past connections between Amazonian and Atlantic forests by comparative phylogeography and paleodistribution models for didelphid mammals - Arielli Fabrício Machado; Maria Nazareth Ferreira Da Silva; Izeni Pires Farias; Marina Anciães; Mario Silva Nunes; Willian Thomaz Peçanha; Camila Duarte Ritter; Josué Anderson Rêgo Azevedo; Cleuton Lima Miranda; Leandro Duarte (Evolutionary Ecology, 2024)

Commonness as a reliable surrogacy strategy for the conservation planning of rare tree species in the subtropical Atlantic Forest - Guilherme Salgado Grittz; Giesta Maria Olmedo Machado; Alexander Christian Vibrans; André Luís de Gasper (Biodiversity and Conservation, 2024)

Clinical biomarker-based biological age predicts deaths in Brazilian adults: the ELSA-Brasil study - Amanda Viana Machado; Juliana Freitas de Mello e Silva; Enrico Antônio Colosimo; Belinda L. Needham; Chams Bicalho Maluf; Luana Giatti; Lidyane V. Camelo; Sandhi Maria Barreto (GeroScience, 2024)

Nematode community structure in sugarcane fields under continuous vinasse fertigation - Natalia de Jesus Ferreira Costa; Elvira Maria Regis Pedrosa; Thais Fernanda da Silva Vicente; Andressa Cristina Zamboni Machado; Lilian Margarete Paes Guimarães (Pedobiologia, 2024)

Characterization of dual-species biofilms formed by bacteria isolated from milk - Dara Elizabeth Barbosa Rodrigues; Luciano Guimarães; Solimar Gonçalves Machado; Maria Cristina Dantas Vanetti (International Dairy Journal, 2024)

Araticum (Annona crassiflora Mart.): A critical review for the food industry - Rafael Fernandes Almeida; Isabela Ferreira Moreno; Ana Paula Oliveira Machado; Maria Angela A. Meireles; Lilian Karla Figueira da Silva; Eduardo Augusto Caldas Batista (Food Research International, 2024)

Influence of mini-tunnel and different rooting environments on the production of rooted mini-cuttings of subtropical Eucalyptus - Adriana Maria Griebeler; Maristela Machado Araujo; Felipe Turchetto; Claudia Costella; Ezequiel Gasparin; Álvaro Luis Pasquetti Berghetti; Marllos Santos de Lima; Nathália Pimentel; Osmarino Pires dos Santos (New Forests, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Assessment of anthropogenic pollution in Guanabara Bay (SE Brazil) through biogeochemical data and stable isotope mixing models - Thaise Machado Senez-Mello; Maria Virgínia Alves Martins; Paulo Alves de Lima Ferreira; Rubens Figueira; Wellen Fernanda Louzada Castelo; Fabrício Leandro Damasceno; Johann Hohenegger; Egberto Pereira; Wânia Duleba; Mauro Cesar Gerardes (Environmental Science and Pollution Research, 2024)

Benthic foraminifera as bioindicators in an area influenced by a submarine outfall, North Coast of Bahia, Brazil - André Ramos Costa; Zelinda Margarida Andrade Nery Leão; Altair de Jesus Machado; José Maria Landim Dominguez; Gabriela Santiago Mercês Pereira; Marlene Campos Peso Aguiar; Simone Souza de Moraes (Regional Studies in Marine Science, 2024)

Exploring the genetic origin of Brazilian locally adapted breeds: Admixture, population history and relationship with Portuguese and indicine cattle - Lucas Lima Verardo; Pamela Itajara Otto; Marco Antonio Machado; João Cláudio do Carmo Panetto; Daniele Ribeiro de Lima Reis Faza; Andréa Alves do Egito; Andreia Sofia Martins Vitorino; Maria Inês Carvalho Martins Carolino; Nuno Pimentel Carolino; Marcos Vinicius Gualberto Barbosa da Silva (Livestock Science, 2024)

Ant habitat-use guilds response to forest-pasture shifting in the southwestern Amazon - Dhâmyla Bruna de Souza Dutra; Rodrigo Machado Feitosa; Tainara Thais Jory; Francisco Matheus da Silva Sales; Luane Karoline Fontenele; Marília Maria Silva da Costa; Fernando Augusto Schmidt (Journal of Insect Conservation, 2024)

Stress memory in crops: what we have learned so far - Maria D. Pissolato; Tamires S. Martins; Yutcelia C. G. Fajardo; Gustavo M. Souza; Eduardo C. Machado; Rafael V. Ribeiro (Theoretical and Experimental Plant Physiology, 2024)

Distribution of acid-volatile sulfides and simultaneously extracted metals in Guanabara Bay: combination of anthropogenic, sedimentological, and geochemical processes - Renato Campello Cordeiro; Ricardo Erthal Santelli; Wilson Thadeu Valle Machado; Abilio Soares Gomes; Luciane Silva Moreira; Rafael Lopes Oliveira; Ilene Matano Abreu; Maria de Fatima Guadalupe Meniconi (Environmental Science and Pollution Research, 2024)

Mining-free territories and decolonial theory: Evaluating the synergies in the Brazilian context - Rodrigo Machado Vilani; Bruno Milanez; Márcia Barbosa Martins; Maria Amália Silva Alves de Oliveira; Carlos José Saldanha Machado; Marília Luisa de Oliveira (The Extractive Industries and Society, 2024)

Occurrence of Sanionia uncinata sporophytes on King George island, Antarctica: Exploring possible links to climate change - Maria Victória Magalhães de Vargas; Sara Navarrete Bohi Goulart; Guilherme Afonso Kessler de Andrade; Rafael Plá Matielo Lemos; Margéli Pereira de Albuquerque; Lorena Ferreira Peixoto; Ana Laura Pereira Lourenço; Mariana Pulrolnik Parrillo de Oliveira; Stephan Machado Dohms; Dafne Adriana Abreu dos Anjos; Marcelo Henrique Soller Ramada; Filipe de Carvalho Victoria (Polar Science, 2024)

Effects of decreasing roughage NDF in diets with high inclusion of DDGS on performance, feeding behavior, and ruminal parameters in Nellore bulls - Gabriel Namor Issa David; Alana Maria Menezes Di Calaça; Natalia de Almeida Leite; Taniela de Souza Conrado; Izadora Mazagão Veloso; Alessandro Rodrigues Costa Filho; Felipe de Souza Galvão; Yasmin Machado Barreto; Luan de Oliveira Moura Silva; Victor Rezende Moreira Couto; Juliano José de Resende Fernandes (Livestock Science, 2024)

Groundwater Contamination in a Rural Municipality of Northeastern Brazil: Application of Geostatistics, Geoprocessing, and Geochemistry Techniques - Raiany Sandhy Souza Santos; Milton Santos Cardoso Filho; Isadora Machado Marques; Anderson Gomes de Oliveira; Olívia Maria Cordeiro de Oliveira; Ícaro Thiago Andrade Moreira (Water, Air, & Soil Pollution, 2024)

Genomic characterization of a highly divergent tomato chlorotic mottle Guyane virus strain in the Brazilian Amazon River Basin - Izaías Araújo de Oliveira; Luciane de Nazaré Almeida dos Reis; Flávia Milene Barros Nery; Niday Alline Nunes Fernandes; Vinícius Peres Machado Reis Gonçalves; Maria R. Rojas; Robert L. Gilbertson; Ailton Reis; Leonardo Silva Boiteux; Maria Esther de Noronha Fonseca-Boiteux; Rita de Cássia Pereira-Carvalho (Phytoparasitica, 2024)

Production and characterization of protein-rich extracts from the red macroalga Gelidium corneum and its industrial agar extraction residues - Marília Mateus; Rita Mão de Ferro; Helena M. Pinheiro; Remígio Machado; M. Manuela R. da Fonseca; Maria Sapatinha; Carla Pires; Isa Marmelo; António Marques; Maria Leonor Nunes; Carla Motta; M. Teresa Cesário (Algal Research, 2024)

Potential of microbial control agents in a strategy against Duponchelia fovealis Zeller (Lepidoptera: Crambidae) - Thaísa Siqueira Da Luz; Carolina Gracia Poitevin; Rubens Candido Zimmermann; Jason Lee Furuie; Edson José Mazarotto; Maria Aparecida Cassilha Zawadneak; Joatan Machado da Rosa; Carlos Eduardo Nogueira Martins; Ida Chapaval Pimentel (Crop Protection, 2024)

Three snake venoms from Bothrops genus induced apoptosis and cell cycle arrest in K562 human leukemic cell line - Aline D. Marinho; Emerson Lucena da Silva; Adrhyann Jullyanne de Sousa Portilho; Laís Lacerda Brasil de Oliveira; Emanuel Cintra Austregésilo Bezerra; Beatriz Maria Dias Nogueira; Moema Leitão-Araújo; Maria Lúcia Machado-Alves; Carlos Correa Neto; Rui Seabra Ferreira; Caroline de Fátima Aquino Moreira-Nunes; Maria Elisabete Amaral de Moraes; et al. (Toxicon, 2024)

Exploring the agricultural potential of AgNPs/PlyB221 endolysin bioconjugates as enhanced biocontrol agents - Fernanda Coelho; Angelica Maria Mazuera Zapata; Thales Rafael Machado; Fernanda Canduri; Valtencir Zucolotto (Biocatalysis and Agricultural Biotechnology, 2024)

Tree growth performance and xylem functional arrangements of Macrolobium Schreb. (Fabaceae) in different wetland forests in the Central Amazon basin - Yanka Laryssa Almeida Alves; Flavia Machado Durgante; Maria Teresa Fernandez Piedade; Florian Wittmann; Jochen Schӧngart (Trees, 2024)

Large diameters and tree bark physical attributes drive vascular epiphyte-phorophyte relationships in Amazonian black-water floodplain forest - Jeisiane Santos da Silva; Maria Teresa Fernandez Piedade; Viviane Pagnussat Klein; Flávia Machado Durgante; Florian Wittmann; Adriano Costa Quaresma (Plant Ecology, 2024)

New reports of Gilbertella persicaria causing post-harvest rot in different fruits in Brazil - Ana Elisa de Almeida Souza; André Luiz Cabral Monteiro de Azevedo Santiago; Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; José Vitorino da Silva Neto; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Diseases and Protection, 2024)

An opportunity for acerola pulp (Malpighia emarginata DC) valorization evaluating its performance during the block cryoconcentration by physicochemical, bioactive compounds, HPLC–ESI-MS/MS, and multi-elemental profile analysis - Karine Marafon; Marina Pereira-Coelho; Isabel Cristina da Silva Haas; Bruna Rafaela da Silva Monteiro Wanderley; Jefferson Santos de Gois; Luciano Vitali; Aderval S. Luna; Maria Helena Machado Canella; Eduard Hernández; Renata Dias de Mello Castanho Amboni; Elane Schwinden Prudencio (Food Research International, 2024)

Detection of Trichomonas vaginalis by Allplex™ STI Essential Assay (Seegene) in clinical samples from the Brazilian public health system users - Mariana Dicki Freitas; Fernanda Gomes Cardoso; Graziela Vargas Rigo; Hanalydia de Melo Machado; Maria Luiza Bazzo; Tiana Tasca (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Xylitol Production by Candida tropicalis from Sugarcane Bagasse and Straw: an Adaptive Approach to Improve Fermentative Performance - Italo de Andrade Bianchini; Fanny Machado Jofre; Talita Martins Lacerda; Maria das Graças de Almeida Felipe (BioEnergy Research, 2023)

Blue carbon stock heterogeneity in Brazilian mangrove forests: A systematic review - Natalia Beloto; Luiz C. Cotovicz Jr.; José Vítor Machado Rodrigues; Maria Regina Gmach; Martin Zimmer; Véronique Helfer; Marcelo O. Soares; Luis Ernesto Arruda Bezerra (Marine Pollution Bulletin, 2023)

Arbuscular mycorrhizal fungi can reduce severity of fusariosis (Fusarium oxysporum) in cowpea plants (Vigna unguiculata (L.) Walp.) - Wanderson Lima Cunha; Maria Rita da Silva Andrade Leonel; Ana Paula Brito de Sousa; Mickaelle Alves de Sousa Lima; Adrielle de Jesus Machado Santos; Gildean Macedo do Nascimento; Gerbeli de Mattos Salgado Mochel; Sylvia Leticia Oliveira Silva; Camila Pinheiro Nobre; Antonia Alice Costa Rodrigues; Ivaneide de Oliveira Nascimento (Rhizosphere, 2023)

Late Pleistocene–Holocene multi-decadal patterns of extreme floods in NW Iberia: The Duero River palaeoflood record - Gerardo Benito; Noam Greenbaum; Alicia Medialdea; Mikel Calle; Yolanda Sanchez-Moya; Maria Machado; Juan Antonio Ballesteros-Cánovas; Juan Pablo Corella (Quaternary Science Reviews, 2023)

Resistance physical exercise alleviates lipopolysaccharide-triggered neuroinflammation in cortex and hippocampus of rats via purinergic signaling - Vanessa Valéria Miron; Charles Elias Assmann; Vitor Bastianello Mostardeiro; Nathieli Bianchin Bottari; Jucimara Baldissarelli; Karine Paula Reichert; Aniélen Dutra da Silva; Milagros Fanny Vera Castro; Loren Borba de Jesus; Marcylene Vieira da Silveira; Tais Vidal Palma; Vera Maria Morsch; et al. (NeuroToxicology, 2023)

Enhanced root growth and nitric oxide content in ‘Mandarin’ lime under drought stress: experimental evidence - Neidiquele M. Silveira; Maria Isabel M. de Oliveira; Simone F. da Silva; Marcela T. Miranda; Matheus P. Passos; Eduardo C. Machado; Rafael V. Ribeiro (Brazilian Journal of Botany, 2023)

Exploring Autonomous and Remotely Operated Vehicles in Offshore Structure Inspections - Maricruz Fun Sang Cepeda; Marcos de Souza Freitas Machado; Fabrício Hudson Sousa Barbosa; Douglas Santana Souza Moreira; Maria José Legaz Almansa; Marcelo Igor Lourenço de Souza; Jean-David Caprace (Journal of Marine Science and Engineering, 2023)
Operators of offshore production units (OPUs) employ risk-based assessment (RBA) techniques in order to minimise inspection expenses while maintaining risks at an acceptable level. However, when human divers and workers are involved in inspections conducted at high heights, the operational risks can be significant. Recently, there has been a growing trend towards the use of unmanned aerial vehicles (UAVs), autonomous surface vehicles (ASVs), remotely operated vehicles (ROVs), and autonomous underwater vehicles (AUVs) for inspections of offshore structures as a means to reduce exposure to human risk. This article provides an analysis of these vehicle inspection capabilities and their potential to enhance robustness and safety within the oil and gas industry. The review assesses both the advantages and the drawbacks associated with these innovative systems, providing valuable comparisons and assessments on their potential use as viable alternatives to conventional inspection methods.

Effects of Annona squamosa leaf extract on the insects Aedes aegypti, Nasutitermes corniger, and Sitophilus zeamais and the microcrustacean Hyalella sp. - Lucas Gabriel Pita dos Santos; Cristiane Maria Varela de Araújo de Castro; Isabella Coimbra Vila Nova; Estefani Santana do Nascimento; Jéssica da Silva Nascimento; Wliana Alves Viturino da Silva; Janaína Carla Barbosa Machado; Daniela Maria do Amaral Ferraz Navarro; Magda Rhayanny Assunção Ferreira; Luiz Alberto Lira Soares; Patrícia Maria Guedes Paiva; Thiago Henrique Napoleão; et al. (South African Journal of Botany, 2023)

Chemical profile, in vitro bioactivities, and antinociceptive effect of Red Pitaya extracts on zebrafish - Chayane Gomes Marques; Maurício Fraga van Tilburg; Eric Petterson Viana Pereira; Sandra Machado Lira; Paulo Riceli Vasconcelos Ribeiro; Emanuela de Lima Rebouças; Marcelo Oliveira Holanda; Glauber Batista Moreira Santos; José Ytalo Gomes da Silva; Guilherme Julião Zocolo; Ana Paula Dionísio; Maria Izabel Florindo Guedes; et al. (South African Journal of Botany, 2023)

Quantification of polycyclic aromatic sulfur heterocycles in fine airborne urban particles (PM2.5) after multivariate optimization of a green procedure - Pedro Victor Bomfim Bahia; Madson Moreira Nascimento; Gisele Olimpio da Rocha; Jailson Bittencourt de Andrade; Maria Elisabete Machado (Science of The Total Environment, 2023)

Seroprevalence of Dermatophagoides farinae-specific IgE in dogs with atopic dermatitis in São Paulo, Brazil - Ana Paula Di Martino Frezza; Maria Lucia Gomes Lourenço; Júlia Meira; Toshihiro Tsukui; Miyuki Kageyama; Luiz Henrique de Araújo Machado (Research in Veterinary Science, 2023)

Anti-obesity potential of a yogurt functionalized with a CLNA-rich pomegranate oil - Manuela Machado; Sérgio Sousa; Luís M. Rodriguez-Alcalá; Ana Maria Gomes; Manuela Pintado (Food Research International, 2023)

Micromorphology of hesperidin crystals and ultrastructure of crystal-bearing cells in Metrodorea nigra, a neotropical Rutaceae species - Silvia Rodrigues Machado; Karla Bianca de Deus Bento; Shelly Favorito de Carvalho; Yve Canaveze; Tatiane Maria Rodrigues (Flora, 2023)

Phylogeny of Pseudoperonospora causing downy mildew of Cucurbitaceae in Brazil - Glícia Silva de Moraes; Juliana Ferreira de Mello; Amanda Cupertino de Queiroz Brito; Ailton Reis; Sami Jorge Michereff; André Angelo Medeiros Gomes; Marcos Paz Saraiva Câmara; Janiele Cássia Barbosa Vieira; Cristina Maria de Souza-Motta; Alexandre Reis Machado (European Journal of Plant Pathology, 2023)

Nutrient cycling aspects as possible ecosystem functional indicators of successional stage in Semideciduous seasonal forest, Rio de Janeiro state, Brazil - Rodrigo Camara de Souza; Marcos Gervasio Pereira; Deivid Lopes Machado; Luciano de Oliveira Toledo; Carlos Eduardo Gabriel Menezes; Gilsonley Lopes dos Santos; Fernando Silva Coutinho; Roni Fernandes Guareschi; Victória Maria Monteiro Mendonça (Acta Oecologica, 2023)

Different life cycle assessment methods and causes of variation in estimates of global warming in chicken and pork production systems: A critical systematic review - Jéssica Pereira Silva; Carlo Juliantro Giehl; Kátia Maria Cardinal; Ines Andretta; Andréa Machado Leal Ribeiro (Livestock Science, 2023)

Paleoenvironmental characterization of the Ponta Grossa formation (Devonian) at the northwest border of the Paraná Basin, Brazil - Neiva Nascimento da Silva; Ilene Matanó Abreu; José Roberto Cerqueira; Diego Nery do Amaral; Karina Santos Garcia; Lauro T.S. Santos; Olívia M.C. Oliveira; Antônio Fernando de Souza Queiroz; Maria Elisabete Machado (Journal of South American Earth Sciences, 2023)

Correction: Phylogeny of Pseudoperonospora causing downy mildew of Cucurbitaceae in Brazil - Glícia Silva de Moraes; Juliana Ferreira de Mello; Amanda Cupertino de Queiroz Brito; Ailton Reis; Sami Jorge Michereff; André Angelo Medeiros Gomes; Marcos Paz Saraiva Câmara; Janiele Cássia Barbosa Vieira; Cristina Maria de Souza-Motta; Alexandre Reis Machado (European Journal of Plant Pathology, 2023)

Garlic: A systematic review of the effects on cardiovascular diseases - Vitor Massami Imaizumi; Lucas Fornari Laurindo; Barbara Manzan; Elen Landgraf Guiguer; Marie Oshiiwa; Alda Maria Machado Bueno Otoboni; Adriano Cressoni Araujo; Ricardo Jose Tofano; Sandra Maria Barbalho (Critical Reviews in Food Science and Nutrition, 2023)

Forecasting of secondary lead recovery from motorcycle batteries in Brazil: a contribution to waste management - Maria do Livramento Mamede Bezerra; Maisa Mendonça Silva; Simone Machado Santos (Environmental Science and Pollution Research, 2023)

Corrigendum to “Confirming sulfluramid (EtFOSA) application as a precursor of perfluorooctanesulfonic acid (PFOS) in Brazilian agricultural soils” [Chemosphere 325 (June 2023) 138370] - Yago Guida; Fabio Barbosa Machado Torres; Robson Rolland Monticelli Barizon; Marcia Regina Assalin; Maria Aparecida Rosa (Chemosphere, 2023)

Using Streptomyces spp. as plant growth promoters and biocontrol agents - Mateus Torres Nazari; Vera Analise Schommer; Julia Catiane Arenhart Braun; Lara Franco dos Santos; Samuel Teixeira Lopes; Viviane Simon; Bruna Strieder Machado; Valdecir Ferrari; Luciane Maria Colla; Jeferson Steffanello Piccin (Rhizosphere, 2023)

Spatio-temporal distribution of benthic fauna in mangrove areas in the Bay of Vitória estuary, Brazil - Gabriela Carvalho Zamprogno; Mônica Maria Pereira Tognella; Mercia Barcellos da Costa; Mariana Beatriz Paz Otegui; Karina Machado Menezes (Regional Studies in Marine Science, 2023)

Paleomagnetism of the Penatecaua magmatism: The CAMP intrusive rocks in the Amazonas Basin, northern Brazil - Giovanni Moreira; Marcia Ernesto; Angelo De Min; Andrea Marzoli; Fábio Braz Machado; Eleonora Maria Gouvea Vasconcellos; Giuliano Bellieni (Physics of the Earth and Planetary Interiors, 2023)

Functional lipid enriched probiotic cheese: Gastrointestinal stability and potential health benefits - Manuela Machado; Sérgio C. Sousa; Luís M. Rodríguez-Alcalá; Manuela Pintado; Ana Maria Gomes (International Dairy Journal, 2023)

Energy efficiency strategies for Brazilian social housing considering a life cycle perspective: Optimisation between thermal autonomy, energy consumption and costs - Maria Andrea Triana; Rayner Mauricio e Silva Machado; Artur Martins Kamimura; Matheus Körbes Bracht; Ana Paula Melo; Roberto Lamberts (Energy and Buildings, 2023)

Multi-scale characterization from the Hard Cap, Mupe Member, Lower Purbeck Limestone Group, Wessex Basin, Dorset, UK - Rafael Cremonini Baptista; Sérgio Bergamaschi; Marcus Vinicius Berao Ade; Alessandra Silveira Machado; Olga Maria Oliveira de Araújo; Ricardo Tadeu Lopes; Giovanni C. Stael (Journal of Sedimentary Environments, 2023)

Phylogenetic characterization and biodiversity of spore-forming bacteria isolated from Brazilian UHT milk - Isabella Maria Fernandes Botelho Moreira; Rafaela da Silva Rodrigues; Solimar Gonçalves Machado; Antônio Fernandes de Carvalho (Brazilian Journal of Microbiology, 2023)

Cytoprotective effect of Fridericia chica (Bonpl.) L.G. Lohmann extract associated with geranylgeraniol enriched-fraction from Bixa orellana L. on epithelial cells treated with bisphosphonate - Rogério José Machado Júnior; Júlia C. Camilli; Rosanna Tarkany Basting; Patrícia Maria Wiziacki Zago; Ilza Maria de Oliveira Sousa; Kaio Eduardo Buglio; Ana Lúcia T.G Ruiz; Paulo Roberto Nogueira Carvalho; João Ernesto de Carvalho; Sara T. O. Saad; Mary Ann Foglio (Natural Product Research, 2023)

Soy Lecithin Supplementation Promotes Growth and Increases Lipid Digestibility in GIFT Nile Tilapia Raised at Suboptimal Temperature - Rosana Oliveira Batista; Bianca Leticia Richter; Jorge Filipe Banze; Delano Dias Schleder; Maria Salhi; Renata Oselame Nobrega; Maria Fernanda Oliveira da Silva; Bruna Mattioni; James Eugene Pettigrew; Débora Machado Fracalossi (Fishes, 2023)
Soy lecithin (SL) is a source of phospholipids, which play a crucial role in determining cell membrane structure, fluidity, and functionality. This study investigated the effects of dietary SL on the performance, nutrient digestibility, and body composition of Nile tilapia juveniles (average initial weight 12.2 g) raised at 22 °C. The experimental diets contained increasing levels of SL (0.0, 21.0, 43.0, and 64.0 g kg−1). The best weight gain and feed efficiency occurred with 42.2 and 49.8 g kg−1 of SL inclusion, respectively, estimated through quadratic regression after 90 days of feeding. The body composition of the fish was also affected by feeding with SL, with a decrease in total body lipids and viscerosomatic and hepatosomatic indices but an increase in polyunsaturated fatty acids. A digestibility trial using only two diets (0SLD and 43SLD) revealed increased lipid and fatty acids digestibility in fish fed with 43SLD. In addition, the consumption of digestible nutrients was the highest in fish fed the diet 43SL. Therefore, SL supplementation is beneficial in fall/spring diets for Nile tilapia juveniles as it can improve growth, lipid digestibility, and body composition when supplemented within the range of 42 to 50 g kg−1 diet.

Rocky reef incursions: challenges faced by reef fishes in a Brazilian Hope Spot region - Augusto A. Machado; Bruno P. Masi; Aline A. Aguiar; Maria E.C. Ozorio; Caio N. Salles; Maurício Hostim-Silva; Áthila A. Bertoncini (Marine Pollution Bulletin, 2023)

Long-term e-cigarette aerosol exposure causes pulmonary emphysema in adult female and male mice - Andrea Jazel Rodriguez-Herrera; Ana Beatriz Farias de Souza; Thalles de Freitas Castro; Pedro Alves Machado-Junior; Elena Cecilia Marcano-Gomez; Tatiana Prata Menezes; Maria Laura da Cruz Castro; André Talvani; Daniela Caldeira Costa; Sílvia Dantas Cangussú; Frank Silva Bezerra (Regulatory Toxicology and Pharmacology, 2023)

Post-harvest sour rot in sweet potato is caused by Geotrichum candidum in Brazil - Juliana Ferreira de Mello; Amanda Cupertino de Queiroz Brito; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Diseases and Protection, 2023)

Effect of the addition of different concentrations of Solanum glaucophyllum desf. extract on chondrocyte cultures from the growth cartilage of newborn rats - Bruno Machado Bertassoli; Marília Martins Melo; Natália Melo Ocarino; Isabella Cristina Souza Félix; Fabiana Rocha Araújo; Amanda Maria Sena Reis; Endrigo Gabellini Leonel Alves; Eduardo Juan Gimeno; Adriana Raquel Massone; Rogéria Serakides (Toxicon, 2023)

Confirming sulfluramid (EtFOSA) application as a precursor of perfluorooctanesulfonic acid (PFOS) in Brazilian agricultural soils - Yago Guida; Fábio Barbosa Machado Torres; Robson Rolland Monticelli Barizon; Márcia Regina Assalin; Maria Aparecida Rosa (Chemosphere, 2023)

Corrigendum to “Freeze-dried jaboticaba (Myrciaria jaboticaba) peel powder, a rich source of anthocyanins and phenolic acids, mitigates inflammation-driven colorectal cancer in mice” [Food Biosci. 53 (2023) 102578] - Roberto de Paula do Nascimento; Julia Soto Rizzato; Gabriele Polezi; Amanda Maria Tomazini Munhoz Moya; Milena Ferreira Silva; Ana Paula da Fonseca Machado; Gilberto Carlos Franchi Junior; Renata Galhardo Borguini; Manuela Cristina Pessanha de Araújo Santiago; Ana Paula Ribeiro Paiotti; José Aires Pereira; Carlos Augusto Real Martinez; et al. (Food Bioscience, 2023)

Collagen peptide fractions from tilapia (Oreochromis aureus Steindachner, 1864) scales: Chemical characterization and biological activity - Karen Lilián Hernández-Ruiz; Jaime López-Cervantes; Dalia Isabel Sánchez-Machado; Olga Nydia Campas-Baypoli; Angie Araí Quintero-Guerrero; Maria de Lourdes Grijalva-Delgado; Andrés Francisco Chávez-Almanza (Food Bioscience, 2023)

Freeze-dried jaboticaba (Myrciaria jaboticaba) peel powder, a rich source of anthocyanins and phenolic acids, mitigates inflammation-driven colorectal cancer in mice - Roberto de Paula do Nascimento; Julia Soto Rizzato; Gabriele Polezi; Amanda Maria Tomazini Munhoz Moya; Milena Ferreira Silva; Ana Paula da Fonseca Machado; Gilberto Carlos Franchi Junior; Renata Galhardo Borguini; Manuela Cristina Pessanha de Araújo Santiago; Ana Paula Ribeiro Paiotti; José Aires Pereira; Carlos Augusto Real Martinez; et al. (Food Bioscience, 2023)

Impact of commercial formulations of herbicides alone and in mixtures on the antioxidant system and body condition parameters in tadpoles of Rhinella icterica (Spix 1824) - Leici Maria Machado Reichert; Diogo Reis de Oliveira; Jonas Londero Papaleo; Artur Antunes Navarro Valgas; Guendalina Turcato Oliveira (Environmental Toxicology and Pharmacology, 2023)

Effects of molasses supplementation on animal performance and carcass parameters of beef cattle: a meta-analysis - Rodrigo de Nazaré Santos Torres; João Pedro Amaral Bertoco; Maria Carolina Gonçalves de Arruda; Larissa de Melo Coelho; Josimari Regina Paschoaloto; Otavio Rodrigues Machado Neto; Jane Maria Bertocco Ezequiel; Marco Túlio Costa Almeida; Luis Artur Loyola Chardulo; Welder Angelo Baldassini (Tropical Animal Health and Production, 2023)

Richness of Nigrospora spp. (Apiosporaceae) in Manihot esculenta in Brazil and the description of three new species - Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; Ana Elisa de Almeida Souza; Sandy dos Santos Nascimento; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Mycological Progress, 2023)

Detection of Mycoplasma species at various anatomical sites of dogs from different types of kennels - Ana Beatriz Pinheiro Alves; Leandro dos Santos Machado; Jenif Braga de Souza; Gabriela Paixão Spenchutt Vieira; Thomas Salles Dias; Virgínia Léo de Almeida; Elmiro Rosendo do Nascimento; Maria Lúcia Barreto; Nathalie Costa Da Cunha (Brazilian Journal of Microbiology, 2023)

Candidemia in Brazilian neonatal intensive care units: risk factors, epidemiology, and antifungal resistance - Carolina Maria da Silva; Ana Maria Rabelo de Carvalho; Danielle Patrícia Cerqueira Macêdo; Moacir Batista Jucá; Rosemary de Jesus Machado Amorim; Rejane Pereira Neves (Brazilian Journal of Microbiology, 2023)

Species richness and similarity of the flora on four lajedos in Boa Nova, Bahia, Brazil - Morgana Maria Do Carmo Barbosa; Anderson Ferreira Pinto Machado; Andrea Karla Almeida Dos Santos; Raymundo José De Sá-Neto; Michele Martins Corrêa (Journal of Mountain Science, 2023)

A review of 121 years of studies on the freshwater zooplankton of Brazil - Maria Stela Maioli Castilho-Noll; Gilmar Perbiche-Neves; Natan Guilherme dos Santos; Leilane Talita Fatoreto Schwind; Fernando Miranda Lansac-Tôha; Alan Cleber Santos da Silva; Bianca Ramos de Meira; Ciro Yoshio Joko; Cláudio Simões de Morais-Júnior; Edissa Emi Cortez Silva; Eneida Maria Eskinazi-Sant'Anna; Felipe Rafael Oliveira; et al. (Limnologica, 2023)

TRPV1 inactivation alters core body temperature and serum corticosterone levels: Impacts on clock genes expression in the liver and adrenal glands - Nayara AC. Horta; Paola Fernandes; Thais SR. Cardoso; Frederico SM. Machado; Lucas R. Drummond; Cândido C. Coimbra; Samuel P. Wanner; Ana Maria L Castrucci; Maristela O. Poletini (Journal of Thermal Biology, 2023)

Genome sequencing of Cladophialophora exuberans, a novel candidate for bioremediation of hydrocarbon and heavy metal polluted habitats - Nickolas Menezes da Silva; Guilherme Fonseca Reis; Flávia de Fátima Costa; Maria Eduarda Grisolia; Marlon Roger Geraldo; Bruno Paulo Rodrigues Lustosa; Bruna Jacomel Favoreto de Souza Lima; Vinicius Almir Weiss; Emanuel Maltempi de Souza; Ruoyu Li; Yinggai Song; Mariana Machado Fidelis Nascimento; et al. (Fungal Biology, 2023)

Embryotoxicity of silica nanoparticles in the drug delivery of domperidone in zebrafish - Lorranny Pereira de Assis Valadares; Larise Caroline Oliveira Lima; Simone Maria Teixeira de Saboia-Morais; Tatiane Moraes Arantes; Fernando Henrique Cristovan; Naiton Martins da Silva; Aline Borges Andrade; Sandra Aparecida Benite Ribeiro; Benner Geraldo Alves; Barbara do Carmo Rodrigues Virote; Ives Charlie da Silva; Mônica Rodrigues Ferreira Machado (Aquatic Toxicology, 2023)

Antimicrobial and anti-biofilm activity of silver nanoparticles biosynthesized with Cystoseira algae extracts - Mário Fernandes; Noelia González-Ballesteros; André da Costa; Raúl Machado; Andreia C. Gomes; Maria Carmen Rodríguez-Argüelles (JBIC Journal of Biological Inorganic Chemistry, 2023)
Antimicrobial resistance is an ever-growing global concern to public health with no clear or immediate solution. Silver nanoparticles (AgNPs) have long been proposed as efficient agents to fight the growing number of antibiotic-resistant strains. However, the synthesis of these particles is often linked to high costs and the use of toxic, hazardous chemicals, with environmental and health impact. In this study, we successfully produced AgNPs by green synthesis with the aid of the extract of two brown algae— Cystoseira baccata (CB) and Cystoseira tamariscifolia (CT)—and characterized their physico-chemical properties. The NPs produced in both cases (Ag@CB and Ag@CT) present similar sizes, with mean diameters of around 22 nm. The antioxidant activity of the extracts and the NPs was evaluated, with the extracts showing important antioxidant activity. The bacteriostatic and bactericidal properties of both Ag@CB and Ag@CT were tested and compared with gold NPs produced in the same algae extracts as previously reported. AgNPs demonstrated the strongest bacteriostatic and bactericidal properties, at concentrations as low as 2.16 µg/mL against Pseudomonas aeruginosa and Escherichia coli . Finally, the capacity of these samples to prevent the formation of biofilms characteristic of infections with a poorer outcome was assessed, obtaining similar results. This work points towards an alternative for the treatment of bacterial infections, even biofilm-inducing, with the possibility of minimizing the risk of drug resistance, albeit the necessary caution implied using metallic NPs. Graphical abstract

Polycyclic aromatic sulfur heterocycles used as molecular markers in crude oils and source rocks - Lua Morena Leoncio de Oliveira; Diego Nery do Amaral; Kalil Lopes de Amorim Ferreira; Carolina Santiago Souza; Gisele Mara Hadlich; Maria Elisabete Machado (Organic Geochemistry, 2023)

How to use recombinant bovine somatotropin in crossbred Holstein × Gyr (3/4 and 7/8) cows? - Betânia Glória Campos; Mayara Campos Lombardi; Hilton do Carmo Diniz Neto; Ângela Maria Quintão Lana; Marcos Neves Pereira; Euler Rabelo; Bruna Figueiredo Silper; Tiatrizi Siqueira Machado; Sandra Gesteira Coelho (Tropical Animal Health and Production, 2023)

Saline extract of Portulaca elatior leaves with photoprotective and antioxidant activities does not show acute oral and dermal toxicity in mice - Suéllen Pedrosa da Silva; Clarice Barbosa Lucena da Costa; Anderson Felipe Soares de Freitas; José Dayvid Ferreira da Silva; Wêndeo Kennedy Costa; Wênio Sandoval Filho Lima da Silva; Janaina Carla Barbosa Machado; Sandra Maria Souza da Silva; Magda Rhayanny Assunção Ferreira; Luiz Alberto Lira Soares; Jacinto da Costa Silva Neto; Márcia Vanusa da Silva; et al. (Toxicological Research, 2023)

Improvement of phenolic compounds production in callus cultures of Cereus hildmannianus (K.) Schum. by elicitation - Éverton da Silva Santos; Márcia Regina Pereira Cabral; Thaila Fernanda Oliveira da Silva; Arildo José Braz de Oliveira; Maria de Fátima Pires da Silva Machado; Claudete Aparecida Mangolin; Regina Aparecida Correia Gonçalves (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Brilliant blue FCF dye adsorption using magnetic activated carbon from Sapelli wood sawdust - Victoria X. Nascimento; Diana Pinto; Sabrina F. Lütke; Maria C. F. da Silva; Fernando. M. Machado; Éder. C. Lima; Luis F. O. Silva; Guilherme L. Dotto (Environmental Science and Pollution Research, 2023)

Thymic alterations resulting from experimental visceral leishmaniasis in a Syrian hamster (Mesocricetus auratus) - Karen Santos Março; Jaqueline da Silva Borégio; Giulia Gonçalves Jussiani; Laura Flávia Esperança de Souza Ferreira; Gabriela Venicia Araujo Flores; Carmen Maria Sandoval Pacheco; Marcia Dalastra Laurenti; Gisele Fabrino Machado (Veterinary Immunology and Immunopathology, 2023)

Toxic plants from the perspective of a “Quilombola” community in the Cerrado region of Brazil - Ricardo de Castro Santos Paim; Luiza Gabriella Ferreira de Paula; Débora Moreira Soares; Tarik Fernandes Gonçalves Rocha; Amanda Lopes Ribeiro; Natália Barros; Fabrício Carrião dos Santos; Heleno Dias Ferreira; Vera Lúcia Gomes-Klein; Benito Soto-Blanco; José Paes de Oliveira-Filho; Paulo Henrique Jorge da Cunha; et al. (Toxicon, 2023)

Physicochemical characteristics and volatile profile of pitaya (Selenicereus setaceus) - Maria da Graca Tomas; Luiz Jose Rodrigues; Francisco de Almeida Lobo; Katiuchia Pereira Takeuchi; Nelio Ranieli Ferreira de Paula; Daniella Moreira Pinto; Nascimento Nhantumbo; Mariana Pizzatto; Youssef Oualmakran; Gilson Gustavo Lucinda Machado; Eduardo Valerio de Barros Vilas Boas (South African Journal of Botany, 2023)

A pilot study of chemotherapy combinations in rats: Focus on mammary cancer treatment in female dogs - Laís Pereira Silva; Priscila Akemi Yamamoto; Marilia Carneiro de Araújo Machado; Fabiane Maria Fernandes Neves; Francine Johansson Azeredo; Ana Carolyne Santana dos Santos Silva; Nicole Hlavac; Denis de Melo Soares; Ana Leonor Pardo Campos Godoy; Alessandra Estrela-Lima (Research in Veterinary Science, 2023)

Impact of different kernel grades on volatile compounds profile, fatty acids and oxidative quality of cashew nut oil - Amanda Rodrigues Leal; Ana Paula Dionísio; Fernando Antonio Pinto de Abreu; Gilleno Ferreira de Oliveira; Idila Maria da Silva Araújo; Hilton César Rodrigues Magalhães; Andressa Barbosa Leite; Emilly Kaiane Maia da Silva; Ronaldo Ferreira do Nascimento; Hélio Oliveira do Nascimento; Paulo Henrique Machado de Sousa (Food Research International, 2023)

Implications of offshore wind energy developments in coastal and maritime tourism and recreation areas: An analytical overview - Júlia Terra M. Machado; Maria de Andrés (Environmental Impact Assessment Review, 2023)

Investigation of Human and Animal Viruses in Water Matrices from a Rural Area in Southeastern Region of Brazil and Their Potential Use as Microbial Source-Tracking Markers - Debora Regina Lopes dos Santos; Marcelle Silva-Sales; Tulio Machado Fumian; Adriana Gonçalves Maranhão; Fábio Correia Malta; Fernando César Ferreira; Marcia Maria Pimenta; Marize Pereira Miagostovich (Food and Environmental Virology, 2023)

Oxidative stress mediated cytogenotoxicological effects of phytol in wistar albino rats - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Antonielly Campinho dos Reis; José Victor de Oliveira Santos; Adriana Maria Viana Nunes; Felipe Cavalcante Carneiro da Silva; Keylla da Conceição Machado; João Marcelo de Castro e Sousa; Željko Reiner; Miquel Martorell; Sharmila Fagoonee; Javad Sharifi-Rad; et al. (Advances in Traditional Medicine, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Antifungal activity of essential oils and their combinations against storage fungi - Rubens Candido Zimmermann; Carolina Gracia Poitevin; Thaisa Siqueira da Luz; Edson José Mazarotto; Jason Lee Furuie; Carlos Eduardo Nogueira Martins; Wanderlei do Amaral; Roger Raupp Cipriano; Joatan Machado da Rosa; Ida Chapaval Pimentel; Maria A. C. Zawadneak (Environmental Science and Pollution Research, 2023)

Quantification of SARS-CoV-2 in wastewater samples from hospitals treating COVID-19 patients during the first wave of the pandemic in Brazil - Juliana Calábria de Araújo; Camila L. Madeira; Thiago Bressani; Cíntia Leal; Deborah Leroy; Elayne C. Machado; Luyara A. Fernandes; Maria Fernanda Espinosa; Gabriel Tadeu O. Freitas; Thiago Leão; Vera Tainá Mota; Alyne Duarte Pereira; et al. (Science of The Total Environment, 2023)

Silver nano/microparticle toxicity in the shrimp Litopenaeus vannamei (Boone, 1931) - Sonia Astrid Muñoz Buitrago; Grecica Mariana Colombo; Juan Rafael Buitrago; Robson Matheus Marreiro Gomes; Alan Carvalho de Sousa; Virgínia Fonseca Pedrosa; Luís Alberto Romano; Leandro Machado de Carvalho; Franciele Rovasi Adolfo; Wilson Wasielesky Junior; Marcelo Estrella Josende; José Maria Monserrat (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Impact of COVID-19 on Management, Quality and Satisfaction of Health Organizations: A Case Study in a Portuguese Hospital - Tânia Gaspar; Vanesa Salado; Maria do Céu Machado; Fábio Botelho Guedes; Manuela Faia-Correia; Anabela Coelho (International Journal of Environmental Research, 2023)
The hospital health care professionals are the front-line fighting COVID-19 considering they are responsible for all the care provided to patients. The purpose of this study was to determine the impact of COVID-19 at the hospital management level and, also, to understand how psychosocial environment, and satisfaction of Health Professionals were affected. A case study was performed in a Portuguese Hospital. Data were collected at one hospital under study at two different occasions: the first before the pandemic (November 2019) and the second almost two years after the pandemic started (November 2021). Regarding data collection, 37.0% of participants responded in the occasion 1 ( n = 296) and 63.0% responded in the occasion 2 ( n = 503). The instrument for the Assessment of Global Management of Health Organizations (AGMHO) consists of 39 items organized into six dimensions (Gaspar et al. in J Occup Environ Med 63: 581–587, 2021). Comparing timings pre and during pandemic COVID-19, it was found that the participants in the pre-COVID-19 era showed stronger organizational culture, higher quality of life, better psychosocial environment regarding content/leadership and higher job satisfaction when compared to the participants during pandemic COVID-19. On the other hand, participants in the second occasion were found to have higher psychosocial risks related to mental health when compared to participants in the pre-COVID-19 phase. We conclude that the professionals’ perception of the different dimensions of the health organization worsened after 2 years of the pandemic. With special focus on psychosocial risks at work and relationship with leadership.

Green coffee: economic relevance and a systematic review of the effects on human health - Henrique Bosso; Sandra Maria Barbalho; Ricardo de Alvares Goulart; Alda Maria Machado Bueno Otoboni (Critical Reviews in Food Science and Nutrition, 2023)

Static Balance in Hereditary Spastic Paraplegias: a Cross-sectional Study - Diana Maria Cubillos-Arcila; Valéria Feijó Martins; Ana Paula Janner Zanardi; Gustavo Dariva Machado; Daniela Burguêz; Natalia Andrea Gomeñuka; Leonardo Alexandre Peyré-Tartaruga; Jonas Alex Morales Saute (The Cerebellum, 2023)

Bovine anaplasmosis as a risk factor for retained placenta, mastitis, and abomasal displacement in dairy cattle - Claudia Almeida Scariot; Julian Scariot; Inalda Angélica de Souza Ramos; Luiz Ricardo Gonçalves; Ana Cláudia Calchi; Marcos Rogério André; Rosangela Zacarias Machado; Márcio Machado Costa; Luiz Carlos Kreutz; Ricardo Zanella; Maria Isabel Botelho Vieira (Research in Veterinary Science, 2023)

Corrigendum to “Relationship between thermal environment, thermoregulatory responses and energy metabolism in goats: A comprehensive review” Journal of Thermal Biology 109 (2022) 103324] - Ana Rebeca Castro Lima; Robson Mateus Freitas Silveira; Maria Samires Martins Castro; Laura Bertolaso De Vecchi; Angélica Santos Rabelo de Souza Bahia; Thaise Pinto de Melo; Márcia Helena Machado da Rocha Fernandes; Kléber Tomás Resende (Journal of Thermal Biology, 2023)

Influence of the ITCZ and OMZ on the isotopic composition of suspended particulate matter in the western tropical North Atlantic - Andres Piñango; Elias Azar; Mônica Wallner-Kersanach; Eunice da Costa Machado; Gabriela Martins; Thayná Peterle; Carlos Eduardo de Rezende; Maria da Graça Baumgarten (Journal of Marine Systems, 2023)

Chrysolaena obovata (Less.) Dematt., a species native of Brazilian Cerrado: genetic diversity and structure of natural populations and potential for inulin production - Leila M. Díaz; Alessandro Alves-Pereira; Maria I. Zucchi; Maria A. Machado de Carvalho; Marília Gaspar (Genetic Resources and Crop Evolution, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Small mammals from the C aatinga: A dataset for the B razilian semiarid biome - Anna Ludmilla da Costa‐Pinto; Ricardo S. Bovendorp; Adriana Bocchiglieri; Aldo Caccavo; Ana Cláudia Delciellos; Ana Cláudia Malhado; Ana Karolina Rodrigues de Almeida; Caryne Braga; Diogo Loretto; Edeltrudes Maria Valadares Calaça Câmara; Fernando Heberson Menezes; Gabby Guilhon; et al. (Ecology, 2023)
The Caatinga is an exclusively Brazilian biome, and is the largest and most biodiverse Seasonal Tropical Dry Forest in the world. Despite that, the mammalian fauna, especially small mammals, is the least studied of all Brazilian biomes. In order to fill gaps and provide detailed information on small mammals (Didelphimorphia, Rodentia) in the Caatinga biome, we compiled reliable records focusing on richness, composition and some biometric data. These records came from mammal collections, papers, theses, books, and unpublished data, prioritizing records with vouchers housed in scientific collections. We compiled a total of 3133 records from 816 locations, resulting in a richness of 47 native species (12 marsupials and 35 rodents, plus three exotic rodents, Rattus rattus , Rattus norvegicus , and Mus musculus ). This dataset includes records of three new species for the biome and its transition zone: the rodents Calomys mattevii , Holochilus oxe , and Nectomys squamipes . Of the total number of records, 1808 (57.71%) are from consulting activities, 95 (3.03%) are from zoonoses studies and 104 (3.32%) are from the National Plague Service (SNP). All nine Brazilian states with territory in the Caatinga have sampling data for small mammals, but the number of records and localities are unevenly distributed, with the state of Rio Grande do Norte having the lowest number of records and locations sampled. Our dataset is the first of its kind for the Caatinga biome and has considerable potential value for studies of habitat use, landscape ecology, macroecology, biogeography, and conservation. There are no copyright restrictions on the data. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Anatomical Modifications Modulated by Pretreatment with 24-Epibrassinolide Alleviate Boron Stress in Soybean Plants: Valuable Repercussions on Nutrient Contents, Photosynthesis, and Biomass - Ynglety Cascaes Pereira; Angelina Nilcélia da Silva Nascimento; Brenna Thayane dos Santos Aguiar; Breno Ricardo Serrão da Silva; Maria Antônia Machado Barbosa; Bruno Lemos Batista; Andrzej Bajguz; Allan Klynger da Silva Lobato (Journal of Soil Science and Plant Nutrition, 2022)

Antifungal susceptibility of the endophytic fungus Rhinocladiella similis (URM 7800) isolated from the Caatinga dry forest in Brazil - Ana Patrícia Sousa Lopes de Pádua; Alessandra Koehler; Danielle Machado Pagani; Jadson Diogo Pereira Bezerra; Cristina Maria de Souza-Motta; Maria Lúcia Scroferneker (Brazilian Journal of Microbiology, 2022)

Vegetation productivity under climate change depends on landscape complexity in tropical drylands - Helder F. P. de Araujo; Célia C. C. Machado; Ana Carolina Flores Alves; Mônica da Costa Lima; José Maria Cardoso da Silva (Mitigation and Adaptation Strategies for Global Change, 2022)

Enzymatic Hydrolysis of Pacific White Shrimp Residue ( Litopenaeus vannamei ) with Ultrasound Aid - José Stênio Aragão Rebouças Júnior; Vilásia Guimarães Martins; Carlos Prentice-Hernández; José Maria Monsserrat; Marcelo Borges Tesser; Juliana Machado Latorres (Journal of Aquatic Food Product Technology, 2022)

Phycoremediation of Coastal Marine Water Contaminated with Dissolved Oil by Nannochloropsis oculata - Júlia Cintra Almeida; Isadora Machado Marques; José Roberto Botelho de Souza; Ícaro Thiago Andrade Moreira; Olívia Maria Cordeiro de Oliveira (Water, Air, & Soil Pollution, 2022)

Apparent digestibility and ingestive behavior of Nellore bulls with low and high residual feed intake - Rayanne Galdino Menezes; Juliano José de Resende Fernandes; Alana Maria Menezes Di Calaça; Emmanuel Arnhold; Marcia Helena Machado da Rocha Fernandes; Victor Rezende Moreira Couto (Tropical Animal Health and Production, 2022)

Are echocardiographic parameters affected by body condition scores in blue-fronted Amazon parrots (Amazona aestiva, Linnaeus, 1758)? - Gisele Junqueira dos Santos; Amanda Sarita Cruz Aleixo; Alícia Giolo Hippólito; Barbara Sardela Ferro; Priscylla Tatiana Chalfun Guimarães Okamoto; Maria Lucia Gomes Lourenço; Vania Maria de Vasconcelos Machado; Paulo Roberto Rodrigues Ramos; Sheila Canevese Rahal; Carlos Roberto Teixeira; Alessandra Melchert (Veterinary Research Communications, 2022)

Normal echocardiographic and radiographic reference values for crab-eating fox (Cerdocyon thous) anesthetized with ketamine and midazolam - Victor R. F. Ribeiro; Ariana F. Ramos; Angélica Alfonso; Alicia G. Hippolito; Heloísa C. Lima; Viviane M. Codognoto; Diogo C. S. Silva; Miriam H. Tsunemi; Moacir L. Neto; Alessandra Melchert; Priscylla T. C. G. Okamoto; Luiz H. A. Machado; et al. (Veterinary Research Communications, 2022)

Staminode of Jacaranda rugosa A.H. Gentry (Bignoniaceae) promotes functional specialization by ensuring signaling and mechanical fit to medium-sized bees - Cristina Adriane de Souza Pontes; Arthur Domingos-Melo; Paulo Milet-Pinheiro; Daniela Maria do Amaral Ferraz Navarro; Tarcila Lima Nadia; Isabel Cristina Machado (Organisms Diversity & Evolution, 2022)

Applications of chitosan to the roots and shoots change the accumulation pattern of cadmium in Talinum patens (Talinaceae) cuttings - Samuel Vitor Assis Machado de Lima; Daniele Maria Marques; Matheus Felipe Soares Silva; Leticia Aparecida Bressanin; Paulo César Magalhães; Thiago Corrêa de Souza (Environmental Science and Pollution Research, 2022)

Colistin conditioning surfaces combined with antimicrobial treatment to prevent ventilator-associated infections - Diana Alves; Hélder Lopes; Idalina Machado; Maria Olívia Pereira (Biofouling, 2022)

Progression of Functional Gait in Hereditary Spastic Paraplegias - Diana Maria Cubillos-Arcila; Gustavo Dariva Machado; Lauren Sehnem; Daniela Burguêz; Ana Paula Janner Zanardi; Valéria Feijó Martins; Leonardo Alexandre Peyré-Tartaruga; Jonas Alex Morales Saute (The Cerebellum, 2022)

Porcine Primordial Germ Cell-Like Cells Generated from Induced Pluripotent Stem Cells Under Different Culture Conditions - Naira Caroline Godoy Pieri; Aline Fernanda de Souza; Ramon Cesar Botigelli; Laís Vicari de Figueiredo Pessôa; Kaiana Recchia; Lucas Simões Machado; Mayra Hirakawa Glória; Raquel Vasconcelos Guimarães de Castro; Diego Feitosa Leal; Paulo Fantinato Neto; Simone Maria Massami Kitamura Martins; Daniele dos Santos Martins; et al. (Stem Cell Reviews and Reports, 2022)

TNFα rs1799964 TT genotype may be a susceptibility factor for vertical transmission of Toxoplasma gondii and clinical signs in newborns from pregnant women with acute toxoplasmosis - Lillian Gonzalez Bonifácio; Mirele Melo; Christiane Maria Ayo; Letícia Carolina Paraboli Assoni; Larissa Martins Olímpio; Mariana Reis Nogueira; Lígia Cosentino Junqueira Franco Spegiorin; Deusenia Machado Ulisses Barbosa; Luiz Carlos de Mattos; Vera Lucia Pereira-Chioccola; Cinara Cássia Brandão (Molecular Biology Reports, 2022)

Inflammatory profile in cervical cancer: influence of purinergic signaling and possible therapeutic targets - Maria Luiza Mukai Franciosi; Thiago Inácio Teixeira do Carmo; Daniela Zanini; Andréia Machado Cardoso (Inflammation Research, 2022)

Modification by genetic polymorphism of lead-induced IQ alteration: a systematic review - Luíza Siqueira Lima; Maria Eduarda Andrade Galiciolli; Meire Ellen Pereira; Karoline Felisbino; Cleber Machado-Souza; Cláudia Sirlene de Oliveira; Izonete Cristina Guiloski (Environmental Science and Pollution Research, 2022)

Human health risk assessment for (re)emerging protozoan parasites in surface water used for public supply and recreational activities - Brisa Maria Fregonesi; Guilherme Sgobbi Zagui; Karina Aparecida de Abreu Tonani; Carolina Sampaio Machado; Guilherme Gomes-Silva; José Antônio Padula; Solange Martone-Rocha; Maria Tereza Pepe Razzolini; Martin Plath; Susana Segura-Muñoz (Environmental Monitoring and Assessment, 2022)

A neglected disease. Human sporotrichosis in a densely populated urban area in São Paulo, Brazil: clinical–epidemiological and therapeutic aspects - Amanda Azevedo Bittencourt; Luiza Keiko Matsuka Oyafuso; Roberta Figueiredo Cavalin; Renata Bacic Palhares; Gil Benard; Viviane Mazo Fávero Gimenes; Gilda Maria Barbaro Del Negro; Lumena Pereira Machado Siqueira; Roseli Santos de Freitas Xavier; Leila M. Lopes-Bezerra; Renata Buccheri; José Angelo Lauletta Lindoso (Brazilian Journal of Microbiology, 2022)

Level of genetic divergence among accessions of the native forage grass, Mesosetum chaseae Luces, for tracing strategies to conservation of germplasm collections from the brazilian pantanal - Ana Clara de Sousa Meirelles; Eliane Rodrigues Monteiro; Claudete Aparecida Mangolin; Sandra Aparecida Santos; Maria de Fátima P. S. Machado (Conservation Genetics Resources, 2022)

Sunlight Irradiated Pyrite-Fenton System for Advanced Oxidative Treatment of Textile Dyes Mixture - Rayany Magali da Rocha Santana; Daniella Carla Napoleão; Sérgio Gonzaga dos Santos Júnior; Rayssa Kelen de Mendonça Gomes; Alex Leandro Andrade de Lucena; Graziele Elisandra do Nascimento; Victor Marcelo Estolano de Lima; Antônio Acacio de Melo Neto; Giovanna Machado; Ana Maria Mendonça de Albuquerque Melo; Marta Maria Menezes Bezerra Duarte (Water, Air, & Soil Pollution, 2022)

First report of Lasiodiplodia pseudotheobromae causing cladode rot in Hylocereus sp. in Brazil - Juliana Ferreira de Mello; Amanda Cupertino de Queiroz Brito; Eliude dos Santos Oliveira da Silva; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Pathology, 2022)

Adhesive secretion in Schizolobium parahyba (Vell.) Blake (Leguminosae: Caesalpinioideae): histochemical and morpho-functional characterization of this unusual feature in woody plants - Elder Antônio Sousa Paiva; Denise Maria Trombert Oliveira; Yve Canaveze; Silvia Rodrigues Machado (Arthropod-Plant Interactions, 2022)

Leishmanicidal and trypanocidal potential of the essential oil of Psidium myrsinites DC. - Lilian Cortez Sombra Vandesmet; Saulo Almeida de Menezes; Benedito Yago Machado Portela; Mariana Gomes Vidal Sampaio; Cícero Ramon Bezerra dos Santos; Vilmar Luiz Lermen; Maria Celeste Vega Gomez; Márcia Vanusa da Silva; Irwin Rose de Alencar Menezes; Maria Tereza dos Santos Correia (Natural Product Research, 2022)

Portuguese wild hop diversity assessment by fast SNP genotyping using high-resolution melting - Julio C. Machado; Miguel A. Faria; Ana Maria Barata; Isabel Gomes da Silva; Andreja Cerenak; Isabel M. P. L. V. O. Ferreira (Journal of Applied Genetics, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Mini‐cutting technique application in Corymbia and Eucalyptus: effects of mini‐tunnel use across seasons of the year - Marllos Santos de Lima; Maristela Machado Araujo; Álvaro Luís Pasquetti Berghetti; Suelen Carpenedo Aimi; Claudia Costella; Adriana Maria Griebeler; Luiza Michelon Somavilla; Osmarino Pires dos Santos; Brígida Maria dos Reis Teixeira Valente (New Forests, 2022)

Genetic differentiation and gene flow of the Amazonian catfish Pseudoplatystoma punctifer across the Madeira River rapids prior to the construction of hydroelectric dams - Antonio Saulo Cunha-Machado; Izeni Pires Farias; Tomas Hrbek; Maria Doris Escobar; José Antônio Alves-Gomes; Kyara Martins Formiga; Jacqueline da Silva Batista (Hydrobiologia, 2022)

Synthesis, antibiotic modifying activity, ADMET study and molecular docking of chalcone (E)-3-(2,4-dichlorophenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one in strains of Staphylococcus aureus carrying MepA efflux pumps - Janaína Esmeraldo Rocha; Thiago Sampaio de Freitas; Jayze da Cunha Xavier; Raimundo Luiz Silva Pereira; Francisco Nascimento Pereira; Carlos Emídio Sampaio Nogueira; Márcia Machado Marinho; Paulo Nogueira Bandeira; Maria Alyce Albuquerque Fernandes; Emmanuel Silva Marinho; Alexandre Magno Rodrigues Teixeira; Hélcio Silva dos Santos; et al. (Archives of Microbiology, 2022)

Evaluation of the anticonvulsant and antioxidant activity of alkylated cardanol in rodents - Danielle Fernanda Fernandes Vieira; Antonio Luiz Gomes Junior; Keylla da Conceição Machado; Wcleubianne Matias Nascimento Maia; Tassio Lessa do Nascimento; Maria Alexsandra de Sousa Rios; Luciano da Silva Lopes (Natural Product Research, 2021)

Identification and in silico characterization of structural and functional impacts of genetic variants in milk protein genes in the Zebu breeds Guzerat and Gyr - Carolina Guimarães Ramos Matosinho; Izinara Cruz Rosse; Pablo Augusto Souza Fonseca; Francislon Silva de Oliveira; Fausto Gonçalves dos Santos; Flávio Marcos Gomes Araújo; Anna Christina de Matos Salim; Beatriz Cordenonsi Lopes; Wagner Antonio Arbex; Marco Antônio Machado; Maria Gabriela Campolina Diniz Peixoto; Rui da Silva Verneque; et al. (Tropical Animal Health and Production, 2021)

Advances in Bone tissue engineering: A fundamental review - Bruna Maria Manzini; Leonardo Mendes Ribeiro Machado; Pedro Yoshito Noritomi; Jorge Vicente Lopes da Silva (Journal of Biosciences, 2021)

Swine influenza A virus subtypes circulating in Brazilian commercial pig herds from 2012 to 2019 - Ana Luiza Soares Fraiha; Ana Carolina Diniz Matos; João Luis Reis Cunha; Beatriz Senra Álvares da Silva Santos; Maria Vitória Chaves Peixoto; Anna Gabriella Guimarães Oliveira; Grazielle Cossenzo Florentino Galinari; Heloíza Irtes de Jesus Nascimento; Maria Isabel Maldonado Coelho Guedes; Alexandre de Magalhães Vieira Machado; Erica Azevedo Costa; Zélia Inês Portela Lobato (Brazilian Journal of Microbiology, 2021)

Simultaneous changes in visual acuity, cortical population receptive field size, visual field map size, and retinal thickness in healthy human aging - Maria Fatima Silva; Ben M. Harvey; Lília Jorge; Nádia Canário; Fátima Machado; Mário Soares; Otília C. d’Almeida; Miguel Castelo-Branco (Brain Structure and Function, 2021)
Healthy human aging is associated with a deterioration of visual acuity, retinal thinning, visual field map shrinkage and increasing population receptive field sizes. Here we ask how these changes are related to each other in a cross-sectional sample of fifty healthy adults aged 20–80 years. We hypothesized that age-related loss of macular retinal ganglion cells may lead to decreased visual field map sizes, and both may lead to increased pRF sizes in the cortical central visual field representation. We measured our participants’ perceptual corrected visual acuity using standard ophthalmological letter charts. We then measured their early visual field map (V1, V2 and V3) functional population receptive field (pRF) sizes and structural surface areas using fMRI, and their retinal structure using high-definition optical coherence tomography. With increasing age visual acuity decreased, pRF sizes increased, visual field maps surface areas (but not whole-brain surface areas) decreased, and retinal thickness decreased. Among these measures, only functional pRF sizes predicted perceptual visual acuity, and Bayesian statistics support a null relationship between visual acuity and cortical or retinal structure. However, pRF sizes were in turn predicted by cortical structure only (visual field map surface areas), which were only predicted by retinal structure (thickness). These results suggest that simultaneous disruptions of neural structure and function throughout the early visual system may underlie the deterioration of perceptual visual acuity in healthy aging.

Microscopic Detection, Hematological Evaluation and Molecular Characterization of Piroplasms from Naturally Infected Dogs in Rio de Janeiro, Brazil - Fernanda Barbosa dos Santos; Gilberto Salles Gazêta; Laís Lisboa Corrêa; Lucas Fernandes Lobão; João Pedro Siqueira Palmer; Laís Verdan Dib; José André Lessa Damasceno; Nicole Oliveira Moura-Martiniano; Otilio Machado Pereira Bastos; Claudia Maria Antunes Uchôa; Alynne da Silva Barbosa (Acta Parasitologica, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Anti-leukemic activity of semisynthetic derivatives of lupeol - Vanessa Rocha Machado; Amanda Virtuoso Jacques; Natália Stefanes Marceli; Maique Weber Biavatti; Maria Cláudia Santos-Silva (Natural Product Research, 2021)

Tick-borne zoonotic agents infecting horses from an urban area in Midwestern Brazil: epidemiological and hematological features - João Bosco Vilela Campos; Filipe Santos Martins; Carina Elisei de Oliveira; Amanda Alves Taveira; João Roberto de Oliveira; Luiz Ricardo Gonçalves; Matheus Dias Cordeiro; Ana Claudia Calchi; Lina de Campos Binder; Maria Carolina de Azevedo Serpa; Amália Regina Mar Barbieri; Marcelo B. Labruna; et al. (Tropical Animal Health and Production, 2021)

Anxiolytic-like effect of natural product 2-hydroxy-3,4,6-trimethoxyacetophenone isolated from Croton anisodontus in adult zebrafish via serotonergic neuromodulation involvement of the 5-HT system - Antonio Wlisses da Silva; Maria Kueirislene A. Ferreira; Emanuela L. Rebouças; Francisco Rogenio S. Mendes; Atilano Lucas dos S. Moura; Jane Eire S. A. de Menezes; Márcia Machado Marinho; Emmanuel Silva Marinho; Hélcio S. Santos; Alexandre M. R. Teixeira (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Therapeutic approaches employing natural compounds and derivatives for treating bipolar disorder: emphasis on experimental models of the manic phase - Vânia Machado Recart; Luiza Spohr; Mayara Sandrielly Pereira Soares; Karina Pereira Luduvico; Francieli Moro Stefanello; Roselia Maria Spanevello (Metabolic Brain Disease, 2021)

Virological Characterization of Roof-Harvested Rainwater of Densely Urbanized Low-Income Region - Tatsuo Shubo; Adriana Maranhão; Fernando César Ferreira; Tulio Machado Fumian; Márcia Maria Araújo Pimenta; Cláudia do Rosário Vaz Morgado; Simon Toze; Warish Ahmed; Jatinder Sidhu; Marize Pereira Miagostovich (Food and Environmental Virology, 2021)

Minimum temperature and evapotranspiration in Central Amazonian floodplains limit tree growth of Nectandra amazonum (Lauraceae) - Janaína Quixabeira Gonçalves; Flávia Machado Durgante; Florian Wittmann; Maria Teresa Fernandez Piedade; Daigard Ricardo Ortega Rodriguez; Mário Tomazello-Filho; Pia Parolin; Jochen Schöngart (Trees, 2021)

Apoplasmic barrier in the extrafloral nectary of Citharexylum myrianthum (Verbenaceae) - Silvia Rodrigues Machado; Tatiane Maria Rodrigues (Planta, 2021)

Possible role of purinergic signaling in COVID-19 - Maria Luiza Mukai Franciosi; Millena Daher Medeiros Lima; Maria Rosa Chitolina Schetinger; Andréia Machado Cardoso (Molecular and Cellular Biochemistry, 2021)

Effect of temperature on Colletotrichum truncatum growth, and evaluation of its inoculum potential in soybean seed germination - Manoel Batista da Silva Júnior; Mário Lúcio Vilela Resende; Edson A. Pozza; José da Cruz Machado; Alexandre Ribeiro Maia de Resende; Acleide Maria Santos Cardoso; Sarah da Silva Costa Guimarães; Deila Magna dos Santos Botelho (European Journal of Plant Pathology, 2021)

Bacterial biosurfactant increases ex situ biodiesel bioremediation in clayey soil - Andressa Decesaro; Alan Rempel; Thaís Strieder Machado; Ângela Carolina Cappellaro; Bruna Strieder Machado; Iziquiel Cechin; Antônio Thomé; Luciane Maria Colla (Biodegradation, 2021)

A critical view on the technology readiness level (TRL) of microbial plastics biodegradation - Julio Cesar Soares Sales; Ariane Gaspar Santos; Aline Machado de Castro; Maria Alice Zarur Coelho (World Journal of Microbiology and Biotechnology, 2021)

Ginkgo biloba Extract (GbE) Restores Serotonin and Leptin Receptor Levels and Plays an Antioxidative Role in the Hippocampus of Ovariectomized Rats - Meira Maria Forcelini Machado; Renata Mancini Banin; Fernanda Malanconi Thomaz; Iracema Senna de Andrade; Valter Tadeu Boldarine; Jéssica de Souza Figueiredo; Bruna Kelly Sousa Hirata; Lila Missae Oyama; João Henrique Ghilardi Lago; Eliane Beraldi Ribeiro; Mônica Marques Telles (Molecular Neurobiology, 2021)

Two new Penicillium section Sclerotiorum species from sugarcane soil in Brazil - Sérgio Murilo Sousa Ramos; Roberta Cruz; Renan do Nascimento Barbosa; Jos Houbraken; Alexandre Reis Machado; Cristina Maria de Souza-Motta; Neiva Tinti de Oliveira (Mycological Progress, 2021)

Acarbose presents in vitro and in vivo antileishmanial activity against Leishmania infantum and is a promising therapeutic candidate against visceral leishmaniasis - Rafaella R. Costa; João A. Oliveira-da-Silva; Thiago A. R. Reis; Grasiele S. V. Tavares; Débora V. C. Mendonça; Camila S. Freitas; Daniela P. Lage; Vívian T. Martins; Luciana M. R. Antinarelli; Amanda S. Machado; Raquel S. Bandeira; Fernanda Ludolf; et al. (Medical Microbiology and Immunology, 2021)

Peptidogalactomannan from Histoplasma capsulatum yeast cell wall: role of the chemical structure in recognition and activation by peritoneal macrophages - Giulia Maria Pires dos Santos; Gustavo Ramalho Cardoso dos Santos; Mariana Ingrid Dutra da Silva Xisto; Rodrigo Rollin-Pinheiro; Andréa Regina de Souza Baptista; Elisabeth Martins da Silva da Rocha; Ricardo Luiz Dantas Machado; Eliana Barreto-Bergter; Marcia Ribeiro Pinto (Brazilian Journal of Microbiology, 2021)

Vaginal cytology and cervical mucus as tools to predict ovulation time in small ruminants - Joanna Maria Gonçalves Souza-Fabjan; Viviane Lopes Brair; Dafne dos Santos Silva; Ana Paula Pereira Schmidt; Lucas Machado Figueira; Paulo Sérgio Cerqueira Rangel; Gabriel Brun Vergani; Vitória de Oliveira Machado; Maria Emilia Franco Oliveira; Jeferson Ferreira da Fonseca (Tropical Animal Health and Production, 2021)

Histological changes in banana rhizomes promoted by a silicon-Fusarium oxysporum interaction - Emília Gabriela Jesus da Conceição; Fabiano Machado Martins; Adriana Maria de Aguiar Accioly; Larisse de Freitas-Silva; Maria Fernanda Antunes da Cruz (Journal of Plant Pathology, 2021)

Persulfate mediated solar photo-Fenton aiming at wastewater treatment plant effluent improvement at neutral PH: emerging contaminant removal, disinfection, and elimination of antibiotic-resistant bacteria - Maria Clara V. M. Starling; Elizângela P. Costa; Felipe A. Souza; Elayne C. Machado; Juliana Calábria de Araujo; Camila C. Amorim (Environmental Science and Pollution Research, 2021)
This work investigated an innovative alternative to improve municipal wastewater treatment plant effluent (MWWTP effluent) quality aiming at the removal of contaminants of emerging concern (caffeine, carbendazim, and losartan potassium), and antibiotic-resistant bacteria (ARB), as well as disinfection ( E. coli ). Persulfate was used as an alternative oxidant in the solar photo-Fenton process (solar/Fe/S 2 O 8 2− ) due to its greater stability in the presence of matrix components. The efficiency of solar/Fe/S 2 O 8 2− at neutral pH using intermittent iron additions is unprecedented in the literature. At first, solar/Fe/S 2 O 8 2− was performed in a solar simulator (30 W m −2 ) leading to more than 60% removal of CECs, and the intermittent iron addition strategy was proved effective. Then, solar/Fe/S 2 O 8 2− and solar/Fe/H 2 O 2 were compared in semi-pilot scale in a raceway pond reactor (RPR) and a cost analysis was performed. Solar/Fe/S 2 O 8 2− showed higher efficiencies of removal of target CECs (55%), E. coli (3 log units), and ARB (3 to 4 log units) within 1.9 kJ L −1 of accumulated irradiation compared to solar/Fe/H 2 O 2 (CECs, 49%; E. coli , 2 log units; ARB, 1 to 3 log units in 2.5 kJ L −1 ). None of the treatments generated acute toxicity upon Allivibrio fischeri . Lower total cost was obtained using S 2 O 8 2− (0.6 € m −3 ) compared to H 2 O 2 (1.2 € m −3 ). Therefore, the iron intermittent addition aligned to the use of persulfate is suitable for MWWTP effluent quality improvement at neutral pH.

Molecular profiling of the Mahanarva spectabilis salivary glands and phytohormonal response of elephant grass - Nayara B. Saraiva; Nayara B. Emidio; Camilo E. Vital; Michélia A. N. Gusmão; Danielle G. Marconato; Flaviane Silva Coutinho; Jorge Fernando Pereira; Alexander Machado Auad; Priscila Faria-Pinto; Humberto J. O. Ramos; Maria Goreti Almeida Oliveira (International Journal of Tropical Insect Science, 2021)

Genetic and evolutionary analyses of plastomes of the subfamily Cactoideae (Cactaceae) indicate relaxed protein biosynthesis and tRNA import from cytosol - Gleyson Morais da Silva; Amanda de Santana Lopes; Túlio Gomes Pacheco; Kleiton Lima de Godoy Machado; Maria Carolina Silva; José Daniel de Oliveira; Valter Antonio de Baura; Eduardo Balsanelli; Emanuel Maltempi de Souza; Fábio de Oliveira Pedrosa; Marcelo Rogalski (Brazilian Journal of Botany, 2021)

Promising application of the SsCBF ELISA test to monitor the therapeutic response of feline sporotrichosis caused by Sporothrix brasiliensis from Brazilian epidemics - Vivian S. Baptista; Gabriele Barros Mothé; Giulia M. P. Santos; Carla Stefany I. Melivilu; Thayana O. Santos; Emylli D. Virginio; Pãmella A. de Macêdo-Sales; Márcia Ribeiro Pinto; Ricardo Luiz D. Machado; Elisabeth M. S. Rocha; Leila Maria Lopes-Bezerra; Andréa Regina S. Baptista (Brazilian Journal of Microbiology, 2021)

Canine sporotrichosis: polyphasic taxonomy and antifungal susceptibility profiles of Sporothrix species in an endemic area in Brazil - Jéssica Sepulveda Boechat; Sandro Antonio Pereira; Ana Caroline de Sá Machado; Paula Gonçalves Viana; Rodrigo Almeida-Paes; Rosely Maria Zancopé-Oliveira; Isabella Dib Ferreira Gremião; Manoel Marques Evangelista de Oliveira (Brazilian Journal of Microbiology, 2021)

The environmental importance of iron speciation in soils: evaluation of classic methodologies - Gabriele Verônica de Mello Gabriel; Leonardo Machado Pitombo; Luana Maria Tavares Rosa; Acacio Aparecido Navarrete; Wander Gustavo Botero; Janaina Braga do Carmo; Luciana Camargo de Oliveira (Environmental Monitoring and Assessment, 2021)

Rosmarinic acid prevents gastric ulcers via sulfhydryl groups reinforcement, antioxidant and immunomodulatory effects - Raphaela Francelino do Nascimento; Rodrigo de Oliveira Formiga; Flávia Danielle Frota Machado; Igor Rafael Praxedes de Sales; Gedson Moraes de Lima; Edvaldo Balbino Alves Júnior; Giciane Carvalho Vieira; Raquel Fragoso Pereira; Aurigena Antunes de Araújo; Raimundo Fernandes de Araújo Junior; José Maria Barbosa Filho; Leônia Maria Batista (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Labeling PLA-PEG nanocarriers with IR780: physical entrapment versus covalent attachment to polylactide - Marina Guimarães Carvalho Machado; Gwenaelle Pound-Lana; Maria Alice de Oliveira; Elisa Gomes Lanna; Márcia Célia Pacheco Fialho; Ana Carolina Ferreira de Brito; Ana Paula Moreira Barboza; Rodrigo Dian de Oliveira Aguiar-Soares; Vanessa Carla Furtado Mosqueira (Drug Delivery and Translational Research, 2020)

Health benefits and bioavailability of marine resources components that contribute to health – what’s new? - Paulo Nova; Ana Pimenta-Martins; Joana Laranjeira Silva; Ana Machado Silva; Ana Maria Gomes; Ana Cristina Freitas (Critical Reviews in Food Science and Nutrition, 2020)

Influence of nutrient restriction on finishing Morada Nova lambs - Delano de Sousa Oliveira; Arnaud Azevêdo Alves; Marcos Cláudio Pinheiro Rogério; Roberto Cláudio Fernandes Franco Pompeu; Elzânia Sales Pereira; Danielle Maria Machado Ribeiro Azevêdo; Luciana Freitas Guedes; Clésio dos Santos Costa; James Pierre Muir (Tropical Animal Health and Production, 2020)

Microclimate and pasture area preferences by dairy cows under high biodiversity silvopastoral system in Southern Brazil - Matheus Deniz; Abdon L. Schmitt Filho; Maria J. Hötzel; Karolini T. de Sousa; Luiz C. Pinheiro Machado Filho; Paulo A. Sinisgalli (International Journal of Biometeorology, 2020)

Nutrient and sediment fluxes in microbasins with different conservation states in the northeastern Brazil - Felipe de Souza Pimenta; Maria Eugênia Bruck de Moraes; Daniela Mariano Lopes da Silva; Roberto Ferreira Machado Michel (Environmental Monitoring and Assessment, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Relevance of Mitochondrial Dysfunction in the Reserpine-Induced Experimental Fibromyalgia Model - Evelyne da Silva Brum; Maria Fernanda Pessano Fialho; Susana Paula Moreira Fischer; Diane Duarte Hartmann; Débora Farina Gonçalves; Rahisa Scussel; Ricardo Andrez Machado-de-Ávila; Cristiane Lenz Dalla Corte; Félix Alexandre Antunes Soares; Sara Marchesan Oliveira (Molecular Neurobiology, 2020)

MLH1 intronic variants mapping to + 5 position of splice donor sites lead to deleterious effects on RNA splicing - Tamara Alejandra Piñero; Omar Soukarieh; Marion Rolain; Karin Alvarez; Francisco López-Köstner; Giovana Tardin Torrezan; Dirce Maria Carraro; Ivana Lucia De Oliveira Nascimento; Thaís Ferreira Bomfim; Taísa Manuela Bonfim Machado-Lopes; Juliana Côrtes Freitas; Maria Betânia Toralles; et al. (Familial Cancer, 2020)

Targeting NF-κB signaling pathway in cancer by dietary polyphenols - Haroon Khan; Hammad Ullah; Paula Cristina Machado Ferreira Castilho; Antoni Sureda Gomila; Grazia D'Onofrio; Rosanna Filosa; Fang Wang; Seyed Mohammad Nabavi; Maria Daglia; Ana Sanches Silva; Kannan R. R. Rengasamy; Juanying Ou; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Anatomical and ultrastructural studies reveal temporal and spatial variation in the oil production in leaves of the diesel tree (Copaifera langsdorffii, Leguminosae) - Plácido Fabrício Silva Melo Buarque; Silvia Rodrigues Machado; Tatiane Maria Rodrigues (Protoplasma, 2020)

Detection of rubber tree orchards infested by Meloidogyne exigua using vegetation indexes obtained from satellite images - Ernane M. Lemes; Túlio V. Machado; Luciana N. Gontijo; Samuel L. de Andrade; José L. R. Torres; Maria A. Santos; Lísias Coelho (New Forests, 2020)

Diclofenac shifts the role of root glutamine synthetase and glutamate dehydrogenase for maintaining nitrogen assimilation and proline production at the expense of shoot carbon reserves in Solanum lycopersicum L - Maria Martins; Bruno Sousa; Jorge Lopes; Cristiano Soares; Joana Machado; Susana Carvalho; Fernanda Fidalgo; Jorge Teixeira (Environmental Science and Pollution Research, 2020)

Biomarkers of oxidative stress and cell damage in freshwater bivalves Diplodon parodizi exposed to landfill leachate - Juliani Giselli Prestes; Maria Rosa Dmengeon Pedreiro De Souza; Priscila Krebsbach Kandalski; Tatiana Herrerias; Cintia Machado; Elen de Arruda Martins; Vanessa Abelaira dos Anjos; Ananda Karla Alves Neundorf; Diego Mauro Carneiro Pereira; Maurício Osvaldo Moura; Lucelia Donatti (Environmental Science and Pollution Research, 2020)

Genetic connectivity of black drum (Pogonias courbina) stocks in the southwestern Atlantic Ocean - Renan Costa Machado; Maria Cristina da Silva Cortinhas; Maíra Carneiro Proietti; Manuel Haimovici (Environmental Biology of Fishes, 2020)

Phospholipids modifications in human hepatoma cell lines (HepG2) exposed to silver and iron oxide nanoparticles - Joseph A. Adeyemi; Carlos Arterio Sorgi; Ana Rita Thomazela Machado; Abayomi T. Ogunjimi; Luiz Gustavo Araujo Gardinassi; Viviani Nardini; Lucia Helena Faccioli; Lusania Maria Greggi Antunes; Fernando Barbosa (Archives of Toxicology, 2020)

Effect of trace metals on growth performance and accumulation of lipids, proteins, and carbohydrates on the green microalga Scenedesmus obliquus - Carlos Yure Barbosa de Oliveira; Thayna Lie Viegas; Maria Fernanda Oliveira da Silva; Debora Machado Fracalossi; Rafael Garcia Lopes; Roberto Bianchini Derner (Aquaculture International, 2020)

Adaptive Capacity Level Shapes Social Vulnerability to Climate Change of Fishing Communities in the South Brazil Bight - Ivan Machado Martins; Maria A. Gasalla (Frontiers in Marine Science, 2020)

Investigative Analysis of Lanthanum Oxide Nanoparticles on Elements in Bone of Wistar Rats After 30 Days of Repeated Oral Administration - Valderi Luiz Dressler; Oluwafemi Temitayo Ogunmodede; Graciela Marine Heidrich; Vinicius Machado Neves; Maria Rosa Chitolina Schetinger; Vera Maria Morsch (Biological Trace Element Research, 2020)

Evolving trends in next-generation probiotics: a 5W1H perspective - Diana Almeida; Daniela Machado; José Carlos Andrade; Sónia Mendo; Ana Maria Gomes; Ana Cristina Freitas (Critical Reviews in Food Science and Nutrition, 2020)

Foods with microalgae and seaweeds fostering consumers health: a review on scientific and market innovations - Paulo Nova; Ana Pimenta Martins; Carla Teixeira; Helena Abreu; Joana Gabriela Silva; Ana Machado Silva; Ana Cristina Freitas; Ana Maria Gomes (Journal of Applied Phycology, 2020)

Correction to: Genetic Analysis of Hereditary Ataxias in Peru Identifies SCA10 Families with Incomplete Penetrance - Mario Cornejo-Olivas; Miguel Inca-Martinez; Raphael Machado Castilhos; Gabriel Vasata Furtado; Eduardo Preusser Mattos; Giovana Bavia Bampi; Sandra Leistner-Segal; Victoria Marca; Pilar Mazzetti; Maria Luiza Saraiva-Pereira; Laura Bannach Jardim (The Cerebellum, 2020)

Genetic Analysis of Hereditary Ataxias in Peru Identifies SCA10 Families with Incomplete Penetrance - Mario Cornejo-Olivas; Miguel Inca-Martinez; Raphael Machado Castilhos; Gabriel Vasata Furtado; Eduardo Preusser Mattos; Giovana Bavia Bampi; Sandra Leistner-Segal; Victoria Marca; Pilar Mazzetti; Maria Luiza Saraiva-Pereira; Laura Bannach Jardim (The Cerebellum, 2020)

Pollen flow within and among isolated populations of two rare, self-compatible plant species from inselbergs of Northeast Brazil - Artur M. Wanderley; Eloyza Karoline R. dos Santos; Leonardo Galetto; Ana Maria Benko-Iseppon; Isabel Cristina S. Machado (Plant Ecology, 2020)

Neopamera bilobata Say (Hemiptera: Rhyparochromidae) habit and density on strawberry cultivars - Fernando Teruhiko Hata; Maurício Ursi Ventura; Nilson Zacarias Bernabé Ferreira; Vinádio Lucas Béga; Iara Muniz Camacho; Maria Tereza de Paula; Renato Ribeiro Machado; Danilo Pezzoto de Lima (Phytoparasitica, 2020)

Intestinal carriage of extended-spectrum beta-lactamase–producing Enterobacteriaceae at admission in a Portuguese hospital - Marta Aires-de-Sousa; Elizeth Lopes; Maria Luísa Gonçalves; Ana Luísa Pereira; Augusto Machado e Costa; Hermínia de Lencastre; Laurent Poirel (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Gold-Coated Superparamagnetic Iron Oxide Nanoparticles Attenuate Collagen-Induced Arthritis after Magnetic Targeting - Maria Fernanda Hornos Carneiro; Ana Rita T. Machado; Lusânia M. G. Antunes; Talita E. Souza; Victor A. Freitas; Luiz C. A. Oliveira; Jairo L. Rodrigues; Marcio C. Pereira; Fernando Barbosa (Biological Trace Element Research, 2020)

Reintroduction of songbirds from captivity: the case of the Great-billed Seed-finch (Sporophila maximiliani) in Brazil - Ricardo Bomfim Machado; Luís Fábio Silveira; Maria Izabel Soares Gomes da Silva; Flávio Kulaif Ubaid; Cesar Augusto Medolago; Mercival Roberto Francisco; José Carmine Dianese (Biodiversity and Conservation, 2020)

Fungal communities differentially respond to warming and drought in tropical grassland soil - Tássio Brito de Oliveira; Rosymar Coutinho de Lucas; Ana Silvia de Almeida Scarcella; Alex Graça Contato; Thiago Machado Pasin; Carlos Alberto Martinez; Maria de Lourdes Teixeira de Moraes Polizeli (Molecular Ecology, 2020)
Climate change is predicted to cause more extreme events, such as heatwaves, and different precipitation patterns. The effects of warming and short‐term drought on soil microbial communities, in particular fungal communities, remain largely unexplored under field conditions. Here, we evaluated how the fungal community of a tropical grassland soil responds to these changes. A field experiment was carried out in a temperature free‐air controlled enhancement (T‐FACE) facility in Ribeirão Preto, Brazil. The isolated and combined effects of drought and a 2°C increase in temperature were investigated. Based on metabarcoding of the ITS2 region, a total of 771 operational taxonomic units were observed. While warming affected the community structure, drought affected the alpha diversity, and the interaction between warming and drought affected both diversity and structure. The change in community composition driven by warming affected only the less abundant species (>1% of the total sequences). The aspect of the fungal communities that was most affected was diversity, which was increased by drought ( p Curvularia , Thielavia and Fusarium species. Overall, our results provide evidence that fungal communities in tropical grassland soils have greater sensitivity to drought than to temperature, which might increase the incidence of certain soil‐borne diseases.

Germination and initial growth of common bean plants under water deficit as affected by seed treatment with S-nitrosoglutathione and calcium chloride - Neidiquele M. Silveira; Rafael V. Ribeiro; Paula J. C. Prataviera; Maria D. Pissolato; Joana C. Pieretti; Amedea B. Seabra; Eduardo C. Machado (Theoretical and Experimental Plant Physiology, 2020)

Purinergic signaling and tumor microenvironment in cervical Cancer - Marta Schmidt Pfaffenzeller; Maria Luiza Mukai Franciosi; Andréia Machado Cardoso (Purinergic Signalling, 2020)

Gastrointestinal Parasites in Captive Animals at the Rio de Janeiro Zoo - Alynne da Silva Barbosa; Jéssica Lima Pinheiro; Claudijane Ramos dos Santos; Camila Souza Carvalho Class de Lima; Laís Verdan Dib; Ginette Villar Echarte; Anderson Mendes Augusto; Augusto Cézar Machado Pereira Bastos; Claudia M. Antunes Uchôa; Otilio Machado Pereira Bastos; Fernanda Nunes Santos; Ana Beatriz Monteiro Fonseca; et al. (Acta Parasitologica, 2020)

It's raining fragrant nectar in the Caatinga: evidence of nectar olfactory signaling in bat‐pollinated flowers - Arthur Domingos‐Melo; Paulo Milet‐Pinheiro; Daniela Maria do Amaral Ferraz Navarro; Ariadna Valentina Lopes; Isabel Cristina Machado (Ecology, 2020)

Synthetic scenario generation of monthly streamflows conditioned to the El Niño–Southern Oscillation: application to operation planning of hydrothermal systems - Felipe Treistman; Maria Elvira Piñeiro Maceira; Débora Dias Jardim Penna; Jorge Machado Damázio; Otto Corrêa Rotunno Filho (Stochastic Environmental Research and Risk Assessment, 2020)

Pharmacological potential of alkylamides from Acmella oleracea flowers and synthetic isobutylalkyl amide to treat inflammatory pain - Jorge Luiz Dallazen; Daniele Maria-Ferreira; Bruna Barbosa da Luz; Adamara Machado Nascimento; Thales Ricardo Cipriani; Lauro Mera de Souza; Letícia Polli Glugoski Felipe; Bruno José Gonçalves Silva; Romina Nassini; Maria Fernanda de Paula Werner (Inflammopharmacology, 2020)

Novel amylase-producing fungus hydrolyzing wheat and brewing residues, Aspergillus carbonarius, discovered in tropical forest remnant - Thiago Machado Pasin; Eliano dos Anjos Moreira; Rosymar Coutinho de Lucas; Vivian Machado Benassi; Luciana Sobrani Ziotti; Mariana Cereia; Maria de Lourdes Teixeira de Moraes Polizeli (Folia Microbiologica, 2020)

Long-term chromium picolinate supplementation improves colostrum profile of Santa Ines ewe - Thiago F. V. Bompadre; Débora B. Moretti; Gabriel Z. Sakita; Egon H. Ieda; Maria I. V. Martinez; Elisabete A. N. Fernandes; Raul Machado-Neto; Adibe L. Abdalla; Helder Louvandini (Biological Trace Element Research, 2020)

Estimating Global Catches of Marine Recreational Fisheries - Kátia Meirelles Felizola Freire; Dyhia Belhabib; Jeniffer C. Espedido; Lincoln Hood; Kristin M. Kleisner; Vicky W. L. Lam; Michel L. Machado; Jocemar Tomasino Mendonça; Jessica J. Meeuwig; Pietro S. Moro; Fábio S. Motta; Maria-Lourdes D. Palomares; et al. (Frontiers in Marine Science, 2020)

Comparison of Four Parasitological Techniques for Laboratory Diagnosis of Eggs from Spirometra spp. in Wild Mammal Fecal Samples - Laís Verdan Dib; João Pedro Siqueira Palmer; Camila de Souza Carvalho Class de Lima; Raissa Cristina Ferreira Ramos; Otilio Machado Pereira Bastos; Claudia Maria Antunes Uchôa; Maria Regina Reis Amendoeira; Ana Beatriz Monteiro Fonseca; Augusto Cezar Machado Pereira Bastos; Alynne da Silva Barbosa (Acta Parasitologica, 2019)

First report of Macrophomina pseudophaseolina causing stem dry rot in cassava in Brazil - Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; Sami Jorge Michereff; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Pathology, 2019)

Photosynthesis and biomass accumulation in young sugarcane plants grown under increasing ammonium supply in nutrient solution - Maria D. Pissolato; Neidiquele M. Silveira; Eduardo C. Machado; Fernando C. B. Zambrosi; Ladaslav Sodek; Rafael V. Ribeiro (Theoretical and Experimental Plant Physiology, 2019)

Effect of long-term thermal challenge on the Antarctic notothenioid Notothenia rossii - Priscila Krebsbach Kandalski; Tania Zaleski; Mariana Forgati; Flávia Baduy; Danilo Santos Eugênio; Cintia Machado; Maria Rosa Dmengeon Pedreiro de Souza; Cláudio Adriano Piechnik; Luís Fernando Fávaro; Lucélia Donatti (Fish Physiology and Biochemistry, 2019)

Genetics and telemetry indicate unexpected movements among structured populations for Brachyplatystoma platynemum in the Amazon - Lisiane Hahn; Priscilla C. Silva; Maria C. Malabarba; Luiz R. Malabarba; Luís F. Da Câmara; Leonardo D. Nunes; Leonardo S. Machado; Eduardo G. Martins; Ronaldo B. Barthem (Journal of Fish Biology, 2019)
The genetic analysis of Brachyplatystoma platynemum individuals sampled from the lower Madeira River reinforces the existence of two structured populations in the Amazon Basin (Madeira and Amazon populations). However, the recapture of an individual from the Amazon population in the Solimões River, which was telemetry‐tagged in the Madeira River after the damming, indicates that fish from the Amazon population move between the two river systems. This has not yet been observed, however, in the Madeira River population, which is currently divided and isolated in the lower and upper Madeira River by the construction of two dams.

A new species of Piaractus (Characiformes: Serrasalmidae) from the Orinoco Basin with a redescription of Piaractus brachypomus - Maria D. Escobar L.; Rafaela P. Ota; Antonio Machado‐Allison; Juana Andrade‐López; Izeni P. Farias; Tomas Hrbek (Journal of Fish Biology, 2019)
Piaractus orinoquensis , a new species of serrasalmid fish, is described from the Orinoco River basin. The new species differs from congeners by having a slenderer body, relatively smaller head and snout, more compressed mid‐body, fewer scales above and below the lateral line and diagnostic molecular characters in the coI mitochondrial gene region. We also provide a re‐description of Piaractus brachypomus , restricting its geographic distribution to the Amazon River basin. Both species are economically important in their respective basins and need to be independently managed as distinct species.

Involvement of the Cholinergic Parameters and Glial Cells in Learning Delay Induced by Glutaric Acid: Protection by N-Acetylcysteine - Fernanda Silva Rodrigues; Viviane Nogueira de Zorzi; Marla Parizzi Funghetto; Fernanda Haupental; Alexandra Seide Cardoso; Sara Marchesan; Andréia M. Cardoso; Maria Rosa C. Schinger; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Marta Maria Medeiros Frescura Duarte; Léder L. Xavier; et al. (Molecular Neurobiology, 2019)

Evaluation of contaminants spreading from sludge piles, applying geochemical fractionation and attenuation of concentrations model in a tropical reservoir - Julio Cesar Wasserman; Aline Mansur Almeida; Daniel Vidal Perez; Maria Angélica Wasserman; Wilson Machado (Environmental Monitoring and Assessment, 2019)

Hemodialysis Water Parameters as Predisposing Factors for Anemia in Patients in Dialytic Treatment: Application of Mixed Regression Models - Meire Nikaido Suzuki; Brisa Maria Fregonesi; Carolina Sampaio Machado; Guilherme Sgobbi Zagui; Luciana Kusumota; Adriano Kamimura Suzuki; José Abrão Cardeal da Costa; Jordi Sierra Llopart; Martí Nadal; Jose Luis Domingo; Susana Segura-Muñoz (Biological Trace Element Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Spatial modeling applied to environmental monitoring: identifying sources of potentially toxic metals in aquatic system - Elisabete Leide Marzola; Luana Maria Tavares Rosa; Rogério Hartung Toppa; Marcos Roberto Martines; Leonardo Machado Pitombo; Alexandre Donizeti Martins Cavagis; Janaina Braga do Carmo; Wander Gustavo Botero; Luciana Camargo de Oliveira (Environmental Geochemistry and Health, 2019)

Subtle Chemical Variations with Strong Ecological Significance: Stereoselective Responses of Male Orchid Bees to Stereoisomers of Carvone Epoxide - Katharina Brandt; Stefan Dötterl; Roman Fuchs; Daniela Maria do Amaral Ferraz Navarro; Isabel Cristina Sobreira Machado; Daniel Dobler; Oliver Reiser; Manfred Ayasse; Paulo Milet-Pinheiro (Journal of Chemical Ecology, 2019)

Ipomoea vespertilia (Convolvulaceae), a new species revealed by pollinator observation - Francisco Diego Sousa Santos; Geadelande Carolino Delgado Junior; Mariana Báez; Andrea Pedrosa-Harand; Joel Araújo Queiroz; Zelma Glebya Maciel Quirino; Isabel Cristina Machado; Maria Teresa Buril (Brittonia, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Population growth of the stored product pest Tyrophagus putrescentiae (Acari: Acaridae) on environmentally and medically important fungi - Guilherme Liberato da Silva; Isadora Zanatta Esswein; Daiane Heidrich; Fabíola Dresch; Mônica Jachetti Maciel; Danielle Machado Pagani; Patrícia Valente; Maria Lúcia Scroferneker; Liana Johann; Noeli Juarez Ferla; Onilda Santos da Silva (Experimental and Applied Acarology, 2019)

Guarana improves behavior and inflammatory alterations triggered by methylmercury exposure: an in vivo fruit fly and in vitro neural cells study - Thaís Doeler Algarve; Charles Elias Assmann; Francine Carla Cadoná; Alencar Kolinski Machado; Maria Fernanda Manica-Cattani; Yukiko Sato-Miyata; Tsunaki Asano; Marta Maria Medeiros Frescura Duarte; Euler Esteves Ribeiro; Toshiro Aigaki; Ivana Beatrice Mânica da Cruz (Environmental Science and Pollution Research, 2019)

Correction to: Selective Forces Related to Spinocerebellar Ataxia Type 2 - Lucas Schenatto Sena; Raphael Machado Castilhos; Eduardo Preusser Mattos; Gabriel Vasata Furtado; José Luiz Pedroso; Orlando Barsottini; Maria Marla Paiva de Amorim; Clecio Godeiro; Maria Luiza Saraiva-Pereira; Laura Bannach Jardim (The Cerebellum, 2019)

Selective Forces Related to Spinocerebellar Ataxia Type 2 - Lucas Schenatto Sena; Raphael Machado Castilhos; Eduardo Preusser Mattos; Gabriel Vasata Furtado; José Luiz Pedroso; Orlando Barsottini; Maria Marla Paiva de Amorim; Clecio Godeiro; Maria Luiza Saraiva Pereira; Laura Bannach Jardim (The Cerebellum, 2019)

Increase of Candida antarctica lipase B production under PGK promoter in Pichia pastoris: effect of multicopies - Julia Macedo Robert; Maritza Ocampo Betancur; Antonio Carlos Oliveira Machado; Andrelisse Arruda; Viviane Castelo Branco Reis; Rodrigo Volcan Almeida; Fernando Araripe Gonçalves Torres; Pau Ferrer Alegre; Francisco Valero; Denise Maria Guimarães Freire (Brazilian Journal of Microbiology, 2019)

Intake, digestibility, microbial protein production, and nitrogen balance of lambs fed with sorghum silage partially replaced with dehydrated fruit by-products - Júlio César Silva Almeida; Darcilene Maria de Figueiredo; Katharine Kelly de Azevedo; Mônica Lopes Paixão; Enilson Geraldo Ribeiro; Gabriel Machado Dallago (Tropical Animal Health and Production, 2019)

Resveratrol-mediated reversal of changes in purinergic signaling and immune response induced by Toxoplasma gondii infection of neural progenitor cells - Nathieli B. Bottari; Micheli M. Pillat; Maria R.C. Schetinger; Karine P. Reichert; Vanessa Machado; Charles E. Assmann; Henning Ulrich; Anielen Dutra; Vera M. Morsch; Taís Vidal; Ivana B. M. Da Cruz; Cinthia Melazzo; et al. (Purinergic Signalling, 2019)

The phenotypic relationship between residual intake and gain and other feed efficiency traits in Nellore cattle - Darcilene Maria de Figueiredo; Maria Eugênia Zerlotti Mercadante; Aldrin Vieira Pires; Renata Helena Branco; Enilson Geraldo Ribeiro; Gabriel Machado Dallago; Marianne Schorer; Pedro Ribeiro Rocha (Tropical Animal Health and Production, 2019)

Integrating phylogeography and ecological niche modelling to test diversification hypotheses using a Neotropical rodent - Arielli Fabrício Machado; Mário Silva Nunes; Cláudia Regina Silva; Marcelo Augusto dos Santos; Izeni Pires Farias; Maria Nazareth Ferreira da Silva; Marina Anciães (Evolutionary Ecology, 2019)

Analysis of the effects of mesoporous silica particles SBA-15 and SBA-16 in Streptococcus pneumoniae transformation process - Maria-Cecília Krähenbühl Amstalden; José Diogo Oliveira; Mathias Strauss; Italo Odone Mazali; Daisy Machado; Thais Holtz Theisen; Marcelo Lancellotti (Folia Microbiologica, 2019)

Comparing toxicity and bioactivity of gold nanoparticles synthetized using two brown algae Cystoseira sp - Sofia Machado; Anabela Gonçalves; Noelia González-Ballesteros; Luana Magalhães; Marisa Sárria; Maria Carmen Rodríguez-Argüelles; Andreia C Gomes (Frontiers in Marine Science, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Effects of short-term thermal stress on the plasma biochemical profiles of two Antarctic nototheniid species - Priscila Krebsbach Kandalski; Maria Rosa Dmengeon Pedreiro de Souza; Tatiana Herrerias; Cintia Machado; Tania Zaleski; Mariana Forgati; Angela Carolina Guillen; Douglas Viana; Maurício Osvaldo Moura; Lucélia Donatti (Reviews in Fish Biology and Fisheries, 2018)

Description of rare mutations and a novel variant in Brazilian patients with Cystic Fibrosis: a case series from a referral center in the Bahia State - Laís Ribeiro Mota; Valmir Machado de Melo Filho; Lorena Lemos de Castro; Daniel Fantozzi Garcia; Regina Terse-Ramos; Maria Betânia Pereira Toralles; Renata Lúcia Leite Ferreira de Lima; Edna Lúcia Souza (Molecular Biology Reports, 2018)

Fumaric acid production using renewable resources from biodiesel and cane sugar production processes - Aikaterini Papadaki; Harris Papapostolou; Maria Alexandri; Nikolaos Kopsahelis; Seraphim Papanikolaou; Aline Machado de Castro; Denise M. G. Freire; Apostolis A. Koutinas (Environmental Science and Pollution Research, 2018)

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Glass eel ( Anguilla anguilla ) recruitment to the river Lis: Ingress dynamics in relation to oceanographic processes in the western Iberian margin and shelf - Yorgos Stratoudakis; Paulo B. Oliveira; Ana Teles‐Machado; José Manuel Oliveira; Maria João Correia; Carlos Antunes (Fisheries Oceanography, 2018)
To provide new information on the ingress dynamics of glass eels at the Portuguese coast, the study analyzes catch per unit effort ( CPUE ) data from river Lis, biometric data from recruits in basins of western Portugal and meteo‐oceanographic data from the Iberian margin and shelf. Biometric data of glass eels in western Portugal are congruent with the latitudinal size gradient of leptocephali in oceanic surveys and show clear seasonality, with longest and heaviest individuals arriving from October to December. Generalized additive models fitted to CPUE s from two experimental fishing periods (1996–1997 and 2013–2014) show that availability of glass eels to the sampling gear was inversely related to lunar phase and sea wave height. CPUE was lowest from May to September, increased towards the end of the year and peaked in February–March, when recruits were almost 40% lighter than autumn arrivals. Commercial CPUE during the 1989–1990 fishing season was significantly higher than experimental fishing data in 1996–1997. Higher variance and smaller sample size in 2013–2014 prevent conclusive interdecadal comparisons. Finally, CPUE was significantly higher during the prevalence of northward current flow off western Portugal and during strong cross‐shelf westerly winds. Findings support the suggestion that eel recruitment in Portugal occurs mainly by leptocephali travelling along the Azores Current, deflected northwards through the Iberian Poleward Current, with river ingress, and possibly oceanic metamorphosis, modulated by seasonal dynamics in coastal hydrology and shelf/upper margin oceanography.

The antioxidant gallic acid induces anxiolytic-, but not antidepressant-like effect, in streptozotocin-induced diabetes - Mariana Machado Pereira; Helen de Morais; Eldevan dos Santos Silva; Claudia Rita Corso; Eliana Rezende Adami; Rose Maria Carlos; Alexandra Acco; Janaina Menezes Zanoveli (Metabolic Brain Disease, 2018)

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

Niche expansion of the common waxbill (Estrilda astrild) in its non-native range in Brazil - José Maria Cardoso da Silva; Manuella Andrade de Souza; Vivian Ribeiro; Ricardo B. Machado (Biological Invasions, 2018)

Amblyomma ticks infesting amphibians and Squamata reptiles from the lower Amazon region, Brazil - Allana Cavalcante Torres; Antonio Humberto Hamad Minervino; Alfredo Pedroso Santos Júnior; Cristiane Sarturi; Thiago Fernandes Martins; Willian Gomes Vale; Adriana Caroprezo Morini; Arlei Marcili; Juliana Machado Portela; Solange Maria Gennari (Experimental and Applied Acarology, 2018)

Spatial distance and climate determine modularity in a cross‐biomes plant–hummingbird interaction network in Brazil - Andréa Cardoso Araujo; Ana M. Martín González; Brody Sandel; Pietro K. Maruyama; Erich Fischer; Jeferson Vizentin‐Bugoni; Francielle Paulina de Araújo; Aline Góes Coelho; Rogério Rodrigues Faria; Glauco Kohler; Flor Maria Guedes Las‐Casas; Ariadna Valentina Lopes; et al. (Journal of Biogeography, 2018)
Aim We examined the effects of space, climate, phylogeny and species traits on module composition in a cross‐biomes plant–hummingbird network. Location Brazil, except Amazonian region. Methods We compiled 31 local binary plant–hummingbird networks, combining them into one cross‐biomes metanetwork. We conducted a modularity analysis and tested the relationship between species’ module membership with traits, geographical location, climatic conditions and range sizes, employing random forest models. We fitted reduced models containing groups of related variables (climatic, spatial, phylogenetic, traits) and combinations of groups to partition the variance explained by these sets into unique and shared components. Results The Brazilian cross‐biomes network was composed of 479 plant and 42 hummingbird species, and showed significant modularity. The resulting six modules conformed well to vegetation domains. Only plant traits, not hummingbird traits, differed between modules, notably plants’ growth form, corolla length, flower shape and colour. Some modules included plant species with very restricted distributions, whereas others encompassed more widespread ones. Widespread hummingbirds were the most connected, both within and between modules, whereas widespread plants were the most connected between modules. Among traits, only nectar concentration had a weak effect on among‐module connectivity. Main conclusions Climate and spatial filters were the main determinants of module composition for hummingbirds and plants, potentially related to resource seasonality, especially for hummingbirds. Historical dispersal‐linked contingency, or environmental variations not accounted for by the explanatory factors here evaluated, could also contribute to the spatial component. Phylogeny and morphological traits had no unique effects on the assignment of species to modules. Widespread species showed higher within‐ and/or among‐module connectivity, indicating their key role connecting biomes, and, in the case of hummingbirds, communities within biomes. Our results indicate that biogeography and climate not only determine the variation of modularity in local plant–animal networks, as previously shown, but also affect the cross‐biomes network structure.

Genistein modulates the expression of Toll-like receptors in experimental autoimmune encephalomyelitis - Alyria Teixeira Dias; Sandra Bertelli Ribeiro de Castro; Caio César de Souza Alves; Marcilene Gomes Evangelista; Luan Cristian da Silva; Daniele Ribeiro de Lima Reis; Marco Antonio Machado; Maria Aparecida Juliano; Ana Paula Ferreira (Inflammation Research, 2018)

Balantioides coli: morphological and ultrastructural characteristics of pig and non-human primate isolates - Alynne da Silva Barbosa; Helene Santos Barbosa; Sandra Maria de Oliveira Souza; Laís Verdan Dib; Claudia Maria Antunes Uchôa; Otilio Machado Pereira Bastos; Maria Regina Reis Amendoeira (Acta Parasitologica, 2018)
Balantioides coli is a ciliated protozoon that inhabits the intestine of pigs, non-human primates and humans. Light microscopy studies have described over 50 species of the genus Balantioides but their validity is in doubt. Due to the limited information about this genus, this study is aimed to identify morphological characteristics of Balantioides coli isolated using fluorescence microscopy and both scanning (SEM) and transmission electron microscopy (TEM). Trophozoites isolated from the feces of pig and macaque were washed and subjected to centrifugation. These cells were fixed with paraformaldehyde for immunofluorescence. Other aliquots of these trophozoites were fixed with glutaraldehyde, post fixed with osmium tetroxide and processed for SEM and TEM. Immunofluorescence studies revealed microtubules with a longitudinal distribution to the main axis of the parasite and in the constitution of cilia. SEM demonstrated a high concentration of cilia covering the oral apparatus and a poor presence of such structures in cytopyge. TEM revealed in the plasma membrane, several associated structures were observed to delineate the cellular cortex and mucocysts. The cytoskeleton of the oral region was observed in detail and had an organization pattern consisting of microtubules, which formed files and nematodesmal networks. Organelles such as hydrogenosomes like and peroxisomes were observed close to the cortex. Macronuclei were observed, but structures that were consistent with micronuclei were not identified. Ultrastructural morphological analysis of isolates confirms its similarity to Balantioides coli . In this study were identified structures that had not yet been described, such as hydrogenosomes like and cytoskeletal structures.

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Adenovirus and rotavirus recovery from a treated effluent through an optimized skimmed-milk flocculation method - Andrêssa Silvino Ferreira Assis; Tulio Machado Fumian; Marize Pereira Miagostovich; Betânia Paiva Drumond; Maria Luzia da Rosa e Silva (Environmental Science and Pollution Research, 2018)

Fungal Diversity of Human Gut Microbiota Among Eutrophic, Overweight, and Obese Individuals Based on Aerobic Culture-Dependent Approach - Francis M. Borges; Thaís O. de Paula; Marjorie R. A. Sarmiento; Maycon G. de Oliveira; Maria L. M. Pereira; Isabela V. Toledo; Thiago C. Nascimento; Alessandra B. Ferreira-Machado; Vânia L. Silva; Cláudio G. Diniz (Current Microbiology, 2018)

Morphophysiological and nutritional characteristics of Crambe abyssinica Hochst under hydric restriction in different phenological stages - Nayara Parisoto Boiago; Andréa Maria Teixeira Fortes; Silvia Renata Machado Coelho; Flávia Danieli Rech Cassol; Daiane Maria Pilatti (Acta Physiologiae Plantarum, 2018)

Resin secretory canals in Protium heptaphyllum (Aubl.) Marchand. (Burseraceae): a tridimensional branched and anastomosed system - Fernanda Helena Palermo; Maria Ivanilde de Araújo Rodrigues; Juan de Nicolai; Silvia Rodrigues Machado; Tatiane Maria Rodrigues (Protoplasma, 2018)

Effect of variations in dietary Pi intake on intestinal Pi transporters (NaPi-IIb, PiT-1, and PiT-2) and phosphate-regulating factors (PTH, FGF-23, and MEPE) - Tatiana Martins Aniteli; Flávia Ramos de Siqueira; Luciene Machado dos Reis; Wagner Vasques Dominguez; Elizabeth Maria Costa de Oliveira; Patrícia Castelucci; Rosa Maria Affonso Moysés; Vanda Jorgetti (Pflügers Archiv - European Journal of Physiology, 2018)

Successful Treatment of Canine Sporotrichosis with Terbinafine: Case Reports and Literature Review - Paula Gonçalves Viana; Anna Barreto Fernandes Figueiredo; Isabella Dib Ferreira Gremião; Luisa Helena Monteiro de Miranda; Isabela Maria da Silva Antonio; Jéssica Sepulveda Boechat; Ana Caroline de Sá Machado; Manoel Marques Evangelista de Oliveira; Sandro Antonio Pereira (Mycopathologia, 2018)

Perceptions of climate and ocean change impacting the resources and livelihood of small-scale fishers in the South Brazil Bight - Ivan Machado Martins; Maria A. Gasalla (Climatic Change, 2018)

Photosynthesis and water relations of peach palms (Bactris gasipaes Kunth) under soil water deficit - Maria Luiza Sant’Anna Tucci; Eduardo Caruso Machado; Valéria Aparecida Modolo; Norma de Magalhães Erismann (Theoretical and Experimental Plant Physiology, 2018)

Extraction of Total Protein from Axillary Buds of Sugarcane (Saccharum spp.) for Proteomic Analysis - Rone Charles Maranho; Mariana Mancini Benez; Gustavo Barizon Maranho; Vanessa Neves de Azevedo Fernandes; Adriana Gonela; Claudete Aparecida Mangolin; Maria de Fátima Pires da Silva Machado (Sugar Tech, 2018)

The roles of geography and environment in divergence within and between two closely related plant species inhabiting an island‐like habitat - Artur Maia Wanderley; Isabel Cristina Sobreira Machado; Erton Mendonça de Almeida; Leonardo Pessoa Felix; Leonardo Galetto; Ana Maria Benko‐Iseppon; Victoria L. Sork (Journal of Biogeography, 2018)
Aim In island‐like habitats, geographic isolation facilitates population and species divergence by constraining gene flow, while environmental isolation can enhance divergence. We tested the relative contribution of geographic and environmental isolation in genetic and phenotypic divergence within and between two species of the figwort Ameroglossum (Scrophulariaceae) inhabiting spatially isolated habitats, known as inselbergs. Location Borborema Plateau, north‐eastern Brazil. Methods Multivariate models of redundancy ( RDA s) and partial redundancy analyses ( pRDA s) were used to partition the geographic and climate components of genetic variation in 48 microsatellite alleles, and phenotypic variation in 11 leaf and flower traits. We also used linear mixed‐effect models ( LME s) to test independent associations of floral tube length variation among inselbergs with local pollinator phenotypes, climate and geography. In each approach, we analysed the data for each species separately and in pooled models for both species. Results RDA s revealed that genetic variation within and between the species of Ameroglossum was associated similarly with geography and climate. Phenotypic variation within A. manoel‐felixii and between species was also associated similarly with geography and climate but, within A. pernambucense , phenotype was more strongly associated with climate. Linear mixed‐effect models revealed that flower divergence in A. manoel‐felixii was associated only with the bill length of local hummingbirds, whereas floral variation in A. pernambucense was associated with geography, bill length and climate. Only climate was associated with flower divergence between species. Main conclusions Genetic and phenotypic variation in Ameroglossum are associated with geographic and environmental isolation. These findings indicate a significant role of ecological factors shaping plant divergence among inselbergs, irrespective of their spatial distances.

Chagas disease: modulation of the inflammatory response by acetylcholinesterase in hematological cells and brain tissue - Aniélen D. Silva; Nathieli B. Bottari; Guilherme M. do Carmo; Matheus D. Baldissera; Carine F. Souza; Vanessa S. Machado; Vera M. Morsch; Maria Rosa C. Schetinger; Ricardo E. Mendes; Silvia G. Monteiro; Aleksandro S. Da Silva (Molecular and Cellular Biochemistry, 2018)

IL-33 signalling in liver immune cells enhances drug-induced liver injury and inflammation - Maísa Mota Antunes; Alan Moreira Araújo; Ariane Barros Diniz; Rafaela Vaz Sousa Pereira; Débora Moreira Alvarenga; Bruna Araújo David; Renata Monti Rocha; Maria Alice Freitas Lopes; Sarah Cozzer Marchesi; Brenda Naemi Nakagaki; Érika Carvalho; Pedro Elias Marques; et al. (Inflammation Research, 2018)

Communities of arbuscular mycorrhizal fungi under Picconia azorica in native forests of Azores - Catarina Drumonde Melo; Sara Luna; Claudia Krüger; Christopher Walker; Duarte Mendonça; Henrique M. A. C. Fonseca; Maria Jaizme-Vega; Artur Câmara Machado (Symbiosis, 2018)

Exposure to predicted precipitation patterns decreases population size and alters community structure of cyanobacteria in biological soil crusts from the Chihuahuan Desert - Vanessa M.C. Fernandes; Náthali Maria Machado de Lima; Daniel Roush; Jennifer Rudgers; Scott L. Collins; Ferran Garcia‐Pichel (Environmental Microbiology, 2018)
Summary Cyanobacteria typically colonize the surface of arid soils, building biological soil crust (biocrusts) that provide a variety of ecosystem benefits, ranging from fertilization to stabilization against erosion. We investigated how future scenarios in precipitation anticipated for the Northern Chihuahuan Desert affected abundance and composition of biocrust cyanobacteria in two grassland ecosystems. Scenarios included a decrease in precipitation and a delay of monsoon rainfall. After three years, both treatments negatively affected cyanobacteria, although the effects of monsoon delay were milder than those of decreased precipitation. Mature biocrusts in black grama grassland suffered severe losses in cyanobacterial biomass and diversity, but compositionally simpler biocrusts in blue grama‐dominated grassland maintained biomass, only suffering diversity losses. This could be partially explained by the differential sensitivity of cyanobacterial taxa: nitrogen‐fixing Scytonema spp. were the most sensitive, followed by phylotypes in the Microcoleus steenstrupii complex. Microcoleus vaginatus was the least affected in all cases, but is known to be very sensitive to warming. We predict that altered precipitation will tend to prevent biocrusts from reaching successional maturity, selecting for M. vaginatus over competing M. steenstrupii , among pioneer biocrust‐formers. A shift towards heat‐sensitive M. vaginatus could ultimately destabilize biocrusts when precipitation changes are combined with global warming.

Genetic diversity, population structure, and correlations between locally adapted zebu and taurine breeds in Brazil using SNP markers - Bárbara Machado Campos; Adriana Santana do Carmo; Andrea Alves do Egito; Arthur Silva da Mariante; Maria Socorro Muaés do Albuquerque; João José Simoni de Gouveia; Carlos Henrique Mendes Malhado; Lucas Lima Verardo; Marcos Vinícius Gualberto Barbosa da Silva; Paulo Luiz Souza Carneiro (Tropical Animal Health and Production, 2017)

Effects of Solanum sisymbriifolium on potato cyst nematode populations in Portugal - Margarida C. Dias; Laura S. Perpétuo; Ana T. Cabral; Rosa Guilherme; Maria J. M. da Cunha; Filipe Melo; Óscar C. Machado; Isabel Luci Conceição (Plant and Soil, 2017)

Haplotype Study in SCA10 Families Provides Further Evidence for a Common Ancestral Origin of the Mutation - Giovana B. Bampi; Rafael Bisso-Machado; Tábita Hünemeier; Tailise C. Gheno; Gabriel V. Furtado; Diego Veliz-Otani; Mario Cornejo-Olivas; Pillar Mazzeti; Maria Cátira Bortolini; Laura B. Jardim; Maria Luiza Saraiva-Pereira (NeuroMolecular Medicine, 2017)

Development of 15 SSR polymorphic markers for the endangered Ameroglossum pernambucense Eb. Fischer, S. Vogel & A. V. Lopes (Scrophulariaceae), and cross-transferability in congeneric taxa - Artur Maia Wanderley; Santelmo Vasconcelos; Bruno Huettel; Isabel Cristina Machado; Ana Maria Benko-Iseppon (Brazilian Journal of Botany, 2017)

Development, characterization and cross-amplification of microsatellite markers for Chrysolaena obovata, an important Asteraceae from Brazilian Cerrado - Leila Milena Diaz Camacho; Caio Alexandre de Freitas Schatzer; Alessandro Alves-Pereira; Maria Imaculada Zucchi; Maria Angela Machado de Carvalho; Marília Gaspar (Journal of Genetics, 2017)

Effects of heat stress on the renal and branchial carbohydrate metabolism and antioxidant system of Antarctic fish - Mariana Forgati; Priscila Krebsbach Kandalski; Tatiana Herrerias; Tania Zaleski; Cintia Machado; Maria Rosa Dmengeon Pedreiro Souza; Lucélia Donatti (Journal of Comparative Physiology B, 2017)

Stryphnodendron rotundifolium Mart. As an Adjuvant for the Plant Germination and Development Under Toxic Concentrations of HgCl2 and AlCl2 - Henrique D. M. Coutinho; Gioconda M. A. B. Martins; Maria F. B. Morais-Braga; Irwin R. A. Menezes; Antônio J. T. Machado; Maria A. Freitas; Antônia T. L. Santos; Maria S. Costa; Fábia F. Campina; Ana Raquel P. Silva; Luciene F. Lima; Nadghia F. Leite; et al. (Water, Air, & Soil Pollution, 2017)

A Neuroprotective Effect of the Glutamate Receptor Antagonist MK801 on Long-Term Cognitive and Behavioral Outcomes Secondary to Experimental Cerebral Malaria - Aline Silva de Miranda; Fátima Brant; Luciene Bruno Vieira; Natália Pessoa Rocha; Érica Leandro Marciano Vieira; Gustavo Henrique Souza Rezende; Pollyana Maria de Oliveira Pimentel; Marcio F.D. Moraes; Fabíola Mara Ribeiro; Richard M Ransohoff; Mauro Martins Teixeira; Fabiana Simão Machado; et al. (Molecular Neurobiology, 2017)

Defining the importance of landscape metrics for large branchiopod biodiversity and conservation: the case of the Iberian Peninsula and Balearic Islands - Jordi Sala; Stéphanie Gascón; David Cunillera-Montcusí; Miguel Alonso; Francisco Amat; Luís Cancela da Fonseca; Margarida Cristo; Margarita Florencio; Juan García-de-Lomas; Margarida Machado; Maria Rosa Miracle; Alexandre Miró; et al. (Hydrobiologia, 2017)

In vitro anti-MRSA activity of Couroupita guianensis extract and its component Tryptanthrin - Danielle Cristina Machado Costa; Mariana Maria Barros de Azevedo; Davi Oliveira e Silva; Maria Teresa Villela Romanos; Thais Cristina Baeta Soares Souto-Padrón; Celuta Sales Alviano; Daniela Sales Alviano (Natural Product Research, 2017)

Biosurfactants during in situ bioremediation: factors that influence the production and challenges in evalution - Andressa Decesaro; Thaís Strieder Machado; Ângela Carolina Cappellaro; Christian Oliveira Reinehr; Antônio Thomé; Luciane Maria Colla (Environmental Science and Pollution Research, 2017)

Gut microbiota and probiotics: Focus on diabetes mellitus - Livia Bordalo Tonucci; Karina Maria Olbrich Dos Santos; Celia Lucia De Luces Fortes Ferreira; Sonia Machado Rocha Ribeiro; Leandro Licursi De Oliveira; Hercia Stampini Duarte Martino (Critical Reviews in Food Science and Nutrition, 2017)

Interaction Study Between Humin and Phosphate: Possible Environmental Remediation for Domestic Wastewater - Daniella Araujo Vasconcelos de Oliveira; Wander Gustavo Botero; Josué Carinhanha Caldas Santos; Ricardo Moutinho da Silva; Leonardo Machado Pitombo; Janaina Braga do Carmo; Luana Maria Tavares Rosa; Luciana Camargo de Oliveira (Water, Air, & Soil Pollution, 2017)

Structure and functioning of oil cavities in the shoot apex of Metrodorea nigra A. St.-Hil. (Rutaceae) - Silvia Rodrigues Machado; Yve Canaveze; Tatiane Maria Rodrigues (Protoplasma, 2017)

Decrease in Adult Neurogenesis and Neuroinflammation Are Involved in Spatial Memory Impairment in the Streptozotocin-Induced Model of Sporadic Alzheimer’s Disease in Rats - Taysa Bervian Bassani; Jéssica M. Bonato; Meira M. F. Machado; Valentín Cóppola-Segovia; Eric L. R. Moura; Silvio M. Zanata; Rúbia M. M. W. Oliveira; Maria A. B. F. Vital (Molecular Neurobiology, 2017)

Spineless cactus associated with Tifton hay or sugarcane bagasse may replace corn silage in sheep diets - Julimar do Sacramento Ribeiro; Luana Lira Santos; Dorgival Morais de Lima Júnior; Tobyas Maia de Albuquerque Mariz; Márcio Machado Ladeira; Paulo Sérgio de Azevedo; Carolyny Batista Lima; Maria Josilaine Matos dos Santos Silva (Tropical Animal Health and Production, 2017)

Differential Pattern of Cerebellar Atrophy in Tremor-Predominant and Akinetic/Rigidity-Predominant Parkinson’s Disease - Camila Callegari Piccinin; Lidiane Soares Campos; Rachel Paes Guimarães; Luiza Gonzaga Piovesana; Maria Cristina Arci dos Santos; Paula Christina Azevedo; Brunno Machado Campos; Thiago Junqueira Ribeiro de Rezende; Augusto Amato-Filho; Fernando Cendes; Anelyssa D’Abreu (The Cerebellum, 2017)

The role of the P2X7 receptor in murine cutaneous leishmaniasis: aspects of inflammation and parasite control - Vanessa Ribeiro Figliuolo; Suzana Passos Chaves; Luiz Eduardo Baggio Savio; Maria Luiza Prates Thorstenberg; Érika Machado Salles; Christina Maeda Takiya; Maria Regina D’Império-Lima; Herbert Leonel de Matos Guedes; Bartira Rossi-Bergmann; Robson Coutinho-Silva (Purinergic Signalling, 2017)

Brazilian Decidual Tropical Forest enclaves: floristic, structural and environmental variations - Anne Priscila Dias Gonzaga; Evandro Luiz Mendonça Machado; Jeanine Maria Felfili; José Roberto Rodrigues Pinto (Brazilian Journal of Botany, 2017)

Main ozone-forming VOCs in the city of Sao Paulo: observations, modelling and impacts - Débora Souza Alvim; Luciana Vanni Gatti; Sergio Machado Corrêa; Júlio Barboza Chiquetto; Carlos de Souza Rossatti; Angélica Pretto; Maria Helena dos Santos; Amélia Yamazaki; João Paulo Orlando; Guaciara Macedo Santos (Air Quality, Atmosphere & Health, 2017)

Guideline Values and Metal Contamination in Soils of an Environmentally Impacted Bay - Nielson Machado dos Santos; Clístenes Williams Araújo do Nascimento; Adriana Maria de Aguiar Accioly (Water, Air, & Soil Pollution, 2017)

SNPs markers for the heavily overfished tambaqui Colossoma macropomum, a Neotropical fish, using next-generation sequencing-based de novo genotyping - José Gregorio Martínez; Valéria Nogueira Machado; Susana J. Caballero-Gaitán; Maria da C. Freitas Santos; Rodrigo Maciel Alencar; Maria Doris Escobar L.; Tomas Hrbek; Izeni Pires Farias (Conservation Genetics Resources, 2017)

Whole genome sequencing of Guzerá cattle reveals genetic variants in candidate genes for production, disease resistance, and heat tolerance - Izinara C. Rosse; Juliana G. Assis; Francislon S. Oliveira; Laura R. Leite; Flávio Araujo; Adhemar Zerlotini; Angela Volpini; Anderson J. Dominitini; Beatriz C. Lopes; Wagner A. Arbex; Marco A. Machado; Maria G. C. D. Peixoto; et al. (Mammalian Genome, 2017)

The expression patterns of aquaporin 9, vacuolar H+-ATPase, and cytokeratin 5 in the epididymis of the common vampire bat - Mariana M. Castro; Bongki Kim; Eric Hill; Maria C. Q. Fialho; Luciano C. H. P. Puga; Mariella B. Freitas; Sylvie Breton; Mariana Machado-Neves (Histochemistry and Cell Biology, 2017)

Rubus imperialis (Rosaceae) extract and pure compound niga-ichigoside F1: wound healing and anti-inflammatory effects - Talita Dacroce Tonin; Liliani Carolini Thiesen; Maria Luisa de Oliveira Nunes; Milena Fronza Broering; Marcos Paulo Donato; Marina Jagielski Goss; Marcel Petreanu; Rivaldo Niero; Isabel Daufenback Machado; José Roberto Santin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

The cannabinoid 2 receptor agonist β-caryophyllene modulates the inflammatory reaction induced by Mycobacterium bovis BCG by inhibiting neutrophil migration - Magaiver Andrade-Silva; Luana Barbosa Correa; André Luis Peixoto Candéa; Simone C. Cavalher-Machado; Helene Santos Barbosa; Elaine Cruz Rosas; Maria G Henriques (Inflammation Research, 2016)

Spectral reflectance characteristics of soils in northeastern Brazil as influenced by salinity levels - Luiz Guilherme Medeiros Pessoa; Maria Betânia Galvão Dos Santos Freire; Bradford Paul Wilcox; Colleen Heather Machado Green; Rômulo José Tolêdo De Araújo; José Coelho De Araújo Filho (Environmental Monitoring and Assessment, 2016)

Environmental factors affecting chlorophyll-a concentration in tropical floodplain lakes, Central Brazil - Suzana Maria Loures de Oliveira Marcionilio; Karine Borges Machado; Fernanda Melo Carneiro; Manuel Eduardo Ferreira; Priscilla Carvalho; Ludgero Cardoso Galli Vieira; Vera Lúcia de Moraes Huszar; João Carlos Nabout (Environmental Monitoring and Assessment, 2016)

Cytokines in Machado Joseph Disease/Spinocerebellar Ataxia 3 - Gerson da Silva Carvalho; Jonas Alex Morales Saute; Clarissa Branco Haas; Vitor Rocco Torrez; Andressa Wigner Brochier; Gabriele Nunes Souza; Gabriel Vasata Furtado; Tailise Gheno; Aline Russo; Thais Lampert Monte; Artur Schumacher-Schuh; Rui D’Avila; et al. (The Cerebellum, 2016)

Brazilian propolis extract used as an additive to decrease methane emissions from the rumen microbial population in vitro - Nadine Woruby Santos; Lucia Maria Zeoula; Emerson Henri Yoshimura; Erica Machado; Didier Macheboeuf; Agnès Cornu (Tropical Animal Health and Production, 2016)

Diversity of culturable Gram-negative bacteria isolated from irrigation water of two rice crop regions in Southern Brazil - Maria Helena Lima Ribeiro Reche; Catiusca Reali; Michele Pittol; Danilo de Athayde Saul; Vera Regina Mussoi Macedo; Victor Hugo Valiati; Vilmar Machado; Lidia Mariana Fiuza (Environmental Monitoring and Assessment, 2016)

Haloperidol and Risperidone at high concentrations activate an in vitro inflammatory response of RAW 264.7 macrophage cells by induction of apoptosis and modification of cytokine levels - Ivo Emílio da Cruz Jung; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Fernanda Barbisan; Verônica Farina Azzolin; Thiago Duarte; Marta Maria Medeiros Frescura Duarte; Pedro Antônio Schmidt do Prado-Lima; Guilherme Vargas Bochi; Gustavo Scola; Rafael Noal Moresco (Psychopharmacology, 2016)

Nitrogen metabolism, digestive parameters, and protein requirements for the maintenance of buffalo growth - Erica Machado; Emerson Henri Yoshimura; Nadine Woruby Santos; Bruna Calvo Agustinho; Lucelia de Moura Pereira; Rafael Barreiros Samensari; Silvia Cristina de Aguiar; Lucia Maria Zeoula (Tropical Animal Health and Production, 2016)

Susceptibility of meagre (Argyrosomus regius Asso, 1801) to Photobacterium damselae subsp. piscicida - Galhano Fábio; Cristóvão Maria Manuel; Costas Benjamín; Costa Janina; Machado Marina; Azeredo Rita; Morais Hugo; Anjos Catarina; França Marcela; Baptista Teresa (Frontiers in Marine Science, 2016)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

The anti-inflammatory effects of resveratrol on human peripheral blood mononuclear cells are influenced by a superoxide dismutase 2 gene polymorphism - Dianni Capeleto; Fernanda Barbisan; Verônica Azzolin; Eduardo Bortoluzzi Dornelles; Felipe Rogalski; Cibele Ferreira Teixeira; Alencar Kolinski Machado; Francine Carla Cadoná; Tális da Silva; Thiago Duarte; Marta Maria Medeiros Frescura Duarte; Ivana Beatrice Mânica da Cruz (Biogerontology, 2015)

Distribution of infective gastrointestinal helminth larvae in tropical erect grass under different feeding systems for lambs - Jalise Fabíola Tontini; Cesar Henrique Espírito Candal Poli; Carolina Bremm; Juliane Machado de Castro; Neuza Maria Fajardo; Bruna Nunes Marsiglio Sarout; Zélia Maria de Souza Castilhos (Tropical Animal Health and Production, 2015)

Optimization of biomass production of Chlorella vulgaris grown in desalination concentrate - Ângelo Paggi Matos; Weruska Brasileiro Ferreira; Regina Coeli de Oliveira Torres; Luiz Rodrigo Ito Morioka; Maria Helena Machado Canella; Jefferson Rotta; Tiago da Silva; Elisa Helena Siegel Moecke; Ernani Sebastião Sant’Anna (Journal of Applied Phycology, 2015)

Spermatozoan ultrastructure and mitochondrial gene sequence of Caryocorbula caribaea (d'Orbigny, 1853) (Corbulidae: Bivalvia), a species with plasticity in shell morphology - Lenita de Freitas Tallarico; Gisele Orlandi Introíni; Amanda Bonini; Flávio Dias Passos; Fabrizio Marcondes Machado; Eliane Pintor de Arruda; Shirlei Maria Recco-Pimentel (Molluscan Research, 2015)

Aflatoxin M 1 in raw milk from different regions of São Paulo state – Brazil - Ana Beatriz Nappi Santili; Adriano Costa de Camargo; Raquel de Syllos Rosa Nunes; Eduardo Micotti da Gloria; Paulo Fernando Machado; Laerte Dagher Cassoli; Carlos Tadeu dos Santos Dias; Maria Antonia Calori-Domingues (Food Additives & Contaminants Part B-Surveillance, 2015)

Vitamin D3 prevents the increase in ectonucleotidase activities and ameliorates lipid profile in type 1 diabetic rats - Nicéia Spanholi Calgaroto; Pauline da Costa; Andréia Machado Cardoso; Luciane Belmonte Pereira; Juliano Marchi Vieira; Diéssica Dalenogare; Luana Paula Pelinson; Jucimara Baldissarelli; Vera Maria Morsch; Maria Rosa Chitolina Schetinger (Molecular and Cellular Biochemistry, 2015)

Increased biomass saccharification by supplementation of a commercial enzyme cocktail with endo-arabinanase from Bacillus licheniformis - Carla Botelho Machado; Ana Paula Citadini; Rosana Goldbeck; Evandro Antônio de Lima; Fernanda Lopes Figueiredo; Tony Márcio da Silva; Zaira Bruna Hoffmam; Amanda Silva de Sousa; Fábio Márcio Squina; Maria de Lourdes Teixeira de Moraes Poliz; Roberto Ruller; Richard John Ward (Biotechnology Letters, 2015)

Detection of hormones in surface and drinking water in Brazil by LC-ESI-MS/MS and ecotoxicological assessment with Daphnia magna - Nádia Hortense Torres; Mario Mamede Aguiar; Luiz Fernando Romanholo Ferreira; Juliana Heloisa Pinê Américo; Ângela Maria Machado; Eliane Bezerra Cavalcanti; Valdemar Luiz Tornisielo (Environmental Monitoring and Assessment, 2015)

Adhesion, invasion, intracellular survival and cytotoxic activity of strains of Aeromonas spp. in HEp-2, Caco-2 and T-84 cell lines - Paula Azevedo dos Santos; Ana Claudia Machado Pereira; Andréa Fonseca Ferreira; Maria Angélica de Mattos Alves; Ana Cláudia Paula Rosa; Angela Corrêa Freitas-Almeida (Antonie van Leeuwenhoek, 2015)

Effects of curine in HL-60 leukemic cells: cell cycle arrest and apoptosis induction - Bruna Braga Dantas; Gláucia Veríssimo Faheina-Martins; Tangbadioa Hervé Coulidiati; Caio César Barbosa Bomfim; Celidarque da Silva Dias; José Maria Barbosa-Filho; Demetrius Antônio Machado Araújo (Journal of Natural Medicines, 2015)

In vitro propagation of Picconia azorica (Tutin) Knobl. (Oleaceae) an Azorean endangered endemic plant species - Duarte Mendonça; Sara Luna; Sílvia Bettencourt; Maria Susana Lopes; Lisandra Monteiro; João Drumonde Neves; Paulo Monjardino; Artur da Câmara Machado (Acta Physiologiae Plantarum, 2015)

Castanea root transcriptome in response to Phytophthora cinnamomi challenge - Susana Serrazina; Carmen Santos; Helena Machado; Catia Pesquita; Renato Vicentini; Maria Salomé Pais; Mónica Sebastiana; Rita Costa (Tree Genetics & Genomes, 2015)

D-serine plasma concentration is a potential biomarker of (R,S)-ketamine antidepressant response in subjects with treatment-resistant depression - Ruin Moaddel; David A. Luckenbaugh; Ying Xie; Alma Villaseñor; Nancy E. Brutsche; Rodrigo Machado-Vieira; Anuradha Ramamoorthy; Maria Paz Lorenzo; Antonia Garcia; Michel Bernier; Marc C. Torjman; Coral Barbas; et al. (Psychopharmacology, 2015)

Long-chain alkyltriazoles as antitumor agents: synthesis, physicochemical properties, and biological and computational evaluation - Vanessa Silva Gontijo; Michael Éder Oliveira; Rafael José Resende; Amanda Luisa Fonseca; Renata Rachide Nunes; Moacyr Comar Júnior; Alex Gutterres Taranto; Natalia Machado Pereira Oliveira Torres; Gustavo Henrique Ribeiro Viana; Luciana Maria Silva; Rosemeire Brondi Alves; Fernando Pilla Varotti; et al. (Medicinal Chemistry Research, 2015)

Structural lipid changes and NKA activity of gill cells´ basolateral membranes as response to increasing salinity and atrazine stressors in sea lamprey (Petromyzon marinus, L.) juveniles - Lança Maria João; Machado Maria; Candeias Marta; Ferreira Rui; Alves-Pereira Isabel; Ferreira Ana Filipa; Quintella Bernardo; R. Almeida Pedro (Frontiers in Marine Science, 2015)

Oocyte maturation in the sloth’s giant tick Amblyomma varium (Acari: Ixodidae) in an ecological context - Gustavo S. Sanches; Marcos R. André; Angelo P. do Prado; Silmara M. Allegretti; Rafael N. Remedio; Pablo H. Nunes; Rosangela Z. Machado; Gervásio H. Bechara; Maria I. Camargo-Mathias (Experimental and Applied Acarology, 2014)

Protective effect of quercetin in ecto-enzymes, cholinesterases, and myeloperoxidase activities in the lymphocytes of rats exposed to cadmium - Fátima Husein Abdalla; Andréia Machado Cardoso; Roberta Schmatz; Jamile Fabbrin Gonçalves; Jucimara Baldissarelli; Caroline Curry Martins; Daniela Zanini; Lizielle Souza de Oliveira; Pauline da Costa; Victor Camera Pimentel; Luciane Belmonte Pereira; Cibele Lima Lhamas; et al. (Molecular and Cellular Biochemistry, 2014)

Comparative chemical analysis and antifungal activity of Ochtodes secundiramea (Rhodophyta) extracts obtained using different biomass processing methods - Levi Pompermayer Machado; Luciana Retz de Carvalho; Maria Cláudia Marx Young; Leonardo Zambotti-Villela; Pio Colepicolo; Daniel Xavier Andreguetti; Nair S. Yokoya (Journal of Applied Phycology, 2014)

PIPKIIα is widely expressed in hematopoietic-derived cells and may play a role in the expression of alpha- and gamma-globins in K562 cells - Vânia Peretti de Albuquerque Wobeto; João Agostinho Machado-Neto; Tânia Regina Zaccariotto; Daniela Maria Ribeiro; Adriana da Silva Santos Duarte; Sara Teresinha Olalla Saad; Fernando Ferreira Costa; Maria de Fatima Sonati (Molecular and Cellular Biochemistry, 2014)

Allometric models for aboveground biomass estimation of the mangrove Avicennia schaueriana - Gustavo Calderucio Duque Estrada; Mário Luiz Gomes Soares; Daniel Medina Corrêa Santos; Viviane Fernandez; Paula Maria Moura de Almeida; Marciel Rocha de Medeiros Estevam; Maria Rita Olyntho Machado (Hydrobiologia, 2014)

Novel SNPs and INDEL polymorphisms in the 3′UTR of DGAT1 gene: in silico analyses and a possible association - Izinara da Cruz Rosse; Raphael da Silva Steinberg; Roney Santos Coimbra; Maria Gabriela Campolina Diniz Peixoto; Rui Silva Verneque; Marco Antonio Machado; Cleusa Graça Fonseca; Maria Raquel Santos Carvalho (Molecular Biology Reports, 2014)

Assessment of Water Quality in a Border Region Between the Atlantic Forest and an Urbanised Area in Rio de Janeiro, Brazil - Marize Pereira Miagostovich; Flávia Ramos Guimarães; Carmen Baur Vieira; Tulio Machado Fumian; Nilson Porto da Gama; Matias Victoria; Jaqueline Mendes de Oliveira; Anna Carolina de Oliveira Mendes; Ana Maria Coimbra Gaspar; José Paulo Gagliardi Leite (Food and Environmental Virology, 2014)

Geraniol—a flavoring agent with multifunctional effects in protecting the gastric and duodenal mucosa - Katharinne Ingrid Moraes de Carvalho; Flavia Bonamin; Raquel Cássia dos Santos; Larissa Lucena Périco; Fernando Pereira Beserra; Damião Pergentino de Sousa; José Maria Barbosa Filho; Lucia Regina Machado da Rocha; Clelia Akiko Hiruma-Lima (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Generation of reactive oxygen species by leukocytes of Prochilodus lineatus - Marcos Tucunduva de Faria; Maria Fernanda Cury-Boaventura; Lucia Rossetti Lopes; José Roberto Machado Cunha da Silva (Fish Physiology and Biochemistry, 2014)

Trends in the use of natural antioxidants in active food packaging: a review - Ana Sanches-Silva; Denise Costa; Tânia G. Albuquerque; Giovanna Giuliana Buonocore; Fernando Ramos; Maria Conceição Castilho; Ana Vera Machado; Helena S. Costa (Food Additives & Contaminants: Part A, 2014)

Effects of chlorogenic acid, caffeine, and coffee on behavioral and biochemical parameters of diabetic rats - Naiara Stefanello; Roberta Schmatz; Luciane Belmonte Pereira; Maribel A. Rubin; João Batista Teixeira da Rocha; Graziela Facco; Maria Ester Pereira; Cinthia Melazzo de Andrade Mazzanti; Sabina Passamonti; Marília Valvassori Rodrigues; Fabiano Barbosa Carvalho; Michelle Melgarejo da Rosa; et al. (Molecular and Cellular Biochemistry, 2014)

Design, synthesis, and antiviral activity of new 1H-1,2,3-triazole nucleoside ribavirin analogs - Maria de Lourdes G. Ferreira; Luiz C. S. Pinheiro; Osvaldo A. Santos-Filho; Marta D. S. Peçanha; Carolina Q. Sacramento; Viviane Machado; Vitor F. Ferreira; Thiago Moreno L. Souza; Núbia Boechat (Medicinal Chemistry Research, 2014)

Effect of ionic liquids alkyl chain length on horseradish peroxidase thermal inactivation kinetics and activity recovery after inactivation - Maria F. Machado; Rui P. Queirós; Mauro D. Santos; Liliana G. Fidalgo; Ivonne Delgadillo; Jorge A. Saraiva (World Journal of Microbiology and Biotechnology, 2014)

Spinocerebellar Ataxias in Brazil—Frequencies and Modulating Effects of Related Genes - Raphael Machado de Castilhos; Gabriel Vasata Furtado; Tailise Conte Gheno; Paola Schaeffer; Aline Russo; Orlando Barsottini; José Luiz Pedroso; Diego Z. Salarini; Fernando Regla Vargas; Maria Angélica de Faria Domingues d Lima; Clécio Godeiro; Luiz Carlos Santana-da-Silva; et al. (The Cerebellum, 2014)

Investigation of blood parasites of pygoscelid penguins at the King George and Elephant Islands, South Shetlands Archipelago, Antarctica - Ralph Eric Thijl Vanstreels; Flavia R. Miranda; Valeria Ruoppolo; Ana Olívia de Almeida Reis; Erli Schneider Costa; Adriana Rodrigues de Lira Pessôa; João Paulo Machado Torres; Larissa Schmauder Teixeira da Cunha; Roberta da Cruz Piuco; Victor Hugo Valiati; Daniel González-Acuña; Marcelo B. Labruna; et al. (Polar Biology, 2014)

Lacunas: a web interface to identify plant knowledge gaps to support informed decision-making - Dora Ann Lange Canhos; Mariane S. Sousa-Baena; Sidnei Souza; Letícia Couto Garcia; Renato De Giovanni; Leonor Costa Maia; Maria Beatriz Machado Bonacelli (Biodiversity and Conservation, 2014)

The central administration of C75, a fatty acid synthase inhibitor, activates sympathetic outflow and thermogenesis in interscapular brown adipose tissue - Priscila Cassolla; Ernane Torres Uchoa; Frederico Sander Mansur Machado; Juliana Bohnen Guimarães; Maria Antonieta Rissato Garófalo; Nilton de Almeida Brito; Lucila Leico Kagohara Elias; Cândido Celso Coimbra; Isis do Carmo Kettelhut; Luiz Carlos Carvalho Navegantes (Pflügers Archiv - European Journal of Physiology, 2013)

Antinociceptive and wound healing activities of Croton adamantinus Müll. Arg. essential oil - Rafael Matos Ximenes; Lenise de Morais Nogueira; Nathalia Maria Rodrigues Cassundé; Roberta Jeane Bezerra Jorge; Simone Maria dos Santos; Lucimere Paulino Machado Magalhães; Monalisa Ribeiro Silva; Glauce Socorro de Barros Viana; Renata Mendonça Araújo; Kêsia Xisto da Fonseca Ribeiro de Sena; Julianna Ferreira Cavalcanti de Albuquerque; René Duarte Martins (Journal of Natural Medicines, 2013)

Neuroprotective effect of quercetin in ectoenzymes and acetylcholinesterase activities in cerebral cortex synaptosomes of cadmium-exposed rats - Fátima Husein Abdalla; Andréia Machado Cardoso; Luciane Belmonte Pereira; Roberta Schmatz; Jamile Fabbrin Gonçalves; Naiara Stefanello; Amanda Maino Fiorenza; Jessié Martins Gutierres; Jonas Daci da Silva Serres; Daniela Zanini; Victor Camera Pimentel; Juliano Marchi Vieira; et al. (Molecular and Cellular Biochemistry, 2013)

Valproic acid: an anticonvulsant drug with potent antinociceptive and anti-inflammatory properties - José Christian Machado Ximenes; Danilo de Oliveira Gonçalves; Rafaelly Maria Pinheiro Siqueira; Kelly Rose Tavares Neves; Gilberto Santos Cerqueira; Alyne Oliveira Correia; Francisco Hélder Cavalcante Félix; Luzia Kalyne Almeida Moreira Leal; Gerly Anne de Castro Brito; Maria da Graça Naffah-Mazzacorati; Glauce Socorro de Barros Viana (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Expression analyses of Brachiaria brizantha genes encoding ribosomal proteins BbrizRPS8, BbrizRPS15a, and BbrizRPL41 during development of ovaries and anthers - Ana Luiza Machado Lacerda; Diva Maria de Alencar Dusi; Elizangela Ribeiro Alves; Júlio Carlyle Macedo Rodrigues; Ana Cristina Menezes Mendes Gomes; Vera Tavares de Campos Carneiro (Protoplasma, 2013)

Moderate Red Wine and Grape Juice Consumption Modulates the Hydrolysis of the Adenine Nucleotides and Decreases Platelet Aggregation in Streptozotocin-Induced Diabetic Rats - Roberta Schmatz; Thaís R. Mann; Roselia Spanevello; Michel M. Machado; Daniela Zanini; Victor C. Pimentel; Naiara Stefanello; Caroline C. Martins; Andréia M. Cardoso; Margarete Bagatini; Jessié Gutierres; Claudio A. M. Leal; et al. (Cell Biochemistry and Biophysics, 2013)

Fungemia by Candida pelliculosa (Pichia anomala) in a Neonatal Intensive Care Unit: A Possible Clonal Origin - Carolina Maria da Silva; Ana Maria Rabelo de Carvalho Parahym; Mariele Porto Carneiro Leão; Neiva Tinti de Oliveira; Rosemary de Jesus Machado Amorim; Rejane Pereira Neves (Mycopathologia, 2013)

Ectoenzymes and cholinesterase activity and biomarkers of oxidative stress in patients with lung cancer - Daniela Zanini; Roberta Schmatz; Luana Paula Pelinson; Victor Camera Pimentel; Pauline da Costa; Andréia Machado Cardoso; Caroline Curry Martins; Christina Chitolina Schetinger; Jucimara Baldissareli; Maria do Carmo Araújo; Liliane Oliveira; Juarez Chiesa; et al. (Molecular and Cellular Biochemistry, 2013)

Interleukin-6 gene −174G>C and −636G>C promoter polymorphisms and prostate cancer risk - J. F. Magalhães; A. J. Cortinhas; C. M. Albuquerque; C. S. Baptista; R. Ribeiro; Carlos Viegas; Augusto Matos; João Machado; Maria A. Pires; Henrique Guedes-Pinto; A. Martins-Bessa; J. C. Leitão; et al. (Molecular Biology Reports, 2013)

Prognostic significance of NDRG1 expression in oral and oropharyngeal squamous cell carcinoma - Marcelo dos Santos; Ana Maria da Cunha Mercante; Fábio Daumas Nunes; Andréia Machado Leopoldino; Marcos Brasilino de Carvalho; Diana Gazito; Rossana Verónica Mendoza López; Paula Blandina Olga Chiappini; Paulo Bentes de Carvalho Neto; Erica Erina Fukuyama; Eloiza Helena Tajara; Iúri Drumond Louro; et al. (Molecular Biology Reports, 2012)

Exercise training prevents ecto-nucleotidases alterations in platelets of hypertensive rats - Andréia Machado Cardoso; Margarete Dulce Bagatini; Caroline Curry Martins; Fátima Hussein Abdalla; Daniela Zanini; Roberta Schmatz; Jessié Gutierres; Victor Camera Pimentel; Gustavo Thomé; Claudio Alberto Martins Leal; Juliano Marchi Vieira; Naiara Stefanello; et al. (Molecular and Cellular Biochemistry, 2012)

Erratum to: Analysis of umbu (Spondias tuberosa Arruda (Anacardiaceae)) in different landscape management regimes - Ernani Machado de Freitas Lins Neto; Nivaldo Peroni; Christine Maria Carneiro Maranhão; Maria Inês Sucupira Maciel; Ulysses Paulino de Albuquerque (Environmental Monitoring and Assessment, 2012)

The use of microsatellites to analyze relationships and to decipher homonyms and synonyms in Azorean apples (Malus × domestica Borkh.) - Iris Foroni; Claudio Baptista; Lisandra Monteiro; Maria S. Lopes; Duarte Mendonça; Mónica Melo; Conceição Carvalho; Paulo Monjardino; David J. H. Lopes; Artur da Câmara Machado (Plant Systematics and Evolution, 2012)

Erratum to: Febrile response induced by cecal ligation and puncture (CLP) in rats: involvement of prostaglandin E2 and cytokines - Maria José Figueiredo; Denis Melo Soares; Juliano Manvailer Martins; Renes de Resende Machado; Carlos Arterio Sorgi; Lucia Helena Faccioli; Miriam Cristina Contin de Melo; David do Carmo Malvar; Glória E. P. Souza (Medical Microbiology and Immunology, 2012)

Analysis of umbu (Spondias tuberosa Arruda (Anacardiaceae)) in different landscape management regimes - Ernani Machado de Freitas Lins Neto; Nivaldo Peroni; Christine Maria Carneiro Maranhão; Maria Inês Sucupira Maciel; Ulysses Paulino de Albuquerque (Environmental Monitoring and Assessment, 2012)

Febrile response induced by cecal ligation and puncture (CLP) in rats: involvement of prostaglandin E2 and cytokines - Maria José Figueiredo; Denis de Melo Soares; Juliano Manvailer Martins; Renes de Resende Machado; Carlos Arterio Sorgi; Lucia Helena Faccioli; Miriam Cristina Contin de Melo; David do Carmo Malvar; Glória E. P. Souza (Medical Microbiology and Immunology, 2012)

Hymenoptera (Insecta: Hymenoptera) associated with silvopastoral systems - Alexander Machado Auad; Tiago Teixeira Resende; Daniela Maria da Silva; Marcy das Graças Fonseca (Agroforestry Systems, 2012)

A crucial role for IL-6 in the CNS of rats during fever induced by the injection of live E. coli - Denis M. Soares; Maria José Figueiredo; Juliano Manvailer Martins; Renes Resende Machado; Carlos Sorgi; Lucia Helena Faciolli; José C. Alves-Filho; Fernando Q. Cunha; Glória E. P. Souza (Medical Microbiology and Immunology, 2012)

Effect of antimicrobial residues on early adhesion and biofilm formation by wild-type and benzalkonium chloride-adapted Pseudomonas aeruginosa - Idalina Machado; Joana Graça; Ana Margarida Sousa; Susana Patrícia Lopes; Maria Olívia Pereira (Biofouling, 2011)

The annual cycle of spermatogenesis in Lipophrys pholis (Blenniidae), a recently proposed sentinel species for pollution monitoring - Filipa Ferreira; Miguel Machado Santos; Maria Armanda Reis-Henriques; Maria Natividade Vieira; Nuno Miguel Monteiro (Ichthyological Research, 2011)

Esterase Polymorphism and the Analysis of Genetic Diversity and Structure in Cactus Populations Descended from Cereus peruvianus Plants Regenerated In Vitro - Juliana Sala; Claudete Aparecida Mangolin; Juliana Franzoni; Maria de Fátima Pires da Silva Machado (Biochemical Genetics, 2011)

Distribution of oxidizable organic C fractions in soils under cacao agroforestry systems in Southern Bahia, Brazil - Patrícia A. B. Barreto; Emanuela F. Gama-Rodrigues; A. C. Gama-Rodrigues; Alexandre G. Fontes; José C. Polidoro; Maria Kellen S. Moço; Regina C. R. Machado; V. C. Baligar (Agroforestry Systems, 2011)

Glucose-Induced Regulation of NHEs Activity and SGLTs Expression Involves the PKA Signaling Pathway - Olívia Beloto-Silva; Ubiratan Fabres Machado; Maria Oliveira-Souza (The Journal of Membrane Biology, 2011)

Enzymatic Activity, Sensitivity to Antifungal Drugs and Baccharis dracunculifolia Essential Oil by Candida Strains Isolated from the Oral Cavities of Breastfeeding Infants and in Their Mothers’ Mouths and Nipples - Cristiane Aparecida Pereira; Anna Carolina Borges Pereira da Costa; Ana Karina Silva Machado; Miltom Beltrame Júnior; Maria Stella Amorin Costa Zöllner; Juliana Campos Junqueira; Antonio Olavo Cardoso Jorge (Mycopathologia, 2011)

Cell wall alterations in the leaves of fusariosis-resistant and susceptible pineapple cultivars - Glória Maria de Farias Viégas Aquije; Poliana Belisário Zorzal; David Shaun Buss; José Aires Ventura; Patricia Machado Bueno Fernandes; Antonio Alberto Ribeiro Fernandes (Plant Cell Reports, 2010)

Evaluation of the cytotoxic and antimutagenic effects of biflorin, an antitumor 1,4 o-naphthoquinone isolated from Capraria biflora L - Marne C. Vasconcellos; Dinara J. Moura; Renato M. Rosa; Miriana S. Machado; Temenouga N. Guecheva; Izabel Villela; Bruna F. Immich; Raquel C. Montenegro; Aluísio M. Fonseca; Telma L. G. Lemos; Maria Elisabete A. Moraes; Jenifer Saffi; et al. (Archives of Toxicology, 2010)

Saccharomyces cerevisiae strain UFMG 905 protects against bacterial translocation, preserves gut barrier integrity and stimulates the immune system in a murine intestinal obstruction model - Simone V. Generoso; Mirelle Viana; Rosana Santos; Flaviano S. Martins; José A. N. Machado; Rosa M. E. Arantes; Jacques R. Nicoli; Maria I. T. D. Correia; Valbert N. Cardoso (Archives of Microbiology, 2010)

Influence of trees on soil nutrient pools in a silvopastoral system in the Brazilian Savannah - Guilherme Lanna Reis; Ângela Maria Quintão Lana; Rogério Martins Maurício; Regina Maria Quintão Lana; Rodrigo Matta Machado; Iran Borges; Talmir Quinzeiro Neto (Plant and Soil, 2010)

Developmental and structural features of secretory canals in root and shoot wood of Copaifera langsdorffii Desf. (Leguminosae–Caesalpinioideae) - Tatiane Maria Rodrigues; Silvia Rodrigues Machado (Trees, 2009)

Molecular characterization of a putative heat shock protein cognate gene in Rhynchosciara americana - Alexandre de Andrade; Fabio Siviero; Paula Rezende-Teixeira; Roberto Vicente Santelli; Glaucia Maria Machado-Santelli (Chromosome Research, 2009)

The R2 mobile element of Rhynchosciara americana: Molecular, cytological and dynamic aspects - Paula Rezende-Teixeira; Fábio Siviero; Marina da Costa Rosa; Glaucia Maria Machado-Santelli (Chromosome Research, 2009)

Melatonin does not affect the black pigment migration in the crab Neohelice granulata - Fábio E. Maciel; Márcio A. Geihs; Marcelo A. Vargas; Bianca P. Ramos; Bruno P. Cruz; Maria S. L. Machado; Ana M. C. Filadelfi; Fernando M. Louzada; Luiz E. M. Nery (Biologia, 2009)

Erythrocytary Zinc and the Infant Growth Profile in Northeast Brazil - Gildene Alves da Costa; Dilina do Nascimento Marreiro; Juliana Maria Libório Eulálio; José Machado Moita Neto; Amanda Castro Amorim; Apolônia Maria Tavares Nogueira; Semíramis Jamil Hadad do Monte; Nadir do Nascimento Nogueira (Biological Trace Element Research, 2008)

Resveratrol attenuates cisplatin-induced nephrotoxicity in rats - Cátia Lira Do Amaral; Heloísa Della Coletta Francescato; Terezila Machado Coimbra; Roberto Silva Costa; Joana D’arc Castania Darin; Lusânia Maria Greggi Antunes; Maria De Lourdes Pires Bianchi (Archives of Toxicology, 2008)

Photosynthetic limitation by CO2 diffusion in drought stressed orange leaves on three rootstocks - Norma de Magalhães Erismann; Eduardo Caruso Machado; Maria Luiza Sant’ Anna Tucci (Photosynthesis Research, 2008)

Cowpea ribonuclease: properties and effect of NaCl-salinity on its activation during seed germination and seedling establishment - Enéas Gomes-Filho; Carmen Rogélia Farias Machado Lima; José Hélio Costa; Ana Cláudia Marinho da Silva; Maria da Guia Silva Lima; Claudivan Feitosa de Lacerda; José Tarquinio Prisco (Plant Cell Reports, 2008)

Biochemical and Genetic Polymorphisms for Carboxylesterase and Acetylesterase in Grape Clones of Vitis vinifera L. (Vitaceae) Cultivars - Gleice Ribeiro Orasmo; Sandra A. Oliveira-Collet; Ana Sílvia Lapenta; Maria de Fátima P. S. Machado (Biochemical Genetics, 2007)

Immobilization of Psilocybe castanella on ceramic (slate) supports and its potential for soil bioremediation - Luciana Cristina Amaral Compart; Kátia Maria Gomes Machado; Dácio Roberto Matheus; Antonio Valadão Cardoso (World Journal of Microbiology and Biotechnology, 2007)

New insights into the in vitro organogenesis process: the case of Passiflora - Juliana A. Fernando; Maria Lúcia C. Vieira; Silvia R. Machado; Beatriz Appezzato-da-Glória (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Zooplankton biomass in tropical reservoirs in southern Brazil - Claudia Costa Bonecker; Mariza Yuri Nagae; Martin Cesar Maria Bletller; Luiz Felipe Machado Velho; Fábio Amodêo Lansac-Tôha (Hydrobiologia, 2007)

Tomato root distribution, yield and fruit quality under different subsurface drip irrigation regimes and depths - Rui M. A. Machado; Maria do Rosàrio G. Oliveira (Irrigation Science, 2005)

Thermal Stability and Activity Regain of Horseradish Peroxidase in Aqueous Mixtures of Imidazolium-Based Ionic Liquids - Maria Fátima Machado; Jorge Manuel Saraiva (Biotechnology Letters, 2005)

Biodegradation of pentachorophenol by tropical basidiomycetes in soils contaminated with industrial residues - Kátia Maria Gomes Machado; Dácio Roberto Matheus; Regina Teresa Rosim Monteiro; Vera Lúcia Ramos Bononi (World Journal of Microbiology and Biotechnology, 2005)

Diversity, floristic and structural patterns of cerrado vegetation in Central Brazil - Jeanine Maria Felfili; Manoel Cláudio da Silva Júnior; Anderson Cássio Sevilha; Christopher William Fagg; Bruno Machado Teles Walter; Paulo Ernane Nogueira; Alba Valéria Rezende (Plant Ecology, 2004)

Soil Respiration and Carbon Storage of an Acrisol Under Forest and different Cultivations in rio de Janeiro State, Brazil - John E.L. Maddock; Maria B.P. Dos Santos; Sonia R.N. Alves de Sá; Pedro L.O. de A. Machado (Environment, Development and Sustainability, 2004)

Breast cancer micrometastases: Different interactions of carcinoma cells with normal and cancer patients' bone marrow stromata - Maria-Helena A. Nicola; Rosana Bizon; Janaina J.S. Machado; Tereza Sollero; Renato S. Rodarte; João S. Nobre; Maurício M. Magalhães; Christina M. Takiya; Radovan Borojevic (Clinical & Experimental Metastasis, 2003)

Comparison of tomato root distributions by minirhizotron and destructive sampling - Rui M.A. Machado; Maria do Rosário G. Oliveira (Plant and Soil, 2003)

Tomato root distribution, yield and fruit quality under subsurface drip irrigation - Rui M.A. Machado; Maria do Rosário; G. Oliveira; Carlos A. M. Portas (Plant and Soil, 2003)

Developmental changes in the ploidy of mouse implanting trophoblast cells in vitro - Cláudia Regina Gonçalves; Sylvie Antonini; Angela M. Vianna-Morgante; Gláucia Maria Machado-Santelli; Estela Bevilacqua (Histochemistry and Cell Biology, 2003)

RAPD Markers to Evaluate Callus Tissue of Cereus peruvianus Mill. (Cactaceae) Maintained in Different Growth Regulator Combinations - Claudete A. Mangolin; Laura M. M. Ottoboni; Maria de Fátima P. S. Machado (Biochemical Genetics, 2002)

Differential Esterase Expression in Developmental Mutants of Aspergillus nidulans - Maria de Fátima P. S. Machado; Marialba A. A. de Castro-Prado (Biochemical Genetics, 2001)

Differential Esterase Expression in Leaves of Manihot esculenta Crantz Infected with Xanthomonas axonopodis pv. manihotis - Álvaro Júlio Pereira; Ana Sílvia Lapenta; Pedro Soares Vidigal-Filho; Maria de Fátima P. S. Machado (Biochemical Genetics, 2001)

Improved detection methods for fruit tree phytoplasmas - Maria Heinrich; Simona Botti; Licia Caprara; Wolfgang Arthofer; Sabine Strommer; Veronika Hanzer; Hermann Katinger; Assunta Bertaccini; Margit Laimer Da Câmara Machado (Plant Molecular Biology Reporter, 2001)

Ligninolytic activity of tropical rainforest basidiomycetes - Luci Kimie Okino; Kátia Maria Gomes Machado; Carla Fabris; Vera Lúcia Ramos Bononi (World Journal of Microbiology and Biotechnology, 2000)

Isozyme Diversity in Cassava Cultivars (Manihot esculenta Crantz) - Adriana Gazoli Resende; Pedro Soares Vidigal Filho; Maria de Fátima P.S. Machado (Biochemical Genetics, 2000)

THE ROLE OF LOCAL CIRCULATIONS IN SUMMERTIME CONVECTIVE DEVELOPMENT AND NOCTURNAL FOG IN SÃO PAULO, BRAZIL - MARIA A. F. SILVA DIAS; ANTONIO JASCHKE MACHADO (Boundary-Layer Meteorology, 1997)